Distance metrics for ecological niche modeling: beyond a chi-squared correction - Luíz Fernando Esser; Matheus Baumgartner; Dayani Bailly; Marcos Robalinho Lima; Reginaldo Ré (Ecological Modelling, 2026)

Fetal pneumonia and polyarthritis associated with Ureaplasma diversum infection in an aborted beef cattle fetus in Brazil - Letícia Perri Luciano; Roger Fernando Neves da Silva; Wuglenya Daislla Martins da Silva; Ícaro Guilherme dos Santos; Bruna Souza Serrano; Gabriela Viana Castilho Bichara; Maria Sinara Matos; Fabricio Andrade Gomes; Nataliê Ecker; Tayane Bruna Soares Magalhães; Marcos de Almeida Souza; Daniel Moura de Aguiar; et al. (Veterinary Research Communications, 2026)
Ureaplasma diversum is an opportunistic bovine pathogen associated with reproductive disorders, including infertility, granular vulvovaginitis, placentitis, and abortion; however, detailed descriptions of fetal osteoarticular lesions remain exceptionally uncommon. This report describes the gross, histopathological, and molecular findings of a bovine abortion associated with U. diversum infection presenting with concurrent pulmonary and articular lesions, representing an uncommon manifestation in bovine fetuses in Brazil. An approximately six-month-old Angus fetus was submitted for complete postmortem examination following abortion. Tissue samples were collected for histopathology and molecular investigation of major infectious agents associated with bovine reproductive failure. Gross examination revealed bilateral coxofemoral joint lesions characterized by articular cartilage irregularity and erosions. Histologically, the lungs exhibited moderate multifocal pyogranulomatous pneumonia with prominent bronchus-associated lymphoid tissue (BALT) hyperplasia. The coxofemoral joints showed severe multifocal subacute erosive fibrinonecrotizing arthritis with proliferative lymphoplasmacytic synovitis and secondary osteonecrosis. Histologically, fibrovascular pannus formation, cartilage necrosis, and extension of the lesion into the subchondral bone were observed. Quantitative PCR detected U. diversum DNA in brain, spleen, thymus, liver, and kidney, whereas the paraffin-embedded coxofemoral joint sample tested negative. Molecular assays for other major abortifacient pathogens, including bovine viral diarrhea virus (types 1, 2, and 3), bovine herpesvirus 1 and 6, Leptospira spp., Brucella abortus , Mycoplasma bovis , and Neospora caninum were negative. The exclusion of other common infectious causes, combined with the molecular confirmation of U. diversum and the characteristic inflammatory lesions, support an etiological association between U. diversum infection and the abortion. These findings expand the pathological spectrum of U. diversum infection in bovine fetuses, particularly regarding osteoarticular involvement, and emphasize the diagnostic value of systematic joint evaluation combined with molecular testing in bovine abortion investigations.

A comprehensive overview of evolutionary relationships and geographic distributions of cownose rays: more valid taxa needing protective measures - Yasmim Trindade C. Cunha; Renata Daldin Leite; Lucas Gabriel Pereira da Silva; Vanessa Paes Cruz; Jorge Luiz S. Nunes; Matheus Marcos Rotundo; Paola Palacios-Barreto; Píndaro Diaz-Jaimes; Ana P. Barbosa Martins; M. Aaron Macneil; Chris G. Mull; José Augusto Pires Bitencourt; et al. (Reviews in Fish Biology and Fisheries, 2026)
Rays of the family Rhinopteridae Jordan & Evermann, 1896 are highly migratory and widely distributed in warm tropical and temperate waters. Along the Brazilian coast, the presence of two species has been recorded: Rhinoptera bonasus Mitchill, 1815 and Rhinoptera brasiliensis Müller, 1836. These stingrays are commonly caught as bycatch in trawl fisheries, however, the two species lack distinctive external morphological features that allow for reliable differentiation—species identification is primarily based on the shape and arrangement of teeth in the buccal plates. This study aimed to investigate the evolutionary history of the genus Rhinoptera and to explore which evolutionary drivers, such as biogeographic events or behavioral traits, have influenced its diversification. To achieve this, we analyzed both mitochondrial and nuclear genetic markers, focusing on the species occurring along the Brazilian coast. Specimens of both species were collected across various locations in Brazil, and additional sequences from other Rhinoptera species were obtained from GenBank. Our results reveal the presence of multiple cryptic species within Rhinoptera , particularly within R. bonasus , and likely in Rhinoptera steindachneri Evermann & Jenkins, 1891 and Rhinoptera javanica Müller & Henle, 1841. Notably, R. bonasus does not occur in Brazilian waters nor in parts of the Caribbean where a distinct cryptic sister lineage was identified. Based on our findings, we propose the resurrection of Rhinoptera lalandii Müller & Henle, 1841 as the species representing the lineage found along the Brazilian coast and the Eastern Atlantic Ocean. We suggest that philopatric behavior may represent one of several factors potentially influencing diversification within Rhinopteridae, although this hypothesis requires direct behavioral and population level validation. These findings highlight the urgent need for a comprehensive taxonomic revision of the family, as well as a reassessment of current conservation strategies to better reflect the hidden diversity within this group of species. Graphical abstract

Host-pathogen interactions during early stages of bovine mastitis: divergent macrophage responses to distinct bovine-associated Staphylococci species and strains - Sarah Antonieta de Oliveira Veríssimo; Ygor Fagundes Ruas; Filipe Aguera Pinheiro; Luiza Campos Reis; Bernardina Amorim Uscata; Hiro Goto; Soraia Araújo Diniz; Adriana Cortez; Sarne De Vliegher; Marcos Bryan Heinemann; Eduardo Milton Ramos-Sanchez; Fernando Nogueira de Souza; et al. (Brazilian Journal of Microbiology, 2026)
Background Bovine mastitis is the most economically significantdisease in dairy farming, with Staphylococcus aureus and Staphylococcus chromogenes asprominent agents, the former posing a major threat. As principal immune sentinels in themammary gland, macrophages orchestrate early pathogen recognition and immune activation,critically influencing the trajectory and outcome of infection. Thus, this study aimed tocharacterize the early macrophage responses to distinct bovine-associated S. aureus and S.chromogenes strains. Methods Here, RAW 264.7 cells were challenged with four differentstrains: S. aureus [isolated from nose (SN), and intramammary infection (IMI)] and S.chromogenes [IMI, and teat apex (TA)] were evaluated after 90- and 180-min. Nitric oxide (NO)production was analyzed in the supernatants, and mRNA levels of IL-1β, IL-18, NLRP3, NOS2,Arg1, Bax, and Bcl2 were assessed in the cells. Results Macrophages challenged with S. aureusIMI strains showed elevated Nos2 expression but negligible NO production, indicating a potentialimmune evasion mechanism. The commensal S. aureus SN strain uniquely maintained arginaseexpression, suggesting M2-like polarization that may promote immune tolerance and bacterialcolonization. Both S. aureus strains significantly upregulated the anti-apoptotic Bcl2 gene, atranscriptional response that may be associated with host cell survival, which may facilitatebacterial intracellular persistence. In contrast, S. chromogenes strains induced strong NOS2expression, robust NLRP3 inflammasome activation, and increased IL-1β production, indicatingM1 polarization and a pro-inflammatory response. The pro-apoptotic Bax gene showed an earlydecrease followed by a later increase exclusively in S. aureus-infected macrophages, indicating atime-dependent transcriptional modulation of apoptosis-related genes. Conclusions Thesegenotype-dependent macrophage responses reveal complex immune modulation shaping mastitis pathogenesis. However, our findings are based solely on transcriptional data on the murine cells and require further validation.

The silent invasion of anthropogenic plastic debris in an isolated protected area in Antarctica - Jorge Renato Pinheiro Velloso; Pamela Cristina Cazaroto; Fernando Augusto Bertazzo-Silva; Marcos André Pinheiro Velloso; Carlos Ernesto Reynaud Gonçalves Schaefer; Jair Putzke (Marine Pollution Bulletin, 2026)

Eclipta prostrata extract and wedelolactone antagonize Apis mellifera venom activities - Pâmella Dourila Nogueira-Souza; José Roberto da Silva Rocha-Junior; Mayara A. Romanelli; Marcos Monteiro-Machado; Tulio Santos Siqueira Peçanha; Matheus Magalhães de Almeida; Fernando Chagas Patrão-Neto; Paulo A. Melo (Toxicon, 2026)

Global genome-wide patterns of genetic diversity and population structure in Coryphaena hippurus - Píndaro Díaz Jaimes; Verónica Mendoza-Portillo; Silvia Hinojosa-Alvarez; Erika Magallón-Gayón; Rocío Alejandra Chavez-Santoscoy; Jesús Hernández-Pérez; Adán Fernando Mar-Silva; Maried Ochoa-Zavala; Sofia Ortega-Garcia; Oscar Lao; Marco Arculeo (Molecular Phylogenetics and Evolution, 2026)

Linking Neoarchean hydrothermal nickel and IOCG mineralization at the Jaguar Norte Cu–Ni deposit, Carajás Mineral Province (Brazil): constraints from multi-mineral petrological, isotopic, and geochronological data - Laryssa S. Carneiro; Carolina P.N. Moreto; Lena V.S. Monteiro; Marco A.D. Silva; Roberto P. Xavier; Bruno V. Ribeiro; Margareth S. Navarro; Ezequiel Pozocco; Juliana A. Carvalho; Ivandro S. Prado; Fernando M.V. Matos (Precambrian Research, 2026)

Presence of antibodies against Chlamydia spp. in sheep with and without a history of abortion in the State of Mexico sheep production units - María Guadalupe Martínez Serrano; Luis Enrique Vilchis Ceballos; Berenice Guadalupe Alaníz García; Marco Antonio Rodríguez Chávez; Sergio David Zavaleta Iglesias; Nancy Guadalupe Flores Jiménez; José Francisco Morales Álvarez; Fernando Balderas Flores; Rosa Isabel Higuera Piedrahita (Next Research, 2026)

Staphylococcus in the One Health era: genomic insights and ecological roles reshaping food safety from farm to fork - Ygor F Ruas; Marcos B Heineman; Fernando N Souza (Current Opinion in Food Science, 2026)

High prevalence of Giardia spp. in cats without diarrhea and agreement between diagnostic techniques in the municipality of Londrina, Paraná, Brazil - Luiz Roberto Santos Aoki; Fernando de Souza Rodrigues; Giovanna Cristina Justino Santos Aoki; Lethicia Mendes Nino; Mateus Siqueira Pyles; Michel dos Santos Pinto; Michelle Santos Sabioni; João Alfredo Biagi Camargo Neto; Alex Akira Nakamura; Katia Denise Saraiva Bresciani; Gustavo Felippelli; Marcos Franke Pinto (Veterinary Research Communications, 2026)
In this study, we conducted an epidemiological investigation and analyzed the agreement between the Faust technique and the immunochromatographic assay in the diagnosis of Giardia spp. in 272 cats in the municipality of Londrina, Paraná state, Brazil. We identified an overall prevalence of 74.63% (203/272 [95% CI: 69.14–79.44%]) of Giardia spp. in cats, being significantly higher in adult and non-domiciled animals, which presented, respectively, 5.3 and 8.6 times more chances of infection when compared to kittens and domiciled animals. However, all the animals investigated that tested positive did not present with diarrhea. Regarding diagnostic methods, using coproparasitological examination, Giardia spp. cysts were observed in the feces of 193 cats, and through the immunochromatographic assay, coproantigens of this protozoan were detected in 203 samples, demonstrating almost perfect agreement ( Kappa Cohen: 0.907). Thus, according to the authors’ knowledge, this is the highest prevalence of Giardia spp. ever identified in cats in Brazil, and with regard to diagnostic methods, we observed a high concordance between the coproparasitological examination and the immunochromatographic assay in the detection of the aforementioned protozoan.

Jaguar Range‐Wide Connectivity: Prioritising Core Areas and Corridors Between and Within Protected Areas and Indigenous Lands - Guilherme Costa Alvarenga; Caroline C. Sartor; Ana Carolina Srbek‐Araujo; Ana Cristina Mendes‐Oliveira; Bart Harmsen; Carlos De Angelo; Carolina Franco Esteves; Claudia Bueno de Campos; Daiana Jeronimo Polli; Diego F. Passos Viana; Diogo Maia Gräbin; Emiliano Donadio; et al. (Global Change Biology, 2026)
Anthropogenic habitat transformation has led to population declines and increasing isolation of populations of many species, particularly top predators, where small and fragmented populations often experience limited dispersal and reduced genetic diversity. Jaguars ( Panthera onca ), for example, have lost half of their historical range and most populations outside the Amazon biome are small, isolated and highly threatened. Here, we assess jaguar population connectivity across the species' range by identifying and ranking core areas and dispersal corridors, including linkages among Protected Areas and Indigenous Lands (hereafter, PAs). We used cumulative resistant kernels and factorial Least‐Cost Paths (fLCP) in two complementary approaches: core area‐based and PA‐based connectivity. We identified 307 core areas for jaguar movement, covering ~7.75 million km 2 (55% of the current range), of which approximately half lies within PAs. The largest and highest‐ranked core area spans ~6.5 million km 2 across four biomes (Amazon, Llanos, Chaco and Pantanal). We identified 176 dispersal corridors connecting core areas, although connectivity was not continuous across the entire range. Northern populations (Mexico and Central America) showed several connectivity gaps, whereas South America displayed a large, highly interconnected network linking the Amazon, Llanos, Chaco, Pantanal, Cerrado, Caatinga, Iberá and the Atlantic Forest's Green Corridor. In contrast, coastal Atlantic Forest patches appeared largely isolated. The PA‐based analysis predicted 507 potential corridors connecting 905 PAs, including potential links absent from the core area model, particularly across Central America and between the Darién Gap, Amazon and coastal Atlantic Forest. The core‐area approach provides a more biologically realistic representation of current connectivity, while the PA‐based approach complements it by identifying pragmatic opportunities for long‐term connectivity conservation. Together, these approaches identify priority areas and regions of uncertainty, providing a spatial framework to guide jaguar conservation and connectivity planning under accelerating global change.

MIL-53(Fe)-mediated persulfate activation for the removal of pesticides-contaminated water: phytotoxicity evaluation, theoretical reactivity prediction and by-products degradation pathways - Muriel R. Affonso; Igor G.S. Oliveira; Fernando C. Gallina; Beatriz T. Marin; João P.P. Encide; Micael M. Baruch; Robson S. Souto; Renata Colombo; Kathia M. Honorio; Marcos R.V. Lanza; Willyam R.P. Barros (Chemical Engineering Journal, 2026)

Effect of founder breeds on genotype imputation accuracy in Canchim cattle - Roney Teixeira; Maria Victória Henrique Genuíno; Ayrton Fernandes de Oliveira Bessa; Giovanna Maria dos Santos Câmara; Ana Carolina de Jesus Oliveira; Josineudson Augusto II de Vasconcelos Silva; Lucio Flavio Macedo Mota; Fernando Baldi; Luciana Correia de Almeida Regitano; Cintia Righetti Marcondes; Priscila Arrigucci Bernardes; Donagh Pearse Berry; et al. (Journal of Applied Genetics, 2026)

Integrin inhibition differentially remodels vascular networks in lung metastases driven by vessel co-option or angiogenesis - Laura Marcos-Zazo; Iván Carrera-Aguado; Jesús Gómez-Escudero; Patricia Berlana-Galán; Irene Torre-Cea; Elena Guerra-Paes; Celia Redondo-Gonzalez; Juan Sánchez-Mateos; Daniel Cáceres-Calle; Óscar Maiques; Miguel Pericacho; Susana Fraile; et al. (Angiogenesis, 2026)
Tumor progression depends on an adequate blood supply to sustain oxygen and nutrients delivery. While tumor angiogenesis involves the formation of new blood vessels from pre-existing ones, vessel co-option represents a non-angiogenic vascularization strategy whereby tumor cells utilize pre-existing host vessels. Co-opted vessels have been considered refractory to anti-angiogenic therapies, and pharmacological modulation of co-opted vessels remains limited. In this study, we investigate the effects of low-dose cilengitide on tumor vascular remodeling in vessel co-option and angiogenic metastatic models. Our results reveal that cilengitide exerts distinct vascular effects depending on the mode of tumor vascularization. In vessel co-option-driven tumors, cilengitide treatment is associated with the remodeling of the co-opted vasculature into a more organized normalized vascular network, characterized by an increased number of functional blood vessels and enhanced vascular barrier integrity. In contrast, in angiogenic-driven tumors, cilengitide treatment promotes an expansion of the vascular network consistent with augmented, but structurally immature angiogenesis. Importantly, vascular remodeling in vessel co-option metastases is accompanied by enhanced blood vessel perfusion and reduced hypoxia, which correlates with enhanced responsiveness to chemotherapy. Conversely, in angiogenic metastases, the vascular network induced by low-dose cilengitide fails to support immunocompetent microenvironmental features and is associated with increased chemotherapy resistance. This study provides the first evidence that co-opted vasculature can be therapeutically targeted via integrin inhibition, suggesting vascular normalization remodeling as a potential strategy to overcome resistance in tumors undergoing vessel co-option.

Urban aerosols and the intensification of maximum air temperature in a tropical Amazonian city - Rafael Palácios; Marco A. Franco; Fernando G. Morais; Maurício Moura; Francisco de Souza Oliveira; Glauber Cirino; Breno Imbiriba; Leone F.A. Curado; João Basso; Thiago R. Rodrigues; Amaury de Souza; Julia Cohen; et al. (Urban Climate, 2026)

Associations between teat apex, milk microbiota, and udder health in primiparous cows: Effects of decontamination in a low biomass context - José A. Ferronatto; Eduardo M. Ramos-Sanchez; Erika K. Ganda; Marcos B. Heinemann; Juliano L. Gonçalves; Marcos V. dos Santos; Julia A. Arantes; Vinicius S. Duarte; Alessandro S. Guimarães; Marcio C. Costa; Marie Joossens; Sarne De Vliegher; et al. (Research in Veterinary Science, 2026)

Giant paraovarian cyst causing abdominal distention in a Swiss mouse (Mus musculus) - Daniel F. Barrantes Murillo; Luis J. Alfaro Quillas; Regina C. Rodrigues da Paz; Fernando H. Furlan Gouvêa; Caroline Argenta Pescador; Marcos de Almeida Souza (Journal of Comparative Pathology, 2026)

Nuclear receptor disruption contributes to 2,4-dichlorophenol-induced developmental toxicity: Evidence from network toxicology and zebrafish analysis - Rafael Xavier Martins; Romério de Oliveira Lima Filho; Cleyton de Sousa Gomes; Matheus Carvalho; Maria Eduarda de Souza Maia; Bianca Mataribu; Catarina Serrão; Marcos Vinicius Porto Medeiros; Milena Pereira Arruda; Ana Julia Antunes de Magalhães; Juliana Alves da Costa Ribeiro Souza; Thaís Feitosa Guimarães; et al. (Environmental Research, 2026)

Impact of Pre-planting Inoculation with Phosphorus-solubilizing Bacteria on Potato Tuber Quality during Storage - Tainá Ferreira da Rocha; Fernando Angelo Piotto; Maria Carolina Quecine; Carlos Alberto Quiloango-Chimarro; Jéfferson de Oliveira Costa; Ralph Bonandi Barreiros; Marcos Fabián Sanabria Franco; Ricardo Alfredo Kluge (Potato Research, 2026)

Abundant Development of Agaricales Fungi on Livingston Island, Antarctica: Potential Connections to Climate Change - Fernando Augusto Bertazzo-Silva; Flavia Helena Aires Sousa; Kamille Rodrigues Ferraz; Jorge Renato Pinheiro Velloso; Evelise Leis Carvalho; Marcos André Pinheiro Velloso; Vanessa dos Anjos Baptista; Adriano Luis Schünemann; Carlos Ernesto Gonçalves Reynaud Schaefer; Jair Putzke (Current Microbiology, 2026)
Rapid warming across Antarctica is reshaping terrestrial ecosystems, yet the dynamics of macroscopic fungi in this region remain largely undocumented. Here, we present the first ecological and statistical assessment of Agaricales fungi on Byers Peninsula, Livingston Island (South Shetland Islands, Antarctica), based on surveys conducted in February 2023. Across 20 sites, we recorded 2,566 basidiomes representing eight morphospecies in three genera ( Arrhenia, Galerina, and Omphalina ). Community diversity was moderate (Shannon–Wiener H′ = 1.97; Simpson’s D = 0.85), with assemblages dominated by Omphalina (68.4% of basidiomes), while Arrhenia sp. 1 displayed the broadest spatial distribution (65% of sites). Spatial analyses revealed significant variation in Agaricales abundance among sites (ANOVA, p = 0.016), while multivariate ordination (NMDS based on Bray–Curtis dissimilarity) showed substantial overlap in morphospecies composition across dominant vegetation types, with no significant differences detected by PERMANOVA (p = 0.527). The emergence of diverse basidiome assemblages in such an extreme environment underscores the ecological relevance of fungi in polar ecosystems and highlights their potential as sensitive bioindicators of climate-driven change. This quantitative baseline provides a critical reference for long-term monitoring and advances understanding of fungal contributions to biogeochemical processes in a rapidly changing Antarctic landscape.

Mapping the advancements in floristic knowledge of Italy (2005–2025) - Gianniantonio Domina; Gianluigi Bacchetta; Fabrizio Bartolucci; Marco D’Antraccoli; Lorenzo Peruzzi; Adriano Stinca; Alessandro Alessandrini; Liliana Bernardo; Francesco Boscutti; Daniela Bouvet; Maurizio Bovio; Giacomo Calvia; et al. (Plant Biosystems, 2026)
Based on the evaluation of 3,902 local floristic references published between 2005 and 2025, an update to the floristic knowledge map of Italy is presented. To measure the progress in floristic knowledge across Italy’s administrative regions, the ‘Index of Floristic Knowledge Advancement’ (IFA) is proposed here. This index categorizes regions based on the proportion of potential improvement that has actually been achieved. Results showed an improvement in knowledge, most notably for Northern and Central Italy. Emilia-Romagna emerged as the most comprehensively documented region with the highest IFA value (0.81), followed by Lombardia (0.60), Friuli-Venezia Giulia (0.54), Trentino-Alto Adige and Veneto (0.53). In central Italy, Lazio (0.50), Sardegna (0.45) and Toscana (0.36) registered the highest scores. Over the past twenty years, 453 specific and subspecific taxa have been described from the Italian territory, the majority of which (443) are Italian endemics. Hieracium is the most represented genus (147 taxa). The marked progress documented is likely due to the accelerated impact of coordinated scientific projects, citizen science programs, the development of digital databases, and an increased focus on taxonomic research.

Biocontrol potential of anthracnose in sorghum by Bacillus spp. and its lipopeptide extracts - Nataniel Osmar Risse; Evilyn Eduarda Prandini Santana; Vinicius Facin Nugoli; Fernanda Koch; Marco Antonio Bacellar Barreiros; Luciana Grange; Vivian Carré Missio; Robson Fernando Missio (BioControl, 2026)
Climate change is increasing constraints on crop production and reinforcing the need for sustainable alternatives to chemical disease control. Sorghum is a drought-tolerant crop of increasing importance. However, anthracnose caused by Colletotrichum sublineola remains its most destructive disease, and no biological control products are currently registered for its management. This study evaluated bacterial isolates as potential biological control agents against sorghum anthracnose. Bacteria isolated from honey were identified as Bacillus spp. based on 16S rDNA sequencing and screened for antifungal activity in vitro . Four isolates inhibited mycelial growth of C. sublineola by more than 67%. Lipopeptide extraction and characterization confirmed the production of surfactin, fengycin, and iturin. Greenhouse assays demonstrated that bacterial cell suspensions reduced symptomatic leaf area by 40%, whereas lipopeptide extracts reduced disease severity by 77% and significantly increased the chlorophyll index. The most effective treatments were further evaluated under field conditions, confirming their effects on disease suppression and plant physiological performance. Three Bacillus isolates showed strong potential for biological control of sorghum anthracnose using both talc-based formulations and lipopeptide extracts. Further studies are required to optimize formulation stability and assess long-term field efficacy.

Expert‐Based Prioritization of Control Measures for Salmonid Rickettsial Septicemia in Chilean Salmon Aquaculture - Patricio Bustos; Benjamín Diethelm‐Varela; Andrés Riofrio; Marcos Mancilla; Fernando O. Mardones (Journal of Fish Diseases, 2026)
Piscirickettsiosis (SRS) remains the main infectious disease affecting salmon aquaculture in Chile. This study evaluated expert perceptions of the effectiveness of SRS control measures and the level of agreement among industry professionals. A structured cross‐sectional expert‐elicitation survey was conducted with nine head fish health managers representing more than half of the Chilean Atlantic salmon and rainbow trout production. Experts scored 67 control measures using a 5‐point Likert scale, and effectiveness and consensus were assessed using descriptive and variability metrics. Measures related to biosecurity, mortality management, and production practices ranked highest and showed strong agreement. Therapeutic and vaccination‐related measures showed heterogeneous levels of agreement: several specific antimicrobial protocols (oral florfenicol, injectable oxytetracycline monotherapy, and combination florfenicol + oxytetracycline therapy) reached high consensus, while other therapeutic measures and most vaccination strategies exhibited substantially greater variability. The integration of effectiveness and consensus enabled classification of measures into priority tiers, consistently highlighting preventive strategies as high priority. These findings provide a structured, practice‐oriented framework to support decision‐making and reinforce the importance of management‐based approaches for SRS control under field conditions.

Foliar Spraying of Silicon and Titanium Nanoparticles: Biometrics and Mineral Nutrition of Maize - João Henrique Vieira de Almeida; Ana Clara Pereira de Souza Verginio; Fernando Marcos Brignoli; Lucas Hiroshi Suguiura; Tadeu Takeyoshi Inoue; Marcelo Augusto Batista (Journal of Soil Science and Plant Nutrition, 2026)
Purpose: Recent studies highlight the potential of silicon (Si) and titanium (Ti) nanoparticles (NPs) in agriculture, particularly for foliar application. This study aimed to evaluate the effects of foliar-applied Si and Ti NPs on biometric parameters, chlorophyll content, and nutrient uptake by maize. Methods: The experiment was conducted in a completely randomized design with four replications. Concentration of 0, 50, 100, and 200 mg L⁻¹ of Si and Ti were tested in both NP and bulk forms. Root length, root dry mass (RDM), shoot dry mass (SDM), SPAD index, and nutrient content in the SDM were determined. Results: The maximum root length (58 cm) was observed at the 24 mg L⁻¹ dose of TiO 2 NPs. Both SiO 2 and TiO 2 NPs increased shoot length and RDM, with optimal concentration ranging from 164 to 200 mg L⁻¹ for SiO 2 and from 50 to 86 mg L⁻¹ for TiO 2 . SPAD index increased with SiO 2 NPs up to 133 mg L⁻¹. TiO 2 NPs enhanced K content up to 120 mg L⁻¹ and increased P, Ca, Mg, Cu, and Zn concentrations. SiO 2 NPs raised P, Ca, and Mg contents but reduced Fe concentration up to 130 mg L⁻¹. Conclusions: Foliar-applied SiO 2 and TiO 2 NPs altered maize biometric and nutritional traits, indicating beneficial effects associated with both elemental composition and nanoscale properties.

Genome-resolved characterization of microbial consortia driving glyphosate degradation in soil - Mariana Prósperi de Oliveira Paula; Alessandro de Mello Varani; Vitor Luciano Costa da Silva; Luiz Fernando Wurdig Roesch; Marcos Rogério Tótola; Alessandro Coutinho Ramos; Victor Satler Pylro (Chemosphere, 2026)

Blue carbon inventories of Spain and Portugal for their inclusion in national climate mitigation strategies - Nerea Piñeiro-Juncal; Oscar Serrano; Carmen B. de los Santos; Nuria Marbà; Elena Díaz-Almela; Fernando Tuya; Inés Mazarrasa; Joxe Mikel Garmendia; Xosé Lois Otero; Karina Inostroza; Jordi F. Pagès; Gonzalo Mendez-Martínez; et al. (Marine Pollution Bulletin, 2026)

Nutritional Efficiency for Fertigated Sugarcane Varieties Under Deficit Irrigation Strategies - Nathália Lopes Ribeiro; Rubens Duarte Coelho; Fernando da Silva Barbosa; Lucas da Costa Santos; Daniel Philipe Veloso Leal; Jonathan Vásquez Lizcano; Eusímio Felisbino Fraga Júnior; Timóteo Herculino da Silva Barros; Marcos Antonio Correa Matos do Amaral; Jéfferson de Oliveira Costa (Irrigation and Drainage, 2026)
Among the many factors that limit sugarcane crop yield, the precise supply of nutrients and water under drip irrigation systems can be the shortcut to higher yields in the field. This research aimed to evaluate the nutritional efficiency of fertigated sugarcane varieties under deficit irrigation strategies. The experiment was conducted in a rain‐out shelter with the soil type Oxisol Typic Ustox. The experimental design adopted was randomized blocks, with three complete blocks. The treatments were distributed in a factorial scheme (4 × 8), totalling 32 treatments and 96 experimental plots. Four irrigation strategies and eight commercial sugarcane varieties (CTC15, CTC17, RB867515, RB92579, RB931011, RB966928, IAC5000 and NCo376) were studied. Leaf, sheath, pointer and stalk samples were ground for determination of macronutrient and micronutrient contents. All the nutrients had greater quantities allocated to the stalk. The CTC15 variety accumulated a greater quantity of nutrients and was more efficient in terms of gross sugar yield, whereas RB966928 was more efficient in terms of the production of total recoverable sugars and the production of apparent sucrose. The 100% irrigation level provided greater accumulation of nutrients in the aboveground parts, whereas the 50% irrigation level resulted in higher values of nutrient use efficiency.

Climate Predicts Tree Dispersal Strategies Across Brazil's Ecosystems - Fernanda C. Souza; Vinícius Andrade Maia; Renata Françoso; Matheus Coutinho Freitas de Oliveira; Ana Beatriz Ligo; Bruno X. Pinho; Jesús Aguirre‐Gutiérrez; Martin Sullivan; Larissa Rocha‐Santos; Laura de Brito Évora; Leonardo de Sousa Miranda; María Natalia Umaña; et al. (Global Ecology and Biogeography, 2026)
Aim We investigate the distribution of dispersal modes — endozoochory (via animal ingestion), synzoochory (via animal seed accumulation) and anemochory (via wind)—and seed mass of woody plants across Brazilian ecosystems, testing whether their relative abundance in local plant communities could be predicted by climate, edaphic factors and dispersal agents (e.g., the main vectors moving seeds). We expected climate to be the main predictor of dispersal strategy abundance. Location Brazilian ecosystems (Amazon, Atlantic Forest, Cerrado and Caatinga). Time Period 2004–2020. Major Taxa Studied Woody angiosperms, trees and shrubs. Methods We assigned seed mass to 1984 species and dispersal mode to 2203 species within 300 old‐growth and non‐flooded plots. We employed Random Forest regressions to assess the influence of water availability, temperature seasonality, soil fertility, wind and frugivorous primates on the community‐weighted means of seed mass and dispersal modes. We mapped predictions and estimated the area of applicability to identify regions where predictions were reliable. Results Climate was the main factor predicting tree dispersal strategies, followed by dispersal agents or soil properties. Endozoochory was prevalent in wetter regions with high water availability and greater diurnal temperature range. Anemochory was more common in drier regions with low water availability, stronger winds and greater diurnal temperature range, whereas synzoochory was more abundant in areas with low temperature seasonality. Heavier seeds were more prevalent in regions with less seasonal temperatures, smaller diurnal temperature ranges and weaker winds. Main Conclusions Climate is a key predictor of the distribution and prevalence of plants with contrasting dispersal modes and seed masses. We thus expect functional responses to environmental change associated with shifts in the relative abundance of dispersal strategies, with implications for ecosystem services. Our results also highlight the critical role of plot‐based datasets in improving our understanding of how environmental factors influence seed dispersal strategies across tropical ecosystems.

Soil Microbial Diversity and Network Organization Respond to Land Use and Agricultural Inputs Worldwide - Zaki Saati‐Santamaría; Sergio Pérez‐Gorjón; Daniel Abel‐Schaad; Alberto Acedo‐Bécares; Francisca Alba‐Sánchez; Amanda Lucia Alves; Weronika Babinska‐Wensierska; Jorge Ariel Marfetán; Carolina Barroetaveña; Kara Barry; Francisco Beitia; Katerina Biniari; et al. (Global Change Biology, 2026)
Soil microbiomes are critical for ecosystem functioning, yet the global influences of climate and agricultural practices on their diversity and structure remain incompletely characterized. Here we analyzed 1921 soil samples from 33 countries worldwide across diverse biomes to assess how climate gradients and agricultural inputs, including pesticides and fertilizers, shape prokaryotic and fungal communities. We found that microbial diversity peaks at intermediate temperatures and differs markedly between natural and agricultural soils, with agriculture increasing microbial diversity while altering community composition and ecological guilds. Pesticide use selectively reduced bacterial diversity and shifted fungal guilds, decreasing ectomycorrhizal fungi while increasing saprotrophs, whereas fertilization reduced microbial network cohesion, with organic and inorganic fertilizers eliciting distinct community responses. These findings reveal that climatic factors and agricultural management jointly influence soil microbial diversity, community structure, and network connectivity, with implications for soil health and ecosystem resilience in managed landscapes. Overall, our results demonstrate that agricultural practices, including the use of pesticides and both organic and inorganic fertilizers, act as strong ecological filters that reshape soil microbiomes worldwide—enhancing apparent diversity but driving a functional shift toward less mutualistic, more fragmented, and potentially less resilient communities.

Limestone Reapplication and Tillage System Influence Non-Exchangeable Aluminum in Subtropical Oxisol - Fernando Marcos Brignoli; Marcela Vágula Gomes Baffa Clavero; João Henrique Vieira de Almeida Junior; Lucas Hiroshi Suguiura; Tadeu Takeyoshi Inoue; Marcelo Augusto Batista (Journal of Soil Science and Plant Nutrition, 2026)
Liming reduces aluminum (Al) toxicity in acidic soils, but its effects on non-exchangeable aluminum (Al ne ) remain unclear. This study evaluated Al fractions and their relationships with soil chemical properties, soybean ( Glycine max L. Merr.) and wheat ( Triticum aestivum L.) yields. The experiment was established in July 2023 in Paraná State, Brazil, on an Oxisol, using a randomized block design in a 4 × 2 factorial arrangement. Treatments consisted of four limestone reapplication rates (0, 1.0, 1.3, and 1.6 times the rate required to reach 70% base saturation) and two application methods (surface application or incorporation into the 0–0.20 m layer). Nine months after reapplication, soil samples from the 0–0.05, 0.05–0.10, and 0.10–0.20 m layers were analyzed. Liming reduced exchangeable aluminum (Al 3+ ) and increased soil organic matter (SOM) in all layers. Non-exchangeable aluminum decreased only in the 0–0.05 m layer. Conventional tillage reduced SOM and increased Al ne by 18% in the surface layer. Non-exchangeable aluminum was positively correlated with potential acidity (H + Al) and negatively correlated with soil pH and base saturation. Wheat yield was more negatively associated with Al ne than soybean yield. Non-exchangeable aluminum correction remained limited to the surface layer regardless of management. Soil disturbance increased Al extractability, indicating greater exposure of reactive Al forms under conventional tillage. Surface liming and no-till favored SOM stability and moderated Al dynamics in subtropical Oxisols.

Hillslope position affects soil nitrogen dynamics and maize fertilizer needs following a cereal rye cover crop - Mila V. Pessotto; Mark A. Licht; Toby A. Adjuik; Fernando M. Marcos; Rashelle Matthiesen; Peter L. O’Brien; Alison Robertson; Marshall D. McDaniel (Field Crops Research, 2026)

Response of Maize To Foliar Spraying of Ag2O and Co3O4 Nanoparticles: Biometric and Nutritional Parameters - João Henrique Vieira de Almeida; Ana Clara Pereira de Souza Verginio; Fernando Marcos Brignoli; Luis Fernando Cipriano Alves Pereira; Tadeu Takeyoshi Inoue; Marcelo Augusto Batista (Journal of Soil Science and Plant Nutrition, 2026)

Improvements in glucose metabolism after high-, but not low-, volume strength exercise in individuals with obesity are associated with baseline insulin resistance: a secondary analysis from a randomized clinical trial - Luis Filipe Rocha Silva; Paulo H. Evangelista Silva; Jordan Ottoni do Carmo; Bruna Caroline Chaves Garcia; Elizabethe Adriana Esteves; Marco Fabrício Dias-Peixoto; Fernando Gripp; Oscar Chavez; Valmor Tricoli; Zachary Aaron Mang; Fabiano Trigueiro Amorim; Flavio de Castro Magalhaes (European Journal of Applied Physiology, 2026)

Identification and antibacterial activity of benzylisoquinoline alkaloids from Berberis empetrifolia L. and Berberis darwinii H. roots - Andrés Pérez-San Martín; Marysol Alvear-Zamora; Fernando Carvajal-Caiconte; Marco Paredes; Nicole Lagos-Arias; Gustavo Curaqueo; Ana Mutis (Natural Product Research, 2026)

Natural Deep eutectic solvents (NADES) for sustainable extraction of phenolic compounds from acerola residue flour - Marcony Edson da Silva Júnior; Nathalia Barbosa da Silva; Ariell Gilmara Carneiro Teófilo Caldas; Paulo Fernando da Silva Ramos; Marcos dos Santos Lima; Maria Inês Sucupira Maciel (Food Research International, 2026)

A survey of vector-borne bacteria in bat-associated mites (Mesostigmata: Macronyssidae and Spinturnicidae) from Brazil reveals the presence of Ehrlichia spp. - Luís Fernando da Cruz; Victor de Souza Mello-Oliveira; Maria Eduarda Moraes das Chagas; Gabriella Soares; Ana Cláudia Calchi; Ana Carolina Castro-Santiago; Leormando Fortunato Dornelas-Júnior; Érica Munhoz de Mello; Igor Massahiro de Souza Suguiura; Elizabete Captivo Lourenço; João Carlos Marocco; Letícia Dorigoni; et al. (Veterinary Research Communications, 2026)

Lack of seasonality on macrobenthic assemblages from a shallow sublittoral sandy mud bottom (Ría de Muros, NW Iberian Peninsula) - Puri Veiga; Raúl Marín-Aragón; Marcos Rubal; Fernando Aneiros; Marina Gómez; Jesús López; Mariano Lastra; Jesús S. Troncoso (Marine Biodiversity, 2026)
One of the bottlenecks to managing ecosystems in sublittoral sediments is the absence of knowledge about their temporal variability that hampers the discrimination between natural and anthropogenic changes. This study investigated how the structure of macrobenthic assemblages and environmental factors in shallow muddy sediments varied according to season. Results showed no evidence of seasonal variability and a low diversity of macrobenthos due to the dominancy of the tube-building annelid Spiochaetopterus costarum. Most of them were burrowers/infauna, which construct burrows in the sediment and can have deep effects on the nearby environment because of bioturbation and bioengineering activities. The main environmental variables responsible for macrobenthic patterns were identified to provide models of abundance, diversity and multivariate structure of assemblages. However, models indicated that most of the variation in macrobenthos remained unexplained by the environmental variables. This study establishes baseline data useful for future monitoring programs, indispensable to detect and ameliorate changes associated with human activities and to design efficient management plans.

The Italian effort toward a coordinated observation of Essential Variables (EOV, ECV, EBV) in European Marine Environments. Long-term observation in the central Mediterranean seas and Italian coasts - Simone Toller; Emilio Urbinati; Debora Bellafiore; Caterina Bergami; Francesca De Pascalis; Marcello G. Magaldi; Marco Bellacicco; Federico Bellati; Maristella Berta; Angelo Boccacci; Roberto Bozzano; Fabio Brunetti; et al. (Frontiers in Marine Science, 2026)
Monitoring Essential Ocean, Climate, and Biodiversity Variables (EOVs, ECVs and EBVs) collected through the marine Research Infrastructures (RIs) is critical for assessing environmental status, improving scientific knowledge and defining environmental policies. This study evaluates the capacity of the Italian marine monitoring system, including facilities such as fixed stations, buoys, autonomous platforms, and mobile systems across the Mediterranean Sea, to produce those variables. Conducted in 2023 within the framework of the ITINERIS project ( https://itineris.cnr.it/ ), which aims to strengthen coordination among national and ESFRI RIs (European Strategy Forum on Research Infrastructures), the analysis systematically examines the spatial, thematic, and technological coverage of EOVs, ECVs, EBVs observations and their alignment with international standards for environmental monitoring of 155 facilities from eight Italian and pan-European marine RIs. Of the 107 EVs recognized, 50% were actively produced by the RIs considered, with over 90% meeting the established requirements for EVs. These numbers will be updated to reflect the new equipment acquired during the project’s implementation up to early 2026, which is expected to boost EVs production by approximately 38-40%. The national monitoring network demonstrates a high degree of maturity for oceanic and climate variables, while biodiversity observations remain less represented, indicating the need for further technological innovation and automation. These findings emphasize the importance of enhancing coordination and harmonization among RIs to ensure balanced and interoperable monitoring. The study provides key recommendations to strengthen Italy’s capacity to contribute to the global characterization of EOVs, ECVs, and EBVs and to support evidence-based environmental assessments and the development of robust environmental management strategies at European level.

Determinants of L-band backscatter in dry tropical ecosystems: Implications for biomass mapping - João M.B. Carreiras; Thomas Higginbottom; John L. Godlee; Sam Harrison; Lorena Benitez; Penelope J. Mograbi; Aurora Levesley; Karina Melgaço; David Milodowski; Georgia Pickavance; Geoff Wells; Edmar Almeida de Oliveira; et al. (Remote Sensing of Environment, 2026)

Extrusion of high-grade metamorphic and anatectic rocks during inclined transpression in the central Brasília Orogen, Western Gondwana - Fernando Resende Honorato; Marco Antônio Delinardo da Silva; Ticiano José Saraiva dos Santos; João Victor Oliveira Cunha; Ewerton Benetti Poloni; Pamela Pavanetto (Journal of Structural Geology, 2026)

Photocontrol of nitrogen sites for poisoning-free NO₂ sensing - Berta Pérez-Román; Daniel Matatagui; M. Alejandra Mazo; Pilar Marín; Laura Pascual; Jesús López-Sánchez; Fernando Rubio-Marcos (Chemical Engineering Journal, 2026)

The devastating impact of the category 5 hurricane Otis on Mexico’s pacific coast - Fernando Peña; Adrián Pozos-Estrada; Miguel Ángel Jaimes; Marcos M. Chávez; Héctor Guerrero; Baruo D. Aldama-Sánchez; Eduardo Botero-Jaramillo; Leonardo Alcántara; Óscar A. Fuentes-Mariles; Christian M. Appendini; Eduardo Reinoso (Natural Hazards, 2026)

Hydrothermal carbonization of digestate from sewage sludge: Evaluating the impact of process parameters in hydrochar yield and characterization - Matheus Venâncio de Oliveira; Akel Ferreira Kanaan; Fernando A.P. Voll; Marcos L. Corazza (Fuel, 2026)

Suboptimal responses to E2/P4-based timed AI protocols compromise pregnancy outcomes in fertile beef cattle: Roles of ovulation timing and semen viability - César Augusto Pinzón-Osorio; Thomaz Kranen Cunha; German Holguin-Sanabria; Marco Alves Machado; Favorino José de Freitas Collares; Luís Henrique de Aguiar; Paula Rodriguez-Villamil; Felipe Ledur Ongaratto; Eduardo Pradebom da Silva; Eduardo de Oliveira Sanguinet; Carolina Silveira da Silva; Daiane Mentz; et al. (Animal Reproduction Science, 2026)

Therapeutic Efficacy of Monoterpenes in Nile Tilapia Infected With Edwardsiella tarda : A Phytogenic Alternative to Oxytetracycline - Danilo Vitor Vilhena Batista; Adolfo Jatobá; Alexandre Vaz da Silva; Ana Paula de Souza; Caio Francisco Santana Farias; Emilly Monteiro Lopes; Marco Shizuo Owatari; Arlene Sobrinho Ventura; Claudia Andrea Lima Cardoso; Silvia Terra Fontes; Fernando Yugo Yamamoto; Maurício Laterça Martins; et al. (Journal of Fish Diseases, 2026)
The purpose of this research was to assess the effectiveness of a combination of monoterpenes (thymol and carvacrol) in treating juvenile Nile tilapia ( Oreochromis niloticus ) infected with Edwardsiella tarda as a potential substitute for the antibiotic oxytetracycline. The study utilised different concentrations of the monoterpenes blend (MTs): 0.4, 0.6 and 0.8 g kg −1 of feed. A negative control group received a diet without the additive, while a positive control group was given medicated feed containing oxytetracycline (OTC) (11.85 g kg −1 ) for a 10‐day treatment period. Cumulative mortality (%), haematological and immunological parameters were assessed after the feed administration. The negative control group experienced a mortality rate of 53%, while fish treated with medicated feed had a significantly lower mortality rate of 3%. The addition of MTs at concentrations of 0.4 g kg −1 (13% mortality), 0.6 g kg −1 (8% mortality) and 0.8 g kg −1 (0% mortality) also resulted in reduced mortality rates, with the highest concentration showing survival rates comparable to the oxytetracycline group. Following the 10‐day treatment period, no mortality was observed in the treated groups, indicating the efficacy of MTs‐supplemented feed in alleviating the clinical symptoms of Edwardsiellosis. The haematological parameters indicated that as the dosage of MTs increased, the mean corpuscular volume (MCV) decreased. The MCV was significantly lower in the 0.6 and 0.8 g kg −1 treatments compared to the control. Mean corpuscular haemoglobin initially increased with the 0.4 g kg −1 MTs treatment but then decreased with higher doses. The mean corpuscular haemoglobin concentration was higher in the treated groups compared to the control. Red blood cell levels were higher in the 0.8 g kg −1 MTs treatment and lower in the 0.4 g kg −1 treatment. Ht was higher in the control group and lower in the 0.4 g kg −1 MTs treatment. Haemoglobin levels followed a similar trend, with higher values in the control group. The 0.8 g kg −1 MTs treatment had the highest number of total leucocytes and lymphocytes. The control group had the highest number of neutrophils, while the 0.8 g kg −1 MTs group had higher numbers of monocytes, eosinophils, basophils and thrombocytes. The negative control exhibited the lowest antimicrobial titre compared to the OTC and the various concentrations of MTs. The concentrations of MTs (0.4, 0.6 and 0.8 g kg −1 ) demonstrated similar average values and were more effective than the control and OTC. There was no significant difference in agglutinating titre among MTs, control and OTC. Thymol and carvacrol notably decreased the mortality of tilapia infected with E. tarda , with a dosage as high as 0.8 g kg −1 showing equivalent effectiveness to oxytetracycline. Furthermore, they enhanced haematological and immunological parameters, indicating that MTs could be a promising alternative to antibiotic use.

Measurement of urban environmental exposure to extremely low frequency magnetic fields in several Spanish regions - Aránzazu Sanchis-Otero; Raquel Ramirez-Vazquez; Jesús M. Paniagua; Ricardo Bajo; Enrique Arribas; Fernando Giacomone; Rebeca Ramis; Pilar Marín Palacios; Francisco Vargas Marcos (Environmental Science and Pollution Research, 2026)

Asymmetries challenging global biodiversity sciences - Leandro O. Salles; Hussam Zaher; Marcos Tavares; Mario C. C. de Pinna; Rosane G. Collevatti; Krister T. Smith; Diego Pol; Hongyu Yi; Nancy B. Simmons; Christopher J. Tribe; Joaquin Arroyo-Cabrales; Nour-Eddine Jalil; et al. (Systematics and Biodiversity, 2026)

Wastewater analysis as a global toxicovigilance tool for the monitoring of new psychoactive substances - Dhayaalini Nadarajan; Maria Laimou-Geraniou; Andrew Chappell; Christine Baduel; Lubertus Bijlsma; Tim Boogaerts; Daniel A. Burgard; Sara Castiglioni; Nicola Ceolotto; Erin M. Driver; Fernando Fabriz Sodre; Despo Fatta Kassinos; et al. (Water Research, 2026)

Experimental hyper-progesteronemia increases the egg shedding and fertility of Haemonchus contortus in sheep - Marco Antonio Muñoz-Guzmán; Adolfo Sánchez-Paredes; César Cuenca-Verde; María Guadalupe Prado-Ochoa; Omar Escobar-Chavarría; Fernando Alba-Hurtado (Veterinary Parasitology, 2025)

Differential macrophage immune checkpoint expression triggered by bovine-associated staphylococci - Sarah Antonieta de Oliveira Veríssimo; Filipe Aguera Pinheiro; Ygor Fagundes Ruas; Kamila Reis Santos; Eduardo Milton Ramos-Sanchez; Hiro Goto; Soraia Araújo Diniz; Sarne De Vliegher; Marcos Bryan Heinemann; Luiza Campos Reis; Alice Maria Melville Paiva Della Libera; Fernando Nogueira Souza; et al. (Veterinary Immunology and Immunopathology, 2025)

A pretty kettle of fish: Contamination of fish from the Doce River basin after the world’s largest mining disaster and associated human health risks - Larissa Ajala-Batista; Flávia Yoshie Yamamoto; Mayara Padovan; Marina Corrêa Scalon; Marco Tadeu Grassi; Denis Moledo De Souza Abessa; Luís Fernando Fávaro (Total Environment Advances, 2025)

Multiomic insights into sucrose accumulation in sugarcane - Alexandre Hild Aono; Ricardo José Gonzaga Pimenta; Jéssica Faversani Diniz; Marishani Marin Carrasco; Guilherme Kenichi Hosaka; Fernando Henrique Correr; Ana Letycia Basso Garcia; Estela Araujo Costa; Alisson Esdras Coutinho; Luciana Rossini Pinto; Marcos Guimarães de Andrade Landell; Mauro Alexandre Xavier; et al. (Plant Molecular Biology, 2025)

A reference genome for Plinia edulis: expanding the pharmacological and nutraceutical potential of a neglected brazilian tree species - Valdir Marcos Stefenon; Thiago Sanches Ornellas; Yohan Fritsche; Suelen Martinez Guterres; Ingrid Lohani Degering Brand; Ana Kelly de Sousa Silva; Fernando Joner (Molecular Genetics and Genomics, 2025)

Prevalence of bovine tuberculosis and attention zones for Mycobaterium bovis in the state of São Paulo (SP), Brazil, based on data from sanitary inspections at slaughterhouses - Carlos Augusto Scacchetti de Almeida; André Mota; Rogério Giufridda; Marcos Bryan Heinemann; Bruno Marinho; Hugo Leonardo Riani Costa; Marcus Vinicius Salomon; José Soares Ferreira Neto; Fernando José Paganini Listoni; Márcio Garcia Ribeiro (Brazilian Journal of Microbiology, 2025)

Strategic Timing of Larval Harvest as a Practical Approach to Increase Baculovirus Mass Production - Nathan Lemes da Silva Lima; Cidália Gabriela Santos Marinho; Frederick Mendes Aguiar; Marcos Antônio Matiello Fadini; Fernando Hercos Valicente (Neotropical Entomology, 2025)

Fertility and carbon stocks in Oxisols under Urochloa pastures and Eucalyptus-based agrosilvopastoral systems established in the Brazilian Cerrado - Jaqueline de Cássia de Oliveira; Igor Costa de Freitas; Ana Clara Santos Duarte; João Gabriel Figueiredo Moreira; Alex José Silva Couto; Marcos Fernando Gonçalves Lessa; Miguel Marques Gontijo Neto; Márcia Vitória Santos; Mauricio Roberto Cherubin; Carlos Eduardo Pellegrino Cerri; Leidivan Almeida Frazão (Soil and Tillage Research, 2025)

Petrogenesis and emplacement of the Paleoproterozoic A-type Marajoara granite in the Carajás province, southeastern Amazonian craton: Constraints from geochemistry, zircon geochronology, Nd Hf isotopes, coexistence of reduced and oxidized magmas and new insights from a composite dike - Rodrigo Fabiano Silva Santos; Davis Carvalho de Oliveira; José de Arimatéia Costa de Almeida; Roberto Dall'Agnol; Bhrenno Marangoanha; Marco Antonio Galarza; Cláudio Nery Lamarão; Fernando Fernandes da Silva (Lithos, 2025)

Corrigendum to ‘Paleolimnology based on organic matter analysis and geochemical studies: Santa Clara Abajo Formation (Triassic), Cuyana Basin, Mendoza, Argentina’ [J. S. Am. Earth Sci., 165 (2025) 105721] - Federico Siderac; Georgina Erra; Marcos Comerio; Fernando Larriestra; Cecilia Andrea Benavente (Journal of South American Earth Sciences, 2025)

Climate change will boost the invasion of the harmful cyanobacterium Raphidiopsis raciborskii in South America - Felipe Morais Zanon; Bruno Henrique Mioto Stabile; Beatriz Melissa Campos; Érica Oliveira de Lima; Matheus Juan Alarcon Sampaio; Yasmin Rodrigues de Souza; Leonardo Rodrigues Tolardo; Mayra Koma Gomes; Luddy Searom Carias de Moraes; Gabriela Sponchiado Hein; Jaqueline Dantas da Silva; Larissa da Silva Pinha; et al. (Harmful Algae, 2025)

Alginate-pectin microparticles embedding self-assembling antimicrobial peptides and resveratrol for antimicrobial and anti-inflammatory applications - Cesar Augusto Roque-Borda; Marco Roberto Chávez-Morán; Laura Maria Duran Gleriani Primo; José C.E. Márquez Montesinos; Vinicius Martinho Borges Cardoso; Mauro M.S. Saraiva; Caroline Maria Marcos; Marlus Chorilli; Fernando Albericio; Beatriz G. de la Torre; Fernando Rogério Pavan; Andréia Bagliotti Meneguin (Food Hydrocolloids, 2025)

Direct N2O decomposition at low temperature over NiO-Nb2O5 catalysts - Ana Serrano-Lotina; Susana Pérez-Ferreras; Consuelo Álvarez-Galván; Rocío E. Rojas-Hernandez; José F. Fernández; Pedro Ávila; Miguel A. Bañares; Fernando Rubio-Marcos (Chemical Engineering Journal, 2025)

The Dry‐Climate Hypothesis: Identifying the Environmental Drivers of Terrestrial Viviparous Salamanders - Marco Dinis; Fernando Martínez‐Freiría; Wouter Beukema; Sergé Bogaerts; Guillermo Velo‐Antón (Journal of Biogeography, 2025)
Aim The evolution of adaptive innovations carries strong eco‐evolutionary implications, allowing organisms to explore novel ecological opportunities, which facilitates lineage diversification. The remarkable diversity of reproductive strategies in amphibians provides a natural laboratory for identifying ecological mechanisms driving evolutionary novelties. In viviparous salamanders, the transition from larviparous (i.e., live bearing of aquatic larvae) to pueriparous (i.e., live bearing of fully terrestrial juveniles) reproduction is hypothesized to represent an adaptation to the absence of water for larval deposition, in what is known as the dry‐climate hypothesis. This work aimed to identify the ecological drivers of independent evolutionary transitions to pueriparity and test the dry‐climate hypothesis. Location Western Palearctic. Taxon Salamanders of the Salamandra and Lyciasalamandra genera. Methods A comparative ecological niche‐based framework spanning the entire known distribution of larviparity and pueriparity in salamanders was used to identify the ecological drivers of this reproductive transition. Niche divergence was tested between (a) viviparous modes and (b) independent origins of pueriparity to assess the existence of ecological differentiation between groups. The relative contribution of environmental factors to niche divergence was assessed by regression analysis. Results We found that independent transitions from larviparity to pueriparity are consistently associated with ecological differentiation driven primarily by steep topography and karstic geology. Main Conclusions Reproductive transitions to pueriparity in salamanders were consistently associated with scarcity of surface water driven by steep topography and karstic geology, providing the most unambiguous support for the dry‐climate hypothesis to date and supporting convergent evolution of terrestrialisation in salamanders for most pueriparous lineages. Climatic, hydrological (i.e., soil moisture and vapour pressure deficit) and habitat factors appear to be comparatively less relevant drivers of reproductive shifts, yet may have played a role in specific transitions to pueriparity, especially at the intraspecific level. We also found key differences in the use of available habitat between reproductive modes, with pueriparity representing a more specialised strategy likely restricted to areas with strong selective pressure against aquatic breeding.

Bacterial consortia enhance glyphosate breakdown and drive soil microbial dynamics - Mariana Prósperi de Oliveira Paula; Luiz Fernando Wurdig Roesch; Alessandro Coutinho Ramos; Marcos Rogério Tótola; Victor Satler Pylro (Chemosphere, 2025)

Environmental factors influence in vitro embryo production of Gir cattle - Lethissia Amorim da Silva Coelho; Rondineli Pavezzi Barbero; Marco Roberto Bourg de Mello; Jaime Araujo Cobuci; Fernanda Santos Silva Raidan; Luiz Fernando Rodrigues Feres; Elisandra Lurdes Kern (Theriogenology, 2025)

Paleolimnology based on organic matter analysis and geochemical studies: Santa Clara Abajo Formation (Triassic), Cuyana Basin, Mendoza, Argentina - Federico Siderac; Georgina Erra; Marcos Comerio; Fernando Larriestra; Cecilia Andrea Benavente (Journal of South American Earth Sciences, 2025)

Relational follow-up and review of the 2030 Agenda: accelerating the implementation of the sustainable development goals - Fernando Ortiz-Moya; Marco Reggiani (Current Opinion in Environmental Sustainability, 2025)

Molecular architecture strategies for UV-enhanced NO2 sensors under ambient conditions - Berta Pérez-Román; Jesús López-Sánchez; M. Alejandra Mazo; Álvaro Peña; David G. Calatayud; Pilar Marín; Laura Pascual; Rocío E. Rojas-Hernández; Daniel Matatagui; Fernando Rubio-Marcos (Chemical Engineering Journal, 2025)

A unique association of fusioolithid dinosaur eggs from the Upper Cretaceous of Spain (Poyos, central system) - Fernando Sanguino; Ane de Celis; Raúl de la Horra; Elena Fernández Fernández; Javier Fernández Martínez; Fátima Marcos-Fernández; Adán Pérez-García; Francisco Ortega (Cretaceous Research, 2025)

Mapping Resilient Landscapes to Climate Change in a Megadiverse Country - Milena Fermina Rosenfield; Lucas Jardim; Marina Antongiovanni; Luciano Carramaschi de Alagão Querido; Alisson André Ribeiro; Andrea Sánchez‐Tapia; Priscila Silveira; Levi Carina Terribile; Eduardo M. Venticinque; Ana Luisa Albernaz; Letícia Couto Garcia; Leandro Reverberi Tambosi; et al. (Global Change Biology, 2025)
The effects of global climate change on biodiversity and ecosystem functioning are unevenly distributed in the geographic space. Identifying sites more suitable to sustain biodiversity in a changing climate is essential to both species conservation and restoration strategies at different scales. Here, we map terrestrial climate‐resilient sites for biodiversity across Brazil to identify sites with greater chances of providing suitable conditions for species to persist under regional climate change. Our mapping combines spatial metrics based on landscape heterogeneity, a proxy for microclimatic variability, and local connectedness, a measure of connectivity between habitats, to determine landscape resilience, assuming that resilience to climate change will be greater the more heterogeneous the characteristics of local habitats are and the more connected they are in the landscape. Our results show that within each biome, medium to high resilient sites are mostly found in the Amazon (40% of the biome) and Pantanal (38%). Low resilience, conversely, is concentrated in the Atlantic Forest (41% of the biome), followed by Cerrado (37%), Pampa (36%), and Caatinga (34%). Landscape resilience information has the potential to be used to effectively guide decision‐making and public policy on strategies for conservation, restoration, and sustainable use practices. Priority for conservation should be on high resilience sites as they have the potential to sustain biodiversity in face of undergoing and future climate change. Other approaches could be used in situations of medium to low resilience also, such as: conservation of current corridors in sites with high local connectedness, but low landscape heterogeneity; restoration of natural vegetation on sites that show high landscape heterogeneity, but low local connectedness; and sustainable practices in areas of low resilience. Our study provides an updated method to pinpoint climate‐resilient sites for biodiversity which was applied to a megadiverse country but is applicable to any ecosystem around the globe.

Air pollutant detection and chlorinated very short-lived substance characterization with a prototype terahertz time-domain spectrometer - Candida Moffa; Alessandro Curcio; Camilla Merola; Vittoria Maria Orsini; Daniele Francescone; Fernando Jr. Piamonte Magboo; Marco Magi; Massimiliano Coppola; Lucia Giuliano; Mauro Migliorati; Giuseppe Zollo; Massimo Reverberi; et al. (Next Research, 2025)

Efficacy of Platelet and Leukocyte Rich Fibrin (L-PRF) in the healing process and bone repair in maxillary sinus lift surgeries: a systematic review - Élio Hitoshi Shinohara; Ilan Hudson Gomes de Santana; Mayara Rebeca Martins Viana; Edmundo Junio Rodrigues de Almeida; Anderson Jara Ferreira; José Marcos Pereira Júnior; Arthur Felipe de Brito Andrade; Fernando Kendi Horikawa; Eduardo Dias Ribeiro (Cell and Tissue Banking, 2025)

Body mass index and prognosis of infective endocarditis - Raquel Frías-García; Patricia Muñoz García; Marina Machado Vilchez; Gregorio Cuerpo Caballero; Raquel Rodríguez-García; M Ángeles Rodríguez-Esteban; M Carmen Fariñas-Álvarez; José M. Miró Meda; Andrea Gutiérrez Villanueva; Guillermo Ojeda-Burgos; Ane Josune Goikoetxea-Agirre; Marina Bernal Palacios; et al. (Infectious Diseases, 2025)

Magnetic and chemical biomonitoring with lichens and vascular plants for the preservation of cultural heritage: A case study at two museums in a megacity (Buenos Aires, Argentina) - Lisa Grifoni; Aldo Winkler; Marcos A.E. Chaparro; Luigi Antonello Di Lella; Fernando Marte; Antonio Sgamellotti; Lilla Spagnuolo; Marcos Tascon; Daniela Buitrago Posada; Débora C. Marié; Martina Scoccimarro; Stefano Loppi (Science of The Total Environment, 2025)

Oxygen-induced enzymatic and chemical degradation kinetics in wine model solution of selected phenolic compounds involved in browning - Marco Bustamante; Mariona Gil-Cortiella; Álvaro Peña-Neira; Jordi Gombau; Aitor García-Roldán; Matias Cisterna; Xavier Montané; Francesca Fort; Nicolas Rozès; Joan Miquel Canals; Fernando Zamora (Food Chemistry, 2025)

Environmental Impact of Mining Activities on Water Availability, Quality and Sediments in the Sonora River, Mexico - Adrián Pedrozo-Acuña; José Agustín Breña-Naranjo; Norma Ramírez-Salinas; Juan Carlos Bustos-Montes; Julio César Soriano-Monzalvo; Edwin Fernando Zetina-Robleda; Marco Rodrigo López-López (Water, Air, & Soil Pollution, 2025)
The aim of this study is to characterise environmental impacts associated with mining operations in the Sonora River basin, a water-scarce region of Mexico. The focus is on evaluating water availability, water quality, and sediment composition along the river. Furthermore, the quality of groundwater for human consumption is assessed. Data collected from an extensive field campaign is employed for this purpose. For the first time, measurements of groundwater levels in conjunction with satellite data have shown a substantial decline in groundwater levels in the northern part of the Sonora River basin, near the Buenavista del Cobre mine, highlighting how mining activities are directly affecting the loss of groundwater resources. Results relative to heavy metal pollution in the river’s surface water indicated the presence of hazardous metals at health-concerning concentrations in two areas in the river basin’s central region. Both assessed indices, the contamination degree factor and the Metal Evaluation Index, demonstrated significant heavy metal pollution associated with mining operations. Moreover, the sediment analysis clearly reveals various areas and mechanisms of heavy metal contamination within the watershed. The Pollutant Load Index (PLI) and the Ecological Risk Index (ERI) indicated significant ecological danger and severe contamination near a mine and in two regions where sediment deposition occurs (as evidenced by ERI > 300 and PLI > 3). This suggests a diffusive contamination process that conveys metals from the northern section of the basin to the southern areas of the Sonora River, due to the steeper slopes of upstream rivers. Lastly, groundwater sources intended for human consumption demonstrated generally good to excellent water quality, proving to be unaffected by mining operations. Findings show that in arid regions, it is crucial to regularly revise environmental effects of water-intense mining activities to ensure sustainable water use and to lessen risks to nearby ecosystems and local communities. Graphical Abstract

Approaching equine infectious anemia in regions dominated by grade-working animals - a case of Pará, a state in the Brazilian Amazon - Ana Paula Vilhena Beckman Pinho; Fernando Ferreira; Jeferson Jacó Fuck; Jefferson Pinto de Oliveira; Ricardo Augusto Dias; José Henrique Hidebrand Grisi-Filho; Marcos Bryan Heinemann; Evelise Oliveira Telles; Marcos Amaku; José Soares Ferreira Neto (Veterinary Research Communications, 2025)

The interplay of economic complexity and urban sprawl in shaping socio-spatial segregation in Mexico - Marco Cruz-Sandoval; Fernando Gómez-Zaldívar; Gonzalo Peraza-Mues; Roberto Ponce-López (Applied Geography, 2025)

Framing social systems for ecosystem-based management: The Guadalquivir estuary-Gulf of Cadiz coupled SES as case study - Alfredo García-de-Vinuesa; David Florido; Cesar Vilas; María Ángeles Torres; Marina Delgado; Isabel Muñoz; Remedios Cabrera-Castro; Fernando Ramos; Marcos Llope (Environmental Development, 2025)

Prevalence and risk factors for bovine brucellosis in the state of Pará, Amazon region of Brazil - José Soares Ferreira Neto; Jefferson Pinto Oliveira; Ana Paula Vilhena Beckman Pinho; Washington Luiz Assunção Pereira; Ricardo Augusto Dias; José Henrique Hidebrand Grisi Filho; Vitor Salvador Picão Gonçalves; Marcos Bryan Heinemann; Marcos Amaku; Evelise Oliveira Telles; Bruno Fontana Soares Ferreira; Fernando Ferreira (Tropical Animal Health and Production, 2025)

Simultaneous Occurrence of Local Meteotsunamis and the 2022 Tonga Tsunami along the Argentine and Uruguayan Coasts, Southwestern Atlantic Ocean - Walter Dragani; Iael Perez; Fernando Oreiro; Marcos Saucedo (Pure and Applied Geophysics, 2025)

Identification and expression of the AREB/ABF/ABI5 subfamily genes in chickpea and lentil reveal major players involved in ABA-mediated defense response to drought stress - Marcos Fernando Basso; Paolo Iovieno; Maurizio Capuana; Felice Contaldi; Francesca Ieri; Felicia Menicucci; Fabrizio Lo Celso; Giampaolo Barone; Federico Martinelli (Planta, 2025)

Evaluation and calibration of MERRA-2 and CAMS reanalysis for PM2.5 in a semi-urbanized area in the south of the Amazon - Danielle Nassarden; Jorge Menezes; Carlos Barbosa Pessoa; Anderson Carneiro; Luiz O. F. dos Santos; Glauber Cirino; Breno Imbiriba; Fernando Sallo; Leone F. A. Curado; Thiago R. Rodrigues; João Basso; Marco A. Franco; et al. (Air Quality, Atmosphere & Health, 2025)

A global assessment of microplastic abundance and characteristics on marine turtle nesting beaches - Zara L.R. Botterell; Jed Ardren; Elly Dove; Ellen McArthur; David S. Addison; Oyeronke M. Adegbile; Pierre Didier Agamboue; Andrews Agyekumhene; Phil Allman; Alexandra Alterman; Adren Anderson; Theresa Arenholz; et al. (Marine Pollution Bulletin, 2025)

Methods to assess on-farm biosecurity in Europe and beyond - Fernando Duarte; Lena-Mari Tamminen; Miroslav Kjosevski; Giovanna Ciaravino; Mattias Delpont; Carla Correia-Gomes; Bart H.P. van den Borne; Ilias Chantziaras; Laura Valeria Alarcón; Line Svennesen; Ina Toppari; Alessandra Piccirillo; et al. (Preventive Veterinary Medicine, 2025)

Power asymmetry destabilizes reciprocal cooperation in social dilemmas - Marco Colnaghi; Fernando P. Santos; Paul A.M. Van Lange; Daniel Balliet (Journal of Theoretical Biology, 2025)

Morphotectonics in intraplate setting: The case of the western border of the São Paulo Basin – Southeastern Brazil - Marcos Roberto Pinheiro; Fernando Nadal Junqueira Villela; Paola Cianfarra (Journal of South American Earth Sciences, 2025)

Bird–window collisions: A comprehensive dataset for the Neotropical region - Augusto João Piratelli; Bianca Costa Ribeiro; Wesley Dáttilo; Luis‐Bernardo Vázquez; Anelisa Ferreira de Almeida Magalhães; Edna Maria Gomes Cavalcante; Eric Silva; Giovanna Viana Cruz; Gisele Regina Ruy; Juliana Laurito Summa; Júlia Milan; Leila Pedrosa; et al. (Ecology, 2025)
Our primary objective was to compile a comprehensive dataset on bird–window collisions throughout the Neotropical region, including both published and unpublished sources. On May 12, 2020, we extensively disseminated invitations to provide data via email and social media platforms. By providing a template worksheet, we required standardized information from collaborators to complete and register their data. To better understand how these data were acquired (e.g., incidental observations and systematic procedures), we sent out a survey to all collaborators. We established rigorous validation criteria for data inclusion and conducted thorough curation procedures to ensure accuracy. After the filtering process, we compiled a total of 4103 bird–window collision reports. These came from 11 Neotropical countries, dating from 1946 to 2020, and revealing distinct regional patterns and potential seasonal patterns. The five most frequent orders were Passeriformes (2451), Columbiformes (520), Apodiformes (377), Psittaciformes (202), and Piciformes (186). Data on bird–window collisions were collected through a local specific systematic protocol (1419), by chance (1252), by government agencies (742), and by other approaches (632), while a few reports were collected by unknown procedures (58). The volume of records across months in our dataset suggests that there may be temporal patterns, with peaks: the first one in March–April and the second one in October–November, which seem to align with the major migration and reproduction seasons. This dataset represents the first comprehensive effort in the Neotropical region focused on bird–window collision data, providing valuable insights for further scientific advancements and conservation policies. The data are free from copyright or proprietary restrictions. Please cite this data paper when using the data in publications or scientific presentations.

Exploring sustainable scenarios for the brown algae fishery in the intertidal zone along the central Chilean coast (Maule region) - Fernando Berrios; Marco Ortiz (Journal of Environmental Management, 2025)

Microplastics and organic contaminants: Investigation of the sorption process on different polymer types - Fabiane Ferraz Wisniewski; Elisandra Carolina Martins; Danieli Sayuri Hakoyama; Luis Fernando Amorim Batista; Marco Tadeu Grassi; Sonia Faria Zawadzki; Gilberto Abate (Journal of Contaminant Hydrology, 2025)

Characterization of Rugulopteryx okamurae algae: A source of bioactive peptides, omega-3 fatty acids, and volatile compounds - Fernando Rivero-Pino; Teresa Gonzalez-de la Rosa; Maria Torrecillas-Lopez; Luna Barrera-Chamorro; Jose Luis del Rio-Vazquez; Elvira Marquez-Paradas; Africa Fernandez-Prior; Marco Garcia-Vaquero; Jose Carlos Garcia-Gomez; Sergio Montserrat-de la Paz; Carmen Maria Claro-Cala (Food Chemistry, 2025)

Estimating VS30 structure from topographic and geological data in the southeast of Spain - Manuel Navarro; Fernando López; Pedro Martínez-Pagán; Antonio García-Jerez; Marcos A. Martínez-Segura; Yoshiya Oda; Takahisa Enomoto (Engineering Geology, 2025)

Combined impact of pesticides on mono- and bilayer lipid membranes - Luis Fernando do Carmo Morato; Gilia Cristine Marques Ruiz; Carlos Junior Amorim Lessa; Danilo da Silva Olivier; Marcos Serrou do Amaral; Orisson Ponce Gomes; Wallance Moreira Pazin; Augusto Batagin-Neto; Osvaldo N. Oliveira; Carlos José Leopoldo Constantino (Chemistry and Physics of Lipids, 2025)

Phenotypic and behavioral variation as a mechanism behind the invasive potential of a predatory neotropical fish - Marcos Ribeiro da Costa Gaspar; Angelo Antonio Agostinho; Paula Araújo Catelani; Rodrigo Fernandes; Ana Clara Sampaio Franco; José Luis Costa Novaes; Danielle Peretti; Ana Cristina Petry; Fernando Mayer Pelicice (Hydrobiologia, 2025)

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

The Amorphous State of the Antiepileptic Clobazam: Preparation and Characterization - Marina M. Marcos Valdez; Julio Sanchez; María E. Bertotto; Octavio E. Fandiño; Fernando P. Cometto; Norma R. Sperandeo (AAPS PharmSciTech, 2025)

First record of Ixodes uriae White, 1852 (Parasitiformes: Ixodidae) on the great shearwater (Procellariiformes: Procellariidae) in Southern Brazil: a step toward understanding tick-host interactions - Ricardo Bassini-Silva; Fernando de Castro Jacinavicius; Gustavo Seron Sanches; Ana Cláudia Calchi; Ana Carolina Castro-Santiago; Carolina Feltes Alves; Eduardo Macagnan; Gabriela Cristini de Souza; Marcos Rogério André; Adriana Silva Albuquerque; Pedro Volkmer de Castilho; Darci Moraes Barros-Battesti; et al. (Veterinary Research Communications, 2025)

Propagation Materials do not Affect Nutrient Absorption of Sugarcane During the Plant-Cane Cycle - Marco A. Lazarini; Fernando C. B. Zambrosi (Sugar Tech, 2025)

Molecular detection of Ehrlichia Sp. in bat-associated chigger mites (trombidiformes: leeuwenhoekiidae and trombiculidae S. s.) from Brazil - Ricardo Bassini-Silva; Victor de Souza Mello-Oliveira; Beatriz Rocha de Almeida; Isabella Pereira Pesenato; Ana Cláudia Calchi; Ana Carolina Castro-Santiago; Elizabete Captivo Lourenço; Katia Maria Famadas; Cal Welbourn; Ronald Ochoa; Marcos Rogério André; Marcelo Bahia Labruna; et al. (Experimental and Applied Acarology, 2025)

Modified vermiculite as a sorbent phase for stir-bar sorptive extraction - Natascha Amalio Teixeira; Luis Fernando Amorim Batista; Princys Schneider de Mira; Duanne Maciel Scremin Miyazaki; Marco Tadeu Grassi; Sônia Faria Zawadzki; Gilberto Abate (Analytica Chimica Acta, 2025)

Short term effects in soil quality under different cover crops of no tillage vegetables organic production in fragile soils in Southeastern Brazil - Dérique Biassi; Priscila Silva Matos; Fernando Igne Rocha; Thassiany de Castro Alves; Fernanda Palmeira Gabetto; Marcos Gervasio Pereira; Nivaldo Schultz; Everaldo Zonta (Organic Agriculture, 2025)

Exploring the potential of hydrolytic enzymes combined with antibacterial agents to disrupt pathogenic biofilms and disinfect released cells - Patricia Palafox-Rivera; Melvin R. Tapia-Rodriguez; Julio Cesar Lopez-Romero; Marco A. Lugo-Flores; Karen P. Quintero-Cabello; Brenda A. Silva-Espinoza; M. Reynaldo Cruz-Valenzuela; Filomena Nazzaro; J. Fernando Ayala-Zavala (Biofouling, 2025)

Role of sex hormones in the reactivation of Toxocara canis larvae in pregnant bitches - Marco Antonio Muñoz-Guzmán; Fernando Alba-Hurtado (Veterinary Parasitology, 2025)

Cost-effective alternatives to facilitate biomonitoring and bioassessment of neotropical streams - Francisco Valente-Neto; Renato B. Dala-Corte; Almir M. Cunico; André L.B. Magalhães; Bruno S. Godoy; Cecília G. Leal; Diego M.P. Castro; Diego R. Macedo; Dilermando P. Lima-Junior; Éder A. Gubiani; Fabio de O. Roque; Fabrício B. Teresa; et al. (Science of The Total Environment, 2025)

Origin of surface deposits in pediments of Southeastern Brazil - Marcos Roberto Pinheiro; André Mateus Barreiros; Grace Bungenstab Alves; Marcelo Reis Nakashima; Beatriz Ferraz Scigliano; Andrio Filipe Amaral Soares; Antonio Artur dos Santos; Hellen Renata Guimarães Borsoi; Antonio Carlos de Azevedo; Fabiano N Pupim; Caio Breda; Fernando Nadal Junqueira Villela (CATENA, 2025)

Molecular evidence of Wolbachia in bat-associated mite Periglischrus Iheringi Oudemans, 1902 (Mesostigmata: Spinturnicidae) from Brazil - Ricardo Bassini-Silva; Ana Cláudia Calchi; Ana Carolina Castro-Santiago; João Carlos Marocco; Letícia Dorigoni; Rosiléia Marinho de Quadros; Marcos Rogério André; Darci Moraes Barros-Battesti; Ashley P. G. Dowling; Marcelo Bahia Labruna; Fernando de Castro Jacinavicius (Veterinary Research Communications, 2025)

New records of Spelaeorhynchus praecursor Neumann, 1902 (Mesostigmata: Spelaeorhynchidae) in the Brazilian Caatinga - Ricardo Bassini-Silva; Eder Barbier; Marcos Rogério André; Darci Moraes Barros-Battesti; Fernando de Castro Jacinavicius (Systematic Parasitology, 2025)

Inter‐Laboratory Comparison of qPCR Assays for Piscirickettsia salmonis in Atlantic Salmon ( Salmo salar L.) in 11 Chilean Laboratories - Andrea Peña; Marco Rozas‐Serri; Ian A. Gardner; Benjamin Diethelm‐Varela; Carla Anguita; Carlos Navarro Jerez; Fernando O. Mardones (Journal of Fish Diseases, 2025)
Real‐time PCR (qPCR) testing is an essential component of early detection surveillance systems for Piscirickettsia salmonis infection in Atlantic salmon farms in Chile. Currently, all 11 laboratories in the authorised diagnostic laboratory network use assays based on published protocols. Compared with other P. salmonis qPCR assays, these assays have the advantage of targeting two different genes, that is, the 16S ribosomal gene and the internal transcribed spacer (ITS), potentially allowing for higher diagnostic accuracy. However, variation and lack of harmonisation of qPCR testing systems (e.g., primers/probe, RNA/DNA as target, extraction methods, etc.) may contribute to among‐laboratory variation in qPCR results and an increased frequency of false‐negative and false‐positive results. The purpose of the ring trial reported herein was to compare qPCR results from 11 laboratories in Chile routinely testing Atlantic salmon for P. salmonis as part of a national control program. The panel of 14 samples included duplicates of three concentrations of P. salmonis in a homogenised head kidney, LF89 and EM90 bacteria and two negative controls (blank and a suspension of Flavobacterium psychrophilum ). The sample order was randomised across labs, samples were tested blinded and analysed without knowledge of the source lab. Of the laboratories, 8 (72.7%) had at least one incorrect result out of 14 tested samples. Low‐concentration samples ( C t of about 30) were more often incorrectly classified by reverse transcription‐qPCR (RT‐qPCR) (3/6 labs) than by qPCR (0/5). Six (54.5%) labs had at least one false‐positive result indicating that cross‐contamination was likely during sample processing. Affected laboratories are advised to conduct internal investigations to confirm the causes of false‐positive results and recommendations for design and implementation of future ring trials are discussed.

Resistance training protects the hippocampus and precuneus against atrophy and benefits white matter integrity in older adults with mild cognitive impairment - Isadora C. Ribeiro; Camila V. L. Teixeira; Thiago J. R. de Resende; Brunno M. de Campos; Gabriel B. Silva; Marco C. Uchida; Thamires N. C. Magalhães; Luciana R. Pimentel-Silva; Ítalo K. Aventurato; Brenda C. Gonçalves; Marjorie C. R. da Silva; Liara Rizzi; et al. (GeroScience, 2025)

U-Pb ages of pre- to post-salt carbonates, Santos and Campos basins, SE Brazil: Implications for the evolution of the South Atlantic - Fernando F. Alkmim; Cristiano C. Lana; Marco A.L. Silva; Dorval C. Dias-Filho; Katia R.N. Mendonça; Eveline E. Zambonato; Bruno Raphael B.M. de Carvalho (Marine and Petroleum Geology, 2025)

Physicochemical, textural and organoleptic characteristics of costeño cheese: An autochthonous product of the Colombian Caribbean coast - Fernando A. Mendoza-Corvis; Omar A. Pérez Sierra; Alba M. Durango Villadiego; Marco T.P. Gontijo; Laís Silva Batalha; Maryoris E. Soto Lopez (International Dairy Journal, 2025)

Development of a model to study browning caused by tyrosinase in grape must - Aitor García-Roldán; Antoni Canalda-Sabaté; Jordi Gombau-Roigé; Marco Bustamante-Quiñones; Arnau Just-Borras; José M. Heras; Nathalie Sieczkowski; Joan Miquel Canals; Fernando Zamora (Food Chemistry, 2025)

Valorization of brewer's spent grain via systematic study of KOH activation parameters and its potential application in energy storage - Sofía Raviolo; María Victoria Bracamonte; María Belén Suarez Ramanzin; Daniela Alburquenque; Marcos Iván Oliva; Fernando Pablo Cometto; Guillermina Leticia Luque (Biomass and Bioenergy, 2025)

Assessing the efficacy of human-induced grassland as a soil erosion buffer on hillside lands in central Mexico - Antonio de Jesús Meraz-Jiménez; Jorge Alejandro Torres-González; Fernando Rufino-Rodríguez; Marco Antonio Meraz-Mercado; Armando López-Santos (Journal of Soils and Sediments, 2025)

A neuro-fuzzy model to predict respiratory disease hospitalizations arising from the effects of traffic-related air pollution in São Paulo - José Carlos Curvelo Santana; Amanda Carvalho Miranda; Jorge Marcos Rosa; Fernando Tobal Berssaneti; Linda Lee Ho; Luccas Leonardo da Silva Ferreira; Robson Aparecido Gomes; Sidnei Alves de Araújo; Peterson Adriano Belan (Clean Technologies and Environmental Policy, 2025)

Habitat restoration for the endangered Yellow Cardinal (Gubernatrix cristata): a forest treatment without affecting bird diversity at the center of Argentina - María Emilia Rebollo; Marcos Matías Reyes; Miguel Ángel Santillán; Fernando Gabriel López; Maximiliano Adrián Galmes; Pablo Díaz Peñalba; Isabel María Luque Romero; Laura Araceli Bragagnolo; María Soledad Liébana; Juan Manuel Grande (Journal of Ornithology, 2025)

chooseGCM : A Toolkit to Select General Circulation Models in R - Luíz Fernando Esser; Dayani Bailly; Marcos Robalinho Lima; Reginaldo Ré (Global Change Biology, 2025)
Studies on climate change need to make projections based on predicted scenarios. One source of variability in these projections is the choice of general circulation models (GCMs). There is a lack of consensus on how to choose the GCMs. This is particularly notorious in species distribution modeling (SDM) studies. An ideal approach would be to encompass all GCMs, but this is exceedingly costly in terms of computational requirements. We propose a methodological framework, which allows the researcher to evaluate the variation in GCMs. The framework has been implemented in an R package, being an easily accessible tool. The proof of concept using SDMs returned an output correlation > 0.9 with the baseline, saving > 79% of computation time and allowing a broader range of hardware to perform robust projections. The chooseGCM package provides a set of functions to download and analyze GCM data, while also providing a wrapper function, helping both experienced and novice modelers. It facilitates the application and calculation of clusterization, correlation, distances, and exploratory information and can help researchers from different backgrounds since it relies solely on the availability of GCMs projections.

Arsenic(V) and vanadium(V) fractionation after its incorporation into a sandy loam soil from Pampas region, Argentina - Carla A. Costamagna; Marcos A. Orellana Benítez; Marc Benedetti; Raúl S. Lavado; Fernando V. Molina (Environmental Monitoring and Assessment, 2024)

Liming and phosphate fertilization influence soil fertility, physical properties, and carbon stock in a subtropical Ferralsol in Brazil - Fernando Marcos Brignoli; Ana Paula Barroco Geraldini; Cássio Antonio Tormena; Marcelo Alessandro Araújo; Marcelo Augusto Batista (Soil and Tillage Research, 2024)

Retraction notice to “Toxicity of spike fragments SARS-CoV-2 S protein for zebrafish: A tool to study its hazardous for human health?” [Sci. Total Environ. 813 (2022) / 152345] - Bianca H. Ventura Fernandes; Natália Martins Feitosa; Ana Paula Barbosa; Camila Gasque Bomfim; Anali M.B. Garnique; Ivana F. Rosa; Maira S. Rodrigues; Lucas B. Doretto; Daniel F. Costa; Bruno Camargo-dos-Santos; Gabrielli A. Franco; João Favero Neto; et al. (Science of The Total Environment, 2024)

Magnetometric and seismic investigation of the Nova Colinas impact structure, Parnaíba Basin, Brazil - Fernando Lessa Pereira; Alvaro Penteado Crósta; Pietro Demattê Avona; Marcos Alberto Rodrigues Vasconcelos; Ana Maria Goés (Journal of South American Earth Sciences, 2024)

Copper excess transcriptional responses in roots of grapevine (Vitis sp.) rootstocks - Victor Hugo Rolla Fiorentini; Andriele Wairich; Marcos Mota do Carmo Costa; Gustavo Brunetto; Priscila Grynberg; Roberto Coiti Togawa; George Wellington Bastos de Melo; Henrique Pessoa dos Santos; Luis Fernando Revers; Felipe Klein Ricachenevsky (Journal of Hazardous Materials, 2024)

Flash vacuum expansion process promotes increased viability of Limosilactobacillus fermentum J24 in papaya-based beverages under simulated digestion - Teresita de Jesús Castillo-Romero; Jesús Ayala-Zavala; Aarón Fernando González-Córdova; Adrián Hernández-Mendoza; Belinda Vallejo-Cordoba; José Isidro Méndez-Romero; Marco Salgado-Cervantes; Manuel Vargas-Ortiz (Food Bioscience, 2024)

Geostatistical modeling of the rainfall patterns and monthly multiscale characterization of drought in the South Coast of the Northeast Brazilian via Standardized Precipitation Index - Marcos Vinícius da Silva; Jhon Lennon Bezerra da Silva; Maria Beatriz Ferreira; Lizandra de Barros de Sousa; Abelardo Antônio de Assunção Montenegro; Jorge Manuel Guieiro Pereira Isidoro; Héliton Pandorfi; José Francisco de Oliveira-Júnior; Helena Maria Neto Paixão Vazquez Fernandez; Fernando Miguel Granja-Martins; Alexandre Maniçoba da Rosa Ferraz Jardim; Thieres George Freire da Silva; et al. (Atmospheric Research, 2024)

Realized genetic gain with reciprocal recurrent selection in a Eucalyptus breeding program - Saulo F. S. Chaves; Luiz A. S. Dias; Rodrigo S. Alves; Filipe M. Ferreira; Maurício S. Araújo; Marcos D. V. Resende; Elizabete K. Takahashi; João E. Souza; Fernando P. Leite; Samuel B. Fernandes; Kaio Olimpio G. Dias (Tree Genetics & Genomes, 2024)

Effects of different China and ball clays on traditional ceramic process: A multi-methodological approach - Andrea Bernasconi; Nicoletta Marinoni; Lucia Mancini; Marco Voltolini; Fernando Francescon; Rinaldo Sartori; Alessandro Pavese (Applied Clay Science, 2024)

From spores to gametes: A sexual life cycle in a symbiotic Trebouxia microalga - Ayelén Gazquez; César Daniel Bordenave; Javier Montero-Pau; Marta Pérez-Rodrigo; Francisco Marco; Fernando Martínez-Alberola; Lucia Muggia; Eva Barreno; Pedro Carrasco (Algal Research, 2024)

Dusting Metarhizium rileyi conidia with a drone for controlling fall armyworm and soybean looper in maize and soybean fields - Rogerio Biaggioni Lopes; Fernando Garcia Nicodemos; Ana Beatriz Zacaroni; Hebert Ribeiro de Souza; Marcos Faria (BioControl, 2024)

FreshLanDiv : A Global Database of Freshwater Biodiversity Across Different Land Uses - Minghua Shen; Roel van Klink; Alban Sagouis; Danielle K. Petsch; Deborah Atieno Abong'o; Janne Alahuhta; Salman Abdo Al‐Shami; Laura Cecilia Armendáriz; Mi‐Jung Bae; Tiago Octavio Begot; Jerome Belliard; Jonathan Peter Benstead; et al. (Global Ecology and Biogeography, 2024)
Motivation Freshwater ecosystems have been heavily impacted by land‐use changes, but data syntheses on these impacts are still limited. Here, we compiled a global database encompassing 241 studies with species abundance data (from multiple biological groups and geographic locations) across sites with different land‐use categories. This compilation will be useful for addressing questions regarding land‐use change and its impact on freshwater biodiversity. Main Types of Variables Contained The database includes metadata of each study, sites location, sample methods, sample time, land‐use category and abundance of each taxon. Spatial Location and Grain The database contains data from across the globe, with 85% of the sites having well‐defined geographical coordinates. Major Taxa and Level of Measurement The database covers all major freshwater biological groups including algae, macrophytes, zooplankton, macroinvertebrates, fish and amphibians.

Disentangling the veil line for Brazilian biodiversity: An overview from two long-term research programs reveals huge gaps in ecological data reporting - Aretha Franklin Guimaraes; Luciano Carramaschi de Alagao Querido; Taina Rocha; Domingos de Jesus Rodrigues; Pedro Lage Viana; Helena de Godoy Bergallo; Geraldo Wilson Fernandes; Tiago Shizen Pacheco Toma; Helena Streit; Gerhard Ernst Overbeck; Alberico Queiroz Salgueiro de Souza; Albertina Pimentel Lima; et al. (Science of The Total Environment, 2024)

Optimizing sheep growth curves using a meta-heuristic algorithm - Marco Antonio Campos Benvenga; Irenilza de Alencar Nääs; Nilsa Duarte da Silva Lima; Aylpy Renan Dutra Santos; Fernando Miranda de Vargas Junior (Tropical Animal Health and Production, 2024)

Effect of replacing Tifton 85 hay with Moringa hay (Moringa oleifera L.) on the nutrient metabolism, metabolic profile, and water balance of sheep - Elisomar André da Silva; Thiago Luís Alves Campos de Araújo; Marília Williani Filgueira Pereira; José Geraldo Medeiros da Silva; Guilherme Ferreira da Costa Lima; Natália Ingrid Souto da Silva; Michelly Fernandes de Macedo; Fernando Lucas Monteiro Medeiros; Stela Antas Urbano; Maria Mirna Gonçalves Oliveira; Emerson Marcos Nascimento Silva; Dorgival Morais de Lima Junior (Tropical Animal Health and Production, 2024)

Effects of Complex and Contrast Training on Strength, Power, and Agility in Professional Futsal Players: A Preliminary Study - Paulo Henrique Pauli; Edilson Fernando de Borba; Michael Pereira da Silva; Marcos Vinicius Soares Martins; Mayara Maciel Batista; Marcus Peikriszwili Tartaruga (Journal of Science in Sport and Exercise, 2024)

APOE genotype, hippocampal volume, and cognitive reserve predict improvement by cognitive training in older adults without dementia: a randomized controlled trial - Pedro Montejo Carrasco; Mercedes Montenegro-Peña; David Prada Crespo; Inmaculada Rodríguez Rojo; Ana Barabash Bustelo; Borja Montejo Rubio; Alberto Marcos Dolado; Fernando Maestú Unturbe; María Luisa Delgado Losada (Cognitive Processing, 2024)

Admixture With Cultivated Sunflower Likely Facilitated Establishment and Spread of Wild Sunflower ( Helianthus annuus ) in Argentina - Fernando Hernández; Román B. Vercellino; Marco Todesco; Natalia Bercovich; Daniel Alvarez; Johanne Brunet; Alejandro Presotto; Loren H. Rieseberg (Molecular Ecology, 2024)
A better understanding of the genetic and ecological factors underlying successful invasions is critical to mitigate the negative impacts of invasive species. Here, we study the invasion history of Helianthus annuus populations from Argentina, with particular emphasis on the role of post‐introduction admixture with cultivated sunflower (also H. annuus ) and climate adaptation driven by large haploblocks. We conducted genotyping‐by‐sequencing of samples of wild populations as well as Argentinian cultivars and compared them with wild (including related annual Helianthus species) and cultivated samples from the native range. We also characterised samples for 11 known haploblocks associated with environmental variation in native populations to test whether haploblocks contributed to invasion success. Population genomics analyses supported two independent geographic sources for Argentinian populations, the central United States and Texas, but no significant contribution of related annual Helianthus species. We found pervasive admixture with cultivated sunflower, likely as result of post‐introduction hybridization. Genomic scans between invasive populations and their native sources identified multiple genomic regions of divergence, possibly indicative of selection, in the invaded range. These regions significantly overlapped between the two native‐invasive comparisons and showed disproportionally high crop ancestry, suggesting that crop alleles contributed to invasion success. We did not find evidence of climate adaptation mediated by haploblocks, yet outliers of genome scans were enriched in haploblock regions and, for at least two haploblocks, the cultivar haplotype was favoured in Argentina. Our results show that admixture with cultivated sunflower played a major role in the establishment and spread of H. annuus populations in Argentina.

Soybean oil as diluent and vehicle for 17α-methyltestosterone in the masculinization of Nile tilapia (Oreochromis niloticus) in clear water and biofloc systems - Franklin Fernando Batista da Costa; Érika Ramos de Alvarenga; Marcos Antônio da Silva; Ludson Guimarães Manduca; Namíbia Rizzari Leite; Vinícius Monteiro Bezerra; Stefani Grace da Silva Moraes; Lara Quintanilha Goulart; Williane Ferreira Menezes; Arthur Cavatti Neto; Thaiza da Silva Campideli; Eduardo Maldonado Turra; et al. (Aquaculture, 2024)

Post-cooling sperm processing can rescue sperm quality of cooled-stored stallion semen - Lorenzo G.T.M. Segabinazzi; Camila de Paula F. Dell’Aqua; Thais Cavalero; Mariana Frasson; Fernando P. Lisboa; Frederico O. Papa; Marco A. Alvarenga (Theriogenology, 2024)

Experimental and theoretical investigation of the treatment of Cu-rich Acid Mine Drainage using iron oxide magnetic nanoparticles - Nelson Naveas; Ruth Pulido; Teófilo Graber; Raúl Martin-Palma; Fernando Agulló-Rueda; Iván Brito; Miguel Ángel García; María Teresa Sevilla; Jacobo Hernández-Montelongo; Álvaro Muñoz-Noval; Carlo Marini; Leonardo Soriano; et al. (Journal of Environmental Chemical Engineering, 2024)

Diazepam nanocapsules as an alternative for sleep induction: Development study and toxicity assessment - Julia Gabriele de Jesus Ferreira; Victoria Givankliff Flores; Mariana Roza Marco; Bianca Bordignon Fraga; Roberta Rodrigues Zorzo; Patrícia da Fonseca de Morais; Fernando Dal Pont Morisso; Juliane Deise Fleck; Mariele Feiffer Charão; Cristiane Bastos de Mattos; Andresa Heemann Betti (Food and Chemical Toxicology, 2024)

Enhancing the hypotensive effect of latanoprost by combining synthetic phosphatidylcholine liposomes with hyaluronic acid and osmoprotective agents - Marco Brugnera; Marta Vicario-de-la-Torre; Miriam Ana González-Cela Casamayor; José Javier López-Cano; Irene Bravo-Osuna; Fernando Huete-Toral; María Luisa González Rubio; Gonzalo Carracedo; Irene Teresa Molina-Martínez; Vanessa Andrés-Guerrero; Rocío Herrero-Vanrell (Drug Delivery and Translational Research, 2024)
The first line of glaucoma treatment focuses on reducing intraocular pressure (IOP) through the prescription of topical prostaglandin analogues, such as latanoprost (LAT). Topical ophthalmic medicines have low bioavailability due to their rapid elimination from the ocular surface. Nanotechnology offers innovative ways of enhancing the ocular bioavailability of antiglaucoma agents while reducing administration frequency. This study aims to combine LAT-loaded synthetic phosphatidylcholine liposomes with hyaluronic acid (0.2% w/v ) and the osmoprotectants betaine (0.40% w/v ) and leucine (0.90% w/v ) (LAT-HA-LIP) to extend the hypotensive effect of LAT while protecting the ocular surface. LAT-HA-LIP was prepared as a mixture of 1,2-dioleoyl-sn-glycero-3-phosphocholine and 1,2-dimyristoyl-sn-glycero-3-phosphocholine, cholesterol and α-tocopherol acetate. LAT-HA-LIP exhibited high drug-loading capacity (104.52 ± 4.10%), unimodal vesicle sizes (195.14 ± 14.34 nm) and a zeta potential of -13.96 ± 0.78 mV. LAT-HA-LIP was isotonic (284.00 ± 1.41 mOsm L −1 ), had neutral pH (7.63 ± 0.01) and had suitable surface tension (44.07 ± 2.70 mN m −1 ) and viscosity (2.69 ± 0.15 mPa s −1 ) for topical ophthalmic administration. LAT-HA-LIP exhibited optimal in vitro tolerance in human corneal and conjunctival epithelial cells. No signs of ocular alteration or discomfort were observed when LAT-HA-LIP was instilled in albino male New Zealand rabbits. Hypotensive studies revealed that, after a single eye drop, the effect of LAT-HA-LIP lasted 24 h longer than that of a marketed formulation and that relative ocular bioavailability was almost three times higher (p < 0.001). These findings indicate the potential ocular protection and hypotensive effect LAT-HA-LIP offers in glaucoma treatment. Graphical abstract

A Cluster of Diutina catenulata Funguria in Patients with Coronavirus Disease 2019 (COVID-19) Hospitalized in a Tertiary Reference Hospital from Rio de Janeiro, Brazil - Rodrigo Almeida-Paes; Marcus de Melo Teixeira; Fernanda Alves de Oliveira; Marcos de Abreu Almeida; Fernando Almeida-Silva; Kim Mattos Geraldo; Estevão Portela Nunes; Bridget M. Baker; Jason E. Stajich; Beatriz Grinsztejn; Valdilea Gonçalves Veloso; Andrea d’Avila Freitas; et al. (Current Microbiology, 2024)

Characterization of SimulCam, a standoff Raman system for scientific support of SuperCam operations on Mars - Jose A. Manrique; Guillermo Lopez-Reyes; Marco Veneranda; Aurelio Sanz-Arranz; Juan Sancho Santamaria; Sofia Julve-Gonzalez; Ivan Reyes-Rodríguez; Teresa Fornaro; Juan Manuel Madariaga; Gorka Arana; Kepa Castro; Ivair Gontijo; et al. (Advances in Space Research, 2024)

Response of forage production to drought in silvopastoral systems in Argentina - Pablo L. Peri; Santiago Toledo; Luis Gándara; Fabio Trinco; Marcos A. Atanasio; Noelia C. Calamari; Edgardo Casaubon; Natalia Martínez; Roxana Ledesma; Federico Gomez; Javier Lara; Lisandro Blanco; et al. (Agroforestry Systems, 2024)

Multiple Pleistocene refugia for Arctic Bell‐Heather revealed with genomic analyses of modern and historic plants - Cassandra Elphinstone; Fernando Hernández; Marco Todesco; Jean‐Sébastien Légaré; Winnie Cheung; Paul C. Sokoloff; Annika Hofgaard; Casper T. Christiansen; Esther R. Frei; Esther Lévesque; Gergana N. Daskalova; Haydn J. D. Thomas; et al. (Journal of Biogeography, 2024)
Aim Arctic plants survived the Pleistocene glaciations in unglaciated refugia. The number, ages, and locations of these refugia are often unclear. We use high‐resolution genomic data from present‐day and Little‐Ice‐Age populations of Arctic Bell‐Heather to re‐evaluate the biogeography of this species and determine whether it had multiple independent refugia or a single refugium in Beringia. Location Circumpolar Arctic and Coastal British Columbia (BC) alpine. Taxon Cassiope tetragona L., subspecies saximontana and tetragona , outgroup C. mertensiana (Ericaceae). Methods We built genotyping‐by‐sequencing (GBS) libraries using Cassiope tetragona tissue from 36 Arctic locations, including two ~250‐ to 500‐year‐old populations collected under glacial ice on Ellesmere Island, Canada. We assembled a de novo GBS reference to call variants. Population structure, genetic diversity and demography were inferred from PCA, ADMIXTURE, fastsimcoal2, SplitsTree, and several population genomics statistics. Results Population structure analyses identified 4–5 clusters that align with geographic locations. Nucleotide diversity was highest in Beringia and decreased eastwards across Canada. Demographic coalescent analyses dated the following splits with Alaska: BC subspecies saximontana (5 mya), Russia (~1.4 mya), Europe (>200–600 kya), and Greenland (~60 kya). Northern Canada populations appear to have formed during the current interglacial (7–9 kya). Admixture analyses show genetic variants from Alaska appear more frequently in present‐day than historic plants on Ellesmere Island. Conclusions Population and demographic analyses support BC, Alaska, Russia, Europe and Greenland as all having had independent Pleistocene refugia. Northern Canadian populations appear to be founded during the current interglacial with genetic contributions from Alaska, Europe and Greenland. We found evidence, on Ellesmere Island, for continued recent gene flow in the last 250–500 years. These results suggest that a re‐analysis of other Arctic species with shallow population structure using higher resolution genomic markers and demographic analyses may help reveal deeper structure and other circumpolar glacial refugia.

Dominance and rarity in tree communities across the globe: Patterns, predictors and threats - Iris Hordijk; Lalasia Bialic‐Murphy; Thomas Lauber; Devin Routh; Lourens Poorter; Malin C. Rivers; Hans ter Steege; Jingjing Liang; Peter B. Reich; Sergio de‐Miguel; Gert‐Jan Nabuurs; Javier G. P. Gamarra; et al. (Global Ecology and Biogeography, 2024)
Aim Ecological and anthropogenic factors shift the abundances of dominant and rare tree species within local forest communities, thus affecting species composition and ecosystem functioning. To inform forest and conservation management it is important to understand the drivers of dominance and rarity in local tree communities. We answer the following research questions: (1) What are the patterns of dominance and rarity in tree communities? (2) Which ecological and anthropogenic factors predict these patterns? And (3) what is the extinction risk of locally dominant and rare tree species? Location Global. Time period 1990–2017. Major taxa studied Trees. Methods We used 1.2 million forest plots and quantified local tree dominance as the relative plot basal area of the single most dominant species and local rarity as the percentage of species that contribute together to the least 10% of plot basal area. We mapped global community dominance and rarity using machine learning models and evaluated the ecological and anthropogenic predictors with linear models. Extinction risk, for example threatened status, of geographically widespread dominant and rare species was evaluated. Results Community dominance and rarity show contrasting latitudinal trends, with boreal forests having high levels of dominance and tropical forests having high levels of rarity. Increasing annual precipitation reduces community dominance, probably because precipitation is related to an increase in tree density and richness. Additionally, stand age is positively related to community dominance, due to stem diameter increase of the most dominant species. Surprisingly, we find that locally dominant and rare species, which are geographically widespread in our data, have an equally high rate of elevated extinction due to declining populations through large‐scale land degradation. Main conclusions By linking patterns and predictors of community dominance and rarity to extinction risk, our results suggest that also widespread species should be considered in large‐scale management and conservation practices.

Decapod crustacean diversity through time and space in a middle-upper Eocene carbonate-siliciclastic platform (southern Jaca Basin, Pyrenees, Spain) - Fernando A. Ferratges; Samuel Zamora; Adiël A. Klompmaker; Marcos Aurell (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Fluorescent labeling of micro/nanoplastics for biological applications with a focus on “true-to-life" tracking - Aliro Villacorta; Camila Cazorla-Ares; Victor Fuentes-Cebrian; Iris H. Valido; Lourdes Vela; Fernando Carrillo-Navarrete; Michelle Morataya-Reyes; Karen Mejia-Carmona; Susana Pastor; Antonia Velázquez; Jéssica Arribas Arranz; Ricard Marcos; et al. (Journal of Hazardous Materials, 2024)

Epigenetic changes induced by chronic and acute chromium stress treatments in Arabidopsis thaliana identified by the MSAP-Seq - Francesco Guarino; Angela Cicatelli; Werther Guidi Nissim; Ilaria Colzi; Cristina Gonnelli; Marcos Fernando Basso; Chiara Vergata; Felice Contaldi; Federico Martinelli; Stefano Castiglione (Chemosphere, 2024)

Revelation of critical gaps in fisheries management of bull kelp Durvillaea antarctica (Chamisso) in the central coast of the Maule Region of Chile through the application of the DPSIR conceptual framework - Fernando Berrios; Marco Ortiz; Jorge E. González (Ocean & Coastal Management, 2024)

Long-term disability after cerebral ischemic stroke following a Bothrops atrox snakebite in the Brazilian Amazon - Karolaine Oliveira Bentes; Robson Luis Oliveira de Amorim; Fabiane Bianca Albuquerque Barbosa; Victor Carlos Pardo Ratis da Silva; Jefferson Valente; Fernando Almeida-Val; Jacqueline de Almeida Gonçalves Sachett; Wuelton Monteiro; Marco Aurélio Sartim (Toxicon, 2024)

Structural analysis applied to the tectonostratigraphic reconstruction of the Abadia dos Dourados Metavolcano-sedimentary Sequence, southern Brasília Orogen: Implications for the West Gondwana assemblage - Fernando Resende Honorato; Marco Antônio Delinardo da Silva; Pamela Pavanetto; Mariana Nunes Marçal Silva (Journal of South American Earth Sciences, 2024)

Oxidative potential of particulate matter and its association to respiratory health endpoints in high-altitude cities in Bolivia - Lucille Borlaza-Lacoste; Valeria Mardoñez; Anouk Marsal; Ian Hough; Vy Ngoc Thuy Dinh; Pamela Dominutti; Jean-Luc Jaffrezo; Andrés Alastuey; Jean-Luc Besombes; Griša Močnik; Isabel Moreno; Fernando Velarde; et al. (Environmental Research, 2024)

Soil organic carbon stocks and fractions under integrated systems and pasture in the Cerrado of Northeast Brazil - Renato Falconeres Vogado; Henrique Antunes de Souza; Edvaldo Sagrilo; Lucélia de Cássia Rodrigues de Brito; Sammy Sidney Rocha Matias; Marcos Lopes Teixeira Neto; José Oscar Lustosa de Oliveira Junior; Hosana Aguiar Freitas de Andrade; Luiz Fernando Carvalho Leite (CATENA, 2024)

Evaluation of different supportive treatments during packed cell volume replacement in calves naturally infected with tick fever agents - Alexandre Braga Scarpa; Vanessa Ferreira Salvador; Luccas Lourenzzo Lima Lins Leal; Igor Maciel Lopes de Morais; Luiz Fellipe Monteiro Couto; Luciana Maffini Heller; Dina María Beltrán Zapa; Lídia Mendes de Aquino; Daniel de Castro Rodrigues; Nicolas Jalowitzki de Lima; Vando Edésio Soares; Lorena Lopes Ferreira; et al. (Veterinary Research Communications, 2024)

Molecular detection of Bartonella spp. in bat-associated macronyssid mites (Acari: Macronyssidae) from Southern and Southeastern Brazil - Maria Eduarda Moraes das Chagas; Victor Souza de Mello-Oliveira; Mariane Guerro-de-Souza; Ana Cláudia Calchi; Ana Carolina Castro-Santiago; Érica Munhoz de Mello; Igor Massahiro Souza de Suguiura; Elizabete Captivo Lourenço; Katia Maria Famadas; Ashley P. G. Dowling; Marcos Rogério André; Darci Moraes Barros-Battesti; et al. (Veterinary Research Communications, 2024)

Inter-software reliability and agreement for follicular and luteal morphometric and echotextural ultrasonographic parameters in beef cattle - César Augusto Pinzón-Osorio; Marco Alves Machado; Julia Nobre Blank Camozzato; Gabriella dos Santos Velho; André Gustavo Cabrera Dalto; Monique Tomazele Rovani; Fernando Caetano de Oliveira; Marcelo Bertolini (Animal Reproduction Science, 2024)

Reproductive biology of the threatened Kaempfer’s tody-tyrant (Hemitriccus kaempferi) - Guilherme Willrich; Fernando Bittencourt de Farias; Luiz dos Anjos; Marcos Robalinho Lima (Ornithology Research, 2024)

Cotton plants overexpressing the Bacillus thuringiensis Cry23Aa and Cry37Aa binary-like toxins exhibit high resistance to the cotton boll weevil (Anthonomus grandis) - Thuanne Pires Ribeiro; Diogo Martins-de-Sa; Leonardo Lima Pepino Macedo; Isabela Tristan Lourenço-Tessutti; Gustavo Caseca Ruffo; João Pedro Abreu Sousa; Julia Moura do Rósario Santana; Osmundo Brilhante Oliveira-Neto; Stéfanie Menezes Moura; Maria Cristina Mattar Silva; Carolina Vianna Morgante; Nelson Geraldo Oliveira; et al. (Plant Science, 2024)

Geography and ecology shape the phylogenetic composition of Amazonian tree communities - Bruno Garcia Luize; David Bauman; Hans ter Steege; Clarisse Palma‐Silva; Iêda Leão do Amaral; Luiz de Souza Coelho; Francisca Dionízia de Almeida Matos; Diógenes de Andrade Lima Filho; Rafael P. Salomão; Florian Wittmann; Carolina V. Castilho; Marcelo de Jesus Veiga Carim; et al. (Journal of Biogeography, 2024)
Aim Amazonia hosts more tree species from numerous evolutionary lineages, both young and ancient, than any other biogeographic region. Previous studies have shown that tree lineages colonized multiple edaphic environments and dispersed widely across Amazonia, leading to a hypothesis, which we test, that lineages should not be strongly associated with either geographic regions or edaphic forest types. Location Amazonia. Taxon Angiosperms (Magnoliids; Monocots; Eudicots). Methods Data for the abundance of 5082 tree species in 1989 plots were combined with a mega‐phylogeny. We applied evolutionary ordination to assess how phylogenetic composition varies across Amazonia. We used variation partitioning and Moran's eigenvector maps (MEM) to test and quantify the separate and joint contributions of spatial and environmental variables to explain the phylogenetic composition of plots. We tested the indicator value of lineages for geographic regions and edaphic forest types and mapped associations onto the phylogeny. Results In the terra firme and várzea forest types, the phylogenetic composition varies by geographic region, but the igapó and white‐sand forest types retain a unique evolutionary signature regardless of region. Overall, we find that soil chemistry, climate and topography explain 24% of the variation in phylogenetic composition, with 79% of that variation being spatially structured ( R 2 = 19% overall for combined spatial/environmental effects). The phylogenetic composition also shows substantial spatial patterns not related to the environmental variables we quantified ( R 2 = 28%). A greater number of lineages were significant indicators of geographic regions than forest types. Main Conclusion Numerous tree lineages, including some ancient ones (>66 Ma), show strong associations with geographic regions and edaphic forest types of Amazonia. This shows that specialization in specific edaphic environments has played a long‐standing role in the evolutionary assembly of Amazonian forests. Furthermore, many lineages, even those that have dispersed across Amazonia, dominate within a specific region, likely because of phylogenetically conserved niches for environmental conditions that are prevalent within regions.

Sampling completeness changes perceptions of continental scale climate–species richness relationships in odonates - Fernanda Alves‐Martins; Juliana Stropp; Leandro Juen; Richard J. Ladle; Jorge M. Lobo; Javier Martinez‐Arribas; Paulo De Marco Júnior; Leandro Schlemmer Brasil; Victor Rennan Santos Ferreira; Rafael Costa Bastos; Alex Córdoba‐Aguilar; Emmy Fiorella Medina‐Espinoza; et al. (Journal of Biogeography, 2024)
Aim Insects are one of the least studied taxa, with most species lacking basic ecological and biogeographical information. This problem is particularly acute in the tropics, where low sampling effort hampers accurate estimates of species richness at scale and potentially confounds efforts to identify the drivers of biogeographical gradients. Here, we evaluate the quality of the data on the distribution and diversity of odonate species in the Neotropics, while also examining the influence of sampling completeness on climate–richness relationships using a comprehensive database of odonates. Location The Neotropics. Taxon Odonata. Methods Using 56,535 records collected from 1970 to 2021, we assess whether climate–species richness models vary under different scenarios of survey completeness. Results Our survey compilation revealed that most Neotropical diversity of Odonata likely remains unknown. Only 1% of the one‐degree cells covering the Neotropics held reliable information on odonate species richness, with particularly severe gaps in the Caribbean, Central America, northeastern Brazil and northern Chile. Temperature, precipitation and potential evapotranspiration exert consistent effects on Odonata richness across the entire Neotropics, regardless the level of survey completeness. Whereas seasonality‐related variables are less important predictors of species richness at the biogeographical scale. Main Conclusions By highlighting areas where inventories are more reliable and identifying regions that require increased data collection efforts and mobilization, our assessment offers a roadmap for improving the reliability of odonate inventories in the Neotropics. Furthermore, our findings underscore the importance of accounting for varying levels of survey completeness in macroecological models to reveal robust climate–species richness relationships. Simultaneously, they highlight strong climatic predictors of species richness, irrespective of survey effort intensity. These predictors provide a solid foundation for modelling and predicting odonate species richness in the Neotropics.

Decoding the best automated segmentation tools for vascular white matter hyperintensities in the aging brain: a clinician’s guide to precision and purpose - Lucia Torres-Simon; Alberto del Cerro-León; Miguel Yus; Ricardo Bruña; Lidia Gil-Martinez; Alberto Marcos Dolado; Fernando Maestú; Juan Arrazola-Garcia; Pablo Cuesta (GeroScience, 2024)

Growth hormone stimulates the in vitro development and establishment of Haemonchus contortus in sheep - Adolfo Sánchez-Paredes; César Cuenca-Verde; María Guadalupe Prado-Ochoa; Jorge Morales-Montor; Fernando Alba-Hurtado; Marco Antonio Muñoz-Guzmán (Veterinary Parasitology, 2024)

ENSO effects on the relationship between aerosols and evapotranspiration in the south of the Amazon biome - Rafael Palácios; Daniela Castagna; Luzinete Barbosa; Adilson P. Souza; Breno Imbiriba; Cornélio A. Zolin; Danielle Nassarden; Leilane Duarte; Fernando G. Morais; Marco A. Franco; Glauber Cirino; Paulo Kuhn; et al. (Environmental Research, 2024)

Soil Properties Related to Phosphorus Sorption and Prediction of Maximum Phosphorus Adsorption Capacity of Soils from Southern Brazil - Fernando Marcos Brignoli; Gilmar Luiz Mumbach; Luke Gatiboni; João Henrique Vieira de Almeida Junior; João Vitor Ferreira Gonçalves; Marcelo Augusto Batista (Journal of Soil Science and Plant Nutrition, 2024)

Failure Mechanisms of Shear Zones in an Undisturbed Residual Soil by SEM Image Analysis - Mariane Borba de Lemos; Fernando A. M. Marinho; Carina Ulsen; Marcos Egydio da Silva (Geotechnical and Geological Engineering, 2024)

Multispecies and multibiomarker assessment of fish health from Iguaçu River reservoir, Southern Brazil - Dámaso Angel Rubio-Vargas; Tobias Pereira de Morais; Marco Antonio Ferreira Randi; Francisco Filipak Neto; Cláudia Feijó Ortolani-Machado; César de Castro Martins; Andrea Pinto Oliveira; Mariana Gallucci Nazário; Fernando Cesar Alves da Silva Ferreira; Iracema Opuskevitch; Dieter Penner; Juan Esquivel-Muelbert; et al. (Environmental Monitoring and Assessment, 2024)

MelastomaTRAITs 1.0: A database of functional traits in M elastomataceae, a large pantropical angiosperm family - Marcelo Reginato; Carlos A. Ordónez‐Parra; João Vitor S. Messeder; Vinicius L. G. Brito; Agnes Dellinger; Ricardo Kriebel; Camilla Marra; Lilian Melo; Tatiana Cornelissen; Lisieux Fuzessy; Patricia Sperotto; Manuela Calderón‐Hernández; et al. (Ecology, 2024)
The recent availability of open‐access repositories of functional traits has revolutionized trait‐based approaches in ecology and evolution. Nevertheless, the underrepresentation of tropical regions and lineages remains a pervasive bias in plant functional trait databases, which constrains large‐scale assessments of plant ecology, evolution, and biogeography. Here, we present MelastomaTRAITs 1.0, a comprehensive and updatable database of functional traits for the pantropical Melastomataceae, the ninth‐largest angiosperm family with 177 genera and more than 5800 species. Melastomataceae encompass species with a wide diversity of growth forms (herbs, shrubs, trees, epiphytes, and woody climbers), habitats (including tropical forests, savannas, grasslands, and wetlands from sea level to montane areas above the treeline), ecological strategies (from pioneer, edge‐adapted and invasive species to shade‐tolerant understory species), geographic distribution (from microendemic to continental‐wide distribution), reproductive, pollination, and seed dispersal systems. MelastomaTRAITs builds on 581 references, such as taxonomic monographs, ecological research, and unpublished data, and includes four whole‐plant traits, six leaf traits, 11 flower traits, 18 fruit traits, and 27 seed traits for 2520 species distributed in 144 genera across all 21 tribes. Most data come from the Neotropics where the family is most species‐rich. Miconieae (the largest tribe) contains the highest number of trait records (49.6%) and species (41.1%) records. The trait types with the most information in the database were whole‐plant traits, flowers, and leaf traits. With the breadth of functional traits recorded, our database helps to fill a gap in information for tropical plants and will significantly improve our capacity for large‐scale trait‐based syntheses across levels of organization, plant–animal interactions, regeneration ecology, and thereby support conservation and restoration programs. There are no copyright restrictions on the dataset; please cite this data paper when reusing the data.

Workflow to facilitate the detection of new psychoactive substances and drugs of abuse in influent urban wastewater - Richard Bade; Denice van Herwerden; Nikolaos Rousis; Sangeet Adhikari; Darren Allen; Christine Baduel; Lubertus Bijlsma; Tim Boogaerts; Dan Burgard; Andrew Chappell; Erin M. Driver; Fernando Fabriz Sodre; et al. (Journal of Hazardous Materials, 2024)

Neotectonic landforms of the Neoproterozoic basement of Southeastern Brazil: The case of the north border of the São Paulo Basin - Marcos Roberto Pinheiro; Fernando Nadal Junqueira Villela; Paola Cianfarra (Geomorphology, 2024)

Impact of defibrillation technique on the rheological, thermo-mechanical, and nutritional properties of nanosuspensions produced from multiple fractions of pinhão seed (Araucaria angustifolia (Bertol.) Kuntze) - Fernando Castro Leal; Karina Mayumi Ueda; Matheus Samponi Tucunduva Arantes; Tielidy Angelina de Morais de Lima; Fabrício Augusto Hansel; Washington Luiz Esteves Magalhães; Cristiane Vieira Helm; Rilton Alves de Freitas; Fabiane Oliveira Farias; Marcos R. Mafra; Luciana Igarashi-Mafra (Food Chemistry, 2024)

Correction: Aerosol optical depth and water vapor variability assessed through autocorrelation analysis - Marco A. Franco; Fernando G. Morais; Luciana V. Rizzo; Rafael Palácios; Rafael Valiati; Márcio Teixeira; Luiz A. T. Machado; Paulo Artaxo (Meteorology and Atmospheric Physics, 2024)

Recurrent bacteremia and endocarditis due to Staphylococcus capitis in a patient with Bowen’s disease: a case report - Alejandro Díez-Vidal; María Elena González-García; Irene Marco-Clement; Javier Azores-Moreno; Patricia Roces-Álvarez; Cristina Marcelo-Calvo; Patricia Martínez-Martín; Borja González-Muñoz; Fernando Fernández-Hinojal; Belén Loeches (European Journal of Clinical Microbiology & Infectious Diseases, 2024)

Unearthing the soil‐borne microbiome of land plants - Raúl Ochoa‐Hueso; David J. Eldridge; Miguel Berdugo; Pankaj Trivedi; Blessing Sokoya; Concha Cano‐Díaz; Sebastian Abades; Fernando Alfaro; Adebola R. Bamigboye; Felipe Bastida; José L. Blanco‐Pastor; Asunción de los Rios; et al. (Global Change Biology, 2024)
Plant–soil biodiversity interactions are fundamental for the functioning of terrestrial ecosystems. Yet, the existence of a set of globally distributed topsoil microbial and small invertebrate organisms consistently associated with land plants (i.e., their consistent soil‐borne microbiome), together with the environmental preferences and functional capabilities of these organisms, remains unknown. We conducted a standardized field survey under 150 species of land plants, including 58 species of bryophytes and 92 of vascular plants, across 124 locations from all continents. We found that, despite the immense biodiversity of soil organisms, the land plants evaluated only shared a small fraction (less than 1%) of all microbial and invertebrate taxa that were present across contrasting climatic and soil conditions and vegetation types. These consistent taxa were dominated by generalist decomposers and phagotrophs and their presence was positively correlated with the abundance of functional genes linked to mineralization. Finally, we showed that crossing environmental thresholds in aridity (aridity index of 0.65, i.e., the transition from mesic to dry ecosystems), soil pH (5.5; i.e., the transition from acidic to strongly acidic soils), and carbon (less than 2%, the lower limit of fertile soils) can result in drastic disruptions in the associations between land plants and soil organisms, with potential implications for the delivery of soil ecosystem processes under ongoing global environmental change.

Camera trap surveys of A tlantic F orest mammals: A data set for analyses considering imperfect detection (2004–2020) - Ingridi Camboim Franceschi; Rubem Augusto da Paixão Dornas; Isabel Salgueiro Lermen; Artur Vicente Pfeifer Coelho; Ademir Henrique Vilas Boas; Adriano Garcia Chiarello; Adriano Pereira Paglia; Agnis Cristiane de Souza; Alana Rafaela Borsekowsky; Alessandro Rocha; Alex Bager; Alexander Zaidan de Souza; et al. (Ecology, 2024)
Camera traps became the main observational method of a myriad of species over large areas. Data sets from camera traps can be used to describe the patterns and monitor the occupancy, abundance, and richness of wildlife, essential information for conservation in times of rapid climate and land‐cover changes. Habitat loss and poaching are responsible for historical population losses of mammals in the Atlantic Forest biodiversity hotspot, especially for medium to large‐sized species. Here we present a data set from camera trap surveys of medium to large‐sized native mammals (>1 kg) across the Atlantic Forest. We compiled data from 5380 ground‐level camera trap deployments in 3046 locations, from 2004 to 2020, resulting in 43,068 records of 58 species. These data add to existing data sets of mammals in the Atlantic Forest by including dates of camera operation needed for analyses dealing with imperfect detection. We also included, when available, information on important predictors of detection, namely the camera brand and model, use of bait, and obstruction of camera viewshed that can be measured from example pictures at each camera location. Besides its application in studies on the patterns and mechanisms behind occupancy, relative abundance, richness, and detection, the data set presented here can be used to study species' daily activity patterns, activity levels, and spatiotemporal interactions between species. Moreover, data can be used combined with other data sources in the multiple and expanding uses of integrated population modeling. An R script is available to view summaries of the data set. We expect that this data set will be used to advance the knowledge of mammal assemblages and to inform evidence‐based solutions for the conservation of the Atlantic Forest. The data are not copyright restricted; please cite this paper when using the data.

Osteomyelitis in the manus of Smilodon populator (Felidae, Machairodontinae) from the Late Pleistocene of South America - Carlos A. Luna; Roy R. Pool; Marcos D. Ercoli; Nicolás R. Chimento; Fernando H. de S. Barbosa; Alfredo E. Zurita; Pedro Cuaranta (Palaeoworld, 2024)

Exogenous Methyl Salicylate treatment increases tomato zingiberene levels and decreases infestation of adult whiteflies and red spider mites - Marco dos Reis Brugnerotto; Mauricio Ursi Ventura; Luiz Vitor Barbosa de Oliveira; Fernando Teruhiko Hata; Éder Málaga Carrilho; Luiz Henrique de Souza Machado; Luis Eduardo Bocalete; Juliano Tadeu Vilela de Resende (Phytoparasitica, 2024)

Aerosol optical depth and water vapor variability assessed through autocorrelation analysis - Marco A. Franco; Fernando G. Morais; Luciana V. Rizzo; Rafael Palácios; Rafael Valiati; Márcio Teixeira; Luiz A. T. Machado; Paulo Artaxo (Meteorology and Atmospheric Physics, 2024)

Valorization of winemaking residues as biochar for removing Ni(II) from real industrial painting process effluent in a fixed-bed column - Fernando de Lima Carvalho; Jaqueline Pozzada dos Santos; Salah Knani; Amani Alruwaili; Rejiane da Rosa Schio; Sabrina Frantz Lütke; Felipe Ketzer; Marcos Leandro Silva Oliveira; Luis Felipe Oliveira Silva; Guilherme Luiz Dotto (Environmental Science and Pollution Research, 2024)

Pollutant bioaccumulation in sentinel fish chronically exposed in Iguaçu river reservoirs (Southern Brazil) and human health risk of fish consumption - Dámaso Angel Rubio-Vargas; Tobias Pereira de Morais; Marco Antônio Ferreira Randi; Francisco Filipak Neto; César de Castro Martins; Andrea Pinto Oliveira; Mariana Gallucci Nazário; Fernando Cesar Alves da Silva Ferreira; Iracema Opuskevitch; Dieter Penner; Juan Esquivel-Muelbert; Maritana Mela Prodocimo; et al. (Chemosphere, 2024)

December 8, 2022 Meteotsunami Along the Southeastern Coast of South America: A Case Study - Walter Dragani; Iael Perez; Marcos Saucedo; Fernando Oreiro; Rubén Medina; Mónica Fiore (Pure and Applied Geophysics, 2024)

A Novel Digital Educational Strategy Improves Treatment Adherence and Quality of Life in Patients with Multiple Myeloma - Juan Guio; Andrés Melo; Mateo Mejía Saldarriaga; Cynthia Fuentes; Natalia Tíjaro-Ovalle; Andrés Borda; Yuli Guzmán; Elías Bolaños; Guillermo Quintero; Mónica Duarte; Claudia Agudelo; Soraya Aparicio; et al. (Journal of Cancer Education, 2024)

Hybrid modeling for grassland productivity prediction: A parametric and machine learning technique for grazing management with applicability to digital twin decision systems - José M. Paruelo; Marcos Texeira; Fernando Tomasel (Agricultural Systems, 2024)

Airborne geophysics, petrophysics, geochemistry and geology of Ni-Cu (Co-Au-PGE) footprints to define exploration targets in mafic-ultramafic rocks - Thiago Lima Mendes; Marcelo Henrique Leão-Santos; Luiz Fernando Cursino Tabosa; Welitom Rodrigues Borges; Cleber dos Santos Alves; Marcos Tadeu de Freitas Suita (Journal of South American Earth Sciences, 2024)

Identification and expression profile of the SMAX/SMXL family genes in chickpea and lentil provide important players of biotechnological interest involved in plant branching - Marcos Fernando Basso; Felice Contaldi; Fabrizio Lo Celso; César Milton Baratto; Maria Fatima Grossi-de-Sa; Giampaolo Barone; Antonio Ferrante; Federico Martinelli (Planta, 2024)
Main conclusion SMAX/SMXL family genes were successfully identified and characterized in the chickpea and lentil and gene expression data revealed several genes associated with the modulation of plant branching and powerful targets for use in transgenesis and genome editing. Abstract Strigolactones (SL) play essential roles in plant growth, rooting, development, and branching, and are associated with plant resilience to abiotic and biotic stress conditions. Likewise, karrikins (KAR) are “plant smoke-derived molecules” that act in a hormonal signaling pathway similar to SL playing an important role in seed germination and hairy root elongation. The SMAX/SMXL family genes are part of these two signaling pathways, in addition to some of these members acting in a still little known SL- and KAR-independent signaling pathway. To date, the identification and functional characterization of the SMAX/SMXL family genes has not been performed in the chickpea and lentil. In this study, nine SMAX/SMXL genes were systematically identified and characterized in the chickpea and lentil, and their expression profiles were explored under different unstressless or different stress conditions. After a comprehensive in silico characterization of the genes, promoters, proteins, and protein-protein interaction network, the expression profile for each gene was determined using a meta-analysis from the RNAseq datasets and complemented with real-time PCR analysis. The expression profiles of the SMAX/SMXL family genes were very dynamic in different chickpea and lentil organs, with some genes assuming a tissue-specific expression pattern. In addition, these genes were significantly modulated by different stress conditions, indicating that SMAX/SMXL genes, although working in three distinct signaling pathways, can act to modulate plant resilience. Most CaSMAX/SMXL and partner genes such as CaTiE1 and CaLAP1 , have a positive correlation with the plant branching level, while most LcSMAX/SMXL genes were less correlated with the plant branching level. The SMXL6 , SMXL7 , SMXL8 , TiE1 , LAP1 , BES1 , and BRC1 genes were highlighted as powerful targets for use in transgenesis and genome editing aiming to develop chickpea and lentil cultivars with improved architecture. Therefore, this study presented a detailed characterization of the SMAX/SMXL genes in the chickpea and lentil, and provided new insights for further studies focused on each SMAX/SMXL gene.

In planta RNAi targeting Meloidogyne incognita Minc16803 gene perturbs nematode parasitism and reduces plant susceptibility - Valdeir Junio Vaz Moreira; Daniele Heloísa Pinheiro; Isabela Tristan Lourenço-Tessutti; Marcos Fernando Basso; Maria E. Lisei-de-Sa; Maria C. M. Silva; Etienne G. J. Danchin; Patrícia M. Guimarães; Priscila Grynberg; Ana C. M. Brasileiro; Leonardo L. P. Macedo; Carolina V. Morgante; et al. (Journal of Pest Science, 2024)

Cannabaceae comparative analysis based on plastid genome evolution - Cristiane Barbosa D’Oliveira Matielo; Geferson Fernando Metz; Rafael Plá Matielo Lemos; Filipe de Carvalho Victoria; Flávio Anastácio de Oliveira Camargo; Valdir Marcos Stefenon (Journal of Crop Science and Biotechnology, 2024)

Sex differences in the progression to Alzheimer’s disease: a combination of functional and structural markers - Alberto Fernández; Pablo Cuesta; Alberto Marcos; Mercedes Montenegro-Peña; Miguel Yus; Inmaculada Concepción Rodríguez-Rojo; Ricardo Bruña; Fernando Maestú; María Eugenia López (GeroScience, 2023)

Impact of selection for growth and stocking density on Nile tilapia production in the biofloc system - Arthur Cavatti Neto; Érika Ramos de Alvarenga; Fabio Luiz Buranelo Toral; Namíbia Rizzari Leite; Franklin Fernando Batista da Costa; Lara Quintanilla Goulart; Rebeca Dias Serafim Correa; Marcos Antônio da Silva; Bruno Dias dos Santos; Arthur Francisco Araújo Fernandes; Eduardo Maldonado Turra (Aquaculture, 2023)

Nitrous oxide and methane emissions from a Ferralsol as affected by loblolly pine cultivation time in subtropical Brazil - Mariana Alves Ibarr; Josiléia Acordi Zanatta; Jeferson Dieckow; Ricardo Henrique Ribeiro; Janquieli Schirmann; Marcos Fernando Glück Rachwal; James Stahl; Priscila Luzia Simon (Science of The Total Environment, 2023)

Assessment of methionine plus cystine requirement of tambaqui (Colossoma macropomum) based on zootechnical performance, body composition, erythrogram, and plasmatic and hepatic metabolites - Aline da Silva Rocha; Carlos Eduardo Copatti; Rafael Silva Marchão; Thaisa Sales Costa; Guilherme Silva Santana; Márcia Café Coelho; Gilmar Amaro Pereira; David Ramos da Rocha; Antônio Cleber da Silva Camargo; Felipe Barbosa Ribeiro; Marcos Antonio Delmondes Bomfim; José Fernando Bibiano Melo (Veterinary Research Communications, 2023)

Synthesis, characterization, and reusability of novel nanobiocomposite of endophytic fungus Aspergillus flavus and magnetic nanoparticles (Fe3O4) with dye bioremediation potential - Andressa Domingos Polli; Verci Alves de Oliveira Junior; Marcos Alessandro dos Santos Ribeiro; Julio Cesar Polonio; Bianca Rosini; João Arthur dos Santos Oliveira; Raquel Dosciatti Bini; Halison Correia Golias; Cintia Zani Fávaro-Polonio; Ravely Casarotti Orlandelli; Veronica Elisa Pimenta Vicentini; Luiz Fernando Cotica; et al. (Chemosphere, 2023)

How natural and anthropogenic factors should drive microplastic behavior and fate: The scenario of Brazilian urban freshwater - Fernando F. Sodré; Imisi M. Arowojolu; Maria C. Canela; Rodrigo S. Ferreira; Andreia N. Fernandes; Cassiana C. Montagner; Cristiane Vidal; Mariana A. Dias; Gilberto Abate; Leticia C. da Silva; Marco T. Grassi; Crislaine Bertoldi; et al. (Chemosphere, 2023)

Expression profile of the NCED/CCD genes in chickpea and lentil during abiotic stress reveals a positive correlation with increased plant tolerance - Marcos Fernando Basso; Felice Contaldi; Fabrizio Lo Celso; Erna Karalija; Lenin Celiano Paz-Carrasco; Giampaolo Barone; Antonio Ferrante; Federico Martinelli (Plant Science, 2023)

Biodiversity and carbon conservation under the ecosystem stability of tropical forests - Lucas Andrigo Maure; Milena Fiuza Diniz; Marco Túlio Pacheco Coelho; Paulo Guilherme Molin; Fernando Rodrigues da Silva; Erica Hasui (Journal of Environmental Management, 2023)

A novel strategy to predict clonal composites by jointly modeling spatial variation and genetic competition - Filipe M. Ferreira; Saulo F.S. Chaves; Leonardo L. Bhering; Rodrigo S. Alves; Elizabete K. Takahashi; João E. Sousa; Marcos D.V. Resende; Fernando P. Leite; Salvador A. Gezan; José M.S. Viana; Samuel B. Fernandes; Kaio O.G. Dias (Forest Ecology and Management, 2023)

Efficacy of ethyl-4-bromophenyl carbamate on different Rhipicephalus microplus stages implanted in cattle - Sandra Lizeth Iturbe-Requena; César Cuenca-Verde; María Guadalupe Prado-Ochoa; Víctor Hugo Vázquez-Valadez; Marco Antonio Muñoz-Guzmán; Enrique Angeles; Fernando Alba-Hurtado (Experimental and Applied Acarology, 2023)
The effect of ethyl-4-bromophenyl carbamate on different Rhipicephalus microplus stages implanted in cattle was evaluated using the pen test with infestation chambers. Twelve steers were distributed into four groups (n = 3), each with four chambers (12 chambers per group), where approximately 1,000 R. microplus larvae were placed in each chamber. The chambers of the first group were sprayed with a solution of ethyl-4-bromophenyl carbamate (0.668 mg/mL) on day 2 post-infestation (PI) (exposed larvae). The chambers of the second group were sprayed with the same solution on day 8 PI (exposed nymphs), and the chambers of the third group were sprayed on day 16 PI (exposed adults) with the same solution. The chambers of the fourth group were used as controls. The percentages of engorged females, egg laying, egg production and egg hatching were evaluated in all groups. The percentage of cumulative reduction of hatched larvae was 98.3, 96.1 and 94.4% when larvae, nymph and adult stages were treated, respectively. The average cumulative reduction of hatched larvae, considering the three treated stages, was 96.3%, whereby the reproductive potential of this tick was drastically reduced. In conclusion, ethyl-4-bromophenyl carbamate acted as an ixodicide (lethal effect) when larval stages were sprayed and as a growth regulator when nymphal and adult stages were sprayed. The sum of these effects had a direct impact on the efficacy of the product in the pen test, and future studies will indicate the potential use of this product for tick control.

Nutrient cycling aspects as possible ecosystem functional indicators of successional stage in Semideciduous seasonal forest, Rio de Janeiro state, Brazil - Rodrigo Camara de Souza; Marcos Gervasio Pereira; Deivid Lopes Machado; Luciano de Oliveira Toledo; Carlos Eduardo Gabriel Menezes; Gilsonley Lopes dos Santos; Fernando Silva Coutinho; Roni Fernandes Guareschi; Victória Maria Monteiro Mendonça (Acta Oecologica, 2023)

Lime and gypsum application to low-acidity soils: Changes in soil chemical properties, residual lime content and crop agronomic performance - Evandro Antonio Minato; Fernando Marcos Brignoli; Michel Esper Neto; Marcos Renan Besen; Bruno Maia Abdo Rahmen Cassim; Rodrigo Sakurada Lima; Cássio Antonio Tormena; Tadeu Takeyoshi Inoue; Marcelo Augusto Batista (Soil and Tillage Research, 2023)

Spatial and temporal changes of subtidal benthic communities in Antofagasta Bay (SE Pacific) stressed by permanent human disturbances - Brenda B. Hermosillo-Núñez; Leonardo Campos; Fernando Berrios; Marco Ortiz (Regional Studies in Marine Science, 2023)

Correction to: Feather stable isotopes (δ2 Hf and δ13Cf) identify the Sub-Saharan wintering grounds of turtle doves from Europe - Melanie Marx; Yvonne R. Schumm; Kevin J. Kardynal; Keith A. Hobson; Gregorio Rocha; Pavel Zehtindjiev; Dimitris Bakaloudis; Benjamin Metzger; Jacopo G. Cecere; Fernando Spina; Marco Cianchetti-Benedetti; Sylke Frahnert; et al. (European Journal of Wildlife Research, 2023)

Cost Efficiencies of the Shrimp Fishery in Mexico: A Stochastic Frontier Analysis - Gerzaín Avilés-Polanco; Marco Antonio Almendarez-Hernández; Luis Felipe Beltrán-Morales; Fernando Aranceta-Garza (Fishes, 2023)
Fishing sector fuel subsidies are designed to increase profitability by reducing costs. However, despite the number of liters of fuel subsidized in 2018 in Mexico, there is no information available on the effectiveness of the subsidies in reducing cost inefficiencies. The purpose of this study was to estimate the cost efficiency of shrimp fishing companies in Mexico, as well as measure the impact of fuel subsidies on the cost inefficiency of the sector from 2003 to 2018. The True Fixed Effects model was used to represent a Cobb–Douglas stochastic production frontier, which included a shrimp fishing inefficiencies model. The results indicate that shrimp fishing companies could reduce their costs by 25% without reducing their catch levels. Fishing companies in the Gulf of Mexico were more efficient than those operating in the Gulf of California and the South Pacific. Fuel subsidies reduce cost inefficiencies, with a greater effect when the subsidy reaches a level of 20% of the total liters of subsidized fuel.

Soil toxicity in a protected area in Brazil: Cytotoxic, genotoxic, and toxic effects - Daiana Lauxen Schutz; Inara Giacobbo de Marco; Anna Gabriela Drummond Xavier Teles; Ana Paula de Oliveira Schmitz; Eduardo Michel Vieira Gomes; Fernando Cesar Manosso; Ivane Benedetti Tonial; Juan Carlos Pokrywiecki; Rodrigo Lingnau; Ticiane Sauer Pokrywieki; Aparecido Nivaldo Módenes; Fernando Rodolfo Espinoza Quiñones; et al. (Science of The Total Environment, 2023)

Effects of increasing soil phosphorus and association with ectomycorrhizal fungi (Pisolithus microcarpus) on morphological, nutritional, biochemical, and physiological parameters of Pinus taeda L - Matheus Severo de Souza Kulmann; Marcos Vinícius Miranda Aguilar; Adriele Tassinari; Raíssa Schwalbert; Luciane Almeri Tabaldi; Maristela Machado Araujo; Zaida Ines Antoniolli; Fernando Teixeira Nicoloso; Gustavo Brunetto; Mauro Valdir Schumacher (Forest Ecology and Management, 2023)

Biochar and Forage Peanut improve pastures: Evidence from a field experiment in Brazil - Agnieszka E. Latawiec; Aline F. Rodrigues; Katarzyna A. Korys; Maiara Mendes; Marcio Rangel; Ana Castro; Wenceslau Teixeira; Judson F. Valentim; Ednaldo Araujo; Luiz Fernando Duarte de Moraes; Vinicius Pacheco; Marcos Mendes; et al. (Agriculture, Ecosystems & Environment, 2023)

Giants of the Amazon: How does environmental variation drive the diversity patterns of large trees? - Robson Borges de Lima; Eric Bastos Görgens; Diego Armando S. da Silva; Cinthia Pereira de Oliveira; Anderson Pedro B. Batista; Rinaldo L. Caraciolo Ferreira; Flavia R. C. Costa; Renato A. Ferreira de Lima; Perseu da Silva Aparício; Jadson Coelho de Abreu; José Antônio Aleixo da Silva; Aretha Franklin Guimaraes; et al. (Global Change Biology, 2023)
For more than three decades, major efforts in sampling and analyzing tree diversity in South America have focused almost exclusively on trees with stems of at least 10 and 2.5 cm diameter, showing highest species diversity in the wetter western and northern Amazon forests. By contrast, little attention has been paid to patterns and drivers of diversity in the largest canopy and emergent trees, which is surprising given these have dominant ecological functions. Here, we use a machine learning approach to quantify the importance of environmental factors and apply it to generate spatial predictions of the species diversity of all trees (dbh ≥ 10 cm) and for very large trees (dbh ≥ 70 cm) using data from 243 forest plots (108,450 trees and 2832 species) distributed across different forest types and biogeographic regions of the Brazilian Amazon. The diversity of large trees and of all trees was significantly associated with three environmental factors, but in contrasting ways across regions and forest types. Environmental variables associated with disturbances, for example, the lightning flash rate and wind speed, as well as the fraction of photosynthetically active radiation, tend to govern the diversity of large trees. Upland rainforests in the Guiana Shield and Roraima regions had a high diversity of large trees. By contrast, variables associated with resources tend to govern tree diversity in general. Places such as the province of Imeri and the northern portion of the province of Madeira stand out for their high diversity of species in general. Climatic and topographic stability and functional adaptation mechanisms promote ideal conditions for species diversity. Finally, we mapped general patterns of tree species diversity in the Brazilian Amazon, which differ substantially depending on size class.

β-Estradiol and progesterone enhance biofilm development and persister cell formation in monospecies and microcosms biofilms derived from vulvovaginal candidiasis - Ana Raquel Colares de Andrade; Mônica Dantas Sampaio Rezende; Fernando Victor Monteiro Portela; Livia Maria Galdino Pereira; Bruno Nascimento da Silva; Reginaldo Gonçalves de Lima-Neto; Marcos Fábio Gadelha Rocha; José Júlio Costa Sidrim; Débora Souza Collares Maia Castelo-Branco; Rossana de Aguiar Cordeiro (Biofouling, 2023)

Emergence of livestock-associated Mammaliicoccus sciuri ST71 co-harbouring mecA and mecC genes in Brazil - Guilherme S. de Moura; Eneas de Carvalho; Eduardo M. Ramos Sanchez; Fábio P. Sellera; Michele F.S. Marques; Marcos B. Heinemann; Sarne De Vliegher; Fernando N. Souza; Rinaldo A. Mota (Veterinary Microbiology, 2023)

Performance, carcass, and meat traits of locally adapted Brazilian cattle breeds under feedlot conditions - Maíra de Carvalho Porto Barbosa; Maria Clorinda Soares Fioravanti; Vanessa Peripolli; Andrea Alves do Egito; Raquel Soares Juliano; Alexandre Floriani Ramos; Daniela Cardoso; Kamilla Malta Laudares; Gelson Luis Dias Feijó; Cristiano Sales Prado; Romário Gonçalves Vaz Júnior; Neryssa Alencar de Oliveira; et al. (Tropical Animal Health and Production, 2023)

Nodal Segment Size and Encapsulation Matrix Affect Sugarcane Bud Emergence from Synthetic Seeds - Marco A. Ramírez-Mosqueda; María de la Cruz Díaz-Sánchez; Fernando C. Gómez-Merino; Francisco Hernández-Rosas; Daniel A. Rodríguez-Lagunes; Jericó J. Bello-Bello (Sugar Tech, 2023)

Medium-term fertilization strategies on extensive grain cropping systems under water table influence - Diego Hernán Rotili; Santiago Alvarez Prado; Agustín Barattini; Ignacio Lamattina; Matías Gastón Saks; Marcos Gregorini; Fernando O. Garcia; José Francisco Andrade (Agricultural Systems, 2023)

Mannose-modified hyaluronic acid nanocapsules for the targeting of tumor-associated macrophages - Iago Fernández-Mariño; Clément Anfray; Jose Crecente-Campo; Akihiro Maeda; Aldo Ummarino; Carmen Teijeiro-Valiño; Dario Blanco-Martinez; Francis Mpambani; Laurence Poul; Julie Devalliere; Matthieu Germain; Juan Correa; et al. (Drug Delivery and Translational Research, 2023)
Tumor-associated macrophages (TAMs), a class of immune cells that play a key role in tumor immunosuppression, are recognized as important targets to improve cancer prognosis and treatment. Consequently, the engineering of drug delivery nanocarriers that can reach TAMs has acquired special relevance. This work describes the development and biological evaluation of a panel of hyaluronic acid (HA) nanocapsules (NCs), with different compositions and prepared by different techniques, designed to target macrophages. The results showed that plain HA NCs did not significantly influence the polarization of M0 and M2-like macrophages towards an M1-like pro-inflammatory phenotype; however, the chemical functionalization of HA with mannose (HA-Man) led to a significant increase of NCs uptake by M2 macrophages in vitro and to an improved biodistribution in a MN/MNCA1 fibrosarcoma mouse model with high infiltration of TAMs. These functionalized HA-Man NCs showed a higher accumulation in the tumor compared to non-modified HA NCs. Finally, the pre-administration of the liposomal liver occupying agent Nanoprimer™ further increased the accumulation of the HA-Man NCs in the tumor. This work highlights the promise shown by the HA-Man NCs to target TAMs and thus provides new options for the development of nanomedicine and immunotherapy-based cancer treatments. Graphical abstract

Deleterious Effects of Polypropylene Microplastic Ingestion in Nile Tilapia (Oreochromis niloticus) - Luan Souza do Nascimento; Susana Luporini de Oliveira; Camila Carlino da Costa; Mayumi Fernanda Aracati; Letícia Franchin Rodrigues; Ives Charlie-Silva; Gabriel Conde; Cleber Fernando Menegasso Mansano; Dora Ines Kozusny Andreani; Marco Antonio de Andrade Belo (Bulletin of Environmental Contamination and Toxicology, 2023)

Size structure, length-body mass relationship, and relative condition factor of the crocodile shark, Pseudocarcharias kamoharai, in the Southeastern Pacific Ocean, Ecuador - Marcos D. Calle-Morán; Maria Cristina Oddone; J. Fernando Márquez-Farías; Ramón Bonfil (Regional Studies in Marine Science, 2023)

Imputation accuracy for genomic selection using embryo biopsy samples in Gir - Clara Slade Oliveira; Marcos Vinicius Gualberto Barbosa da Silva; Carolina Capobiango Quintão; Pamela Itajara Otto; Rodrigo Vitorio Alonso; Luiz Fernando Feres; João Claudio do Carmo Panetto; Marco Antonio Machado; Luiz Sergio de Almeida Camargo (Reproductive Biology, 2023)

Economic analysis of bovine brucellosis control in the Rondônia state, Brazil - Bruno Fontana Soares Ferreira; Marcelo Luís Barros; Fernando Ferreira; Adelmar Rocha; Ricardo Augusto Dias; José Henrique Hildebrand Grisi Filho; Marcos Bryan Heinemann; Evelise Oliveira Telles; Guilherme Camargo Alevate; José Soares Ferreira Neto (Tropical Animal Health and Production, 2023)

A proteomic overview of the major venom components from Tityus championi from Panama - Marcos H. Salazar; Magdalena Hernández Ortíz; Sergio Encarnación; Fernando Zamudio; Lourival D. Possani; John Cleghorn; Maricruz Morán; Hildaura Acosta; Gerardo Corzo (Toxicon, 2023)

Urinary levels of 30 metal/metalloids in the Brazilian southeast population: Findings from the Brazilian Longitudinal Study of Adult Health (ELSA-Brasil) - Fernando Barbosa; Paula Picoli Devoz; Marcos Rafael Nogueira Cavalcante; Matheus Gallimberti; Jonas Carneiro Cruz; José Luis Domingo; Eduardo J. Simões; Paulo Lotufo; Simin Liu; Isabela Bensenor (Environmental Research, 2023)

Ocean carbon from space: Current status and priorities for the next decade - Robert J.W. Brewin; Shubha Sathyendranath; Gemma Kulk; Marie-Hélène Rio; Javier A. Concha; Thomas G. Bell; Astrid Bracher; Cédric Fichot; Thomas L. Frölicher; Martí Galí; Dennis Arthur Hansell; Tihomir S. Kostadinov; et al. (Earth-Science Reviews, 2023)

Supplemental red LED light promotes plant productivity, “photomodulates” fruit quality and increases Botrytis cinerea tolerance in strawberry - Giulia Lauria; Ermes Lo Piccolo; Costanza Ceccanti; Lucia Guidi; Rodolfo Bernardi; Fabrizio Araniti; Lorenzo Cotrozzi; Elisa Pellegrini; Michela Moriconi; Tommaso Giordani; Claudio Pugliesi; Cristina Nali; et al. (Postharvest Biology and Technology, 2023)

Drivers of variation in seagrass-associated amphipods across biogeographical areas - Sandra Navarro-Mayoral; Fernando Tuya; Patricia Prado; Candela Marco-Méndez; Victoria Fernandez-Gonzalez; Yolanda Fernández-Torquemada; Fernando Espino; Jose Antonio de la Ossa; David Mateu Vilella; Margarida Machado; Begoña Martínez-Crego (Marine Environmental Research, 2023)

Biocrusts Modulate Climate Change Effects on Soil Organic Carbon Pools: Insights From a 9-Year Experiment - Paloma Díaz-Martínez; Marco Panettieri; Pablo García-Palacios; Eduardo Moreno; César Plaza; Fernando T. Maestre (Ecosystems, 2023)
Accumulating evidence suggests that warming associated with climate change is decreasing the total amount of soil organic carbon (SOC) in drylands, although scientific research has not given enough emphasis to particulate (POC) and mineral-associated organic carbon (MAOC) pools. Biocrusts are a major biotic feature of drylands and have large impacts on the C cycle, yet it is largely unknown whether they modulate the responses of POC and MAOC to climate change. Here, we assessed the effects of simulated climate change (control, reduced rainfall (RE), warming (WA), and RE + WA) and initial biocrust cover (low (< 20%) versus high (> 50%)) on the mineral protection of soil C and soil organic matter quality in a dryland ecosystem in central Spain for 9 years. At low initial biocrust cover levels, both WA and RE + WA increased SOC, especially POC but also MAOC, and promoted a higher contribution of carbohydrates, relative to aromatic compounds, to the POC fraction. These results suggest that the accumulation of soil C under warming treatments may be transitory in soils with low initial biocrust cover. In soils with high initial biocrust cover, climate change treatments did not affect SOC, neither POC nor MAOC fraction. Overall, our results indicate that biocrust communities modulate the negative effect of climate change on SOC, because no losses of soil C were observed with the climate manipulations under biocrusts. Future work should focus on determining the long-term persistence of the observed buffering effect by biocrust-forming lichens, as they are known to be negatively affected by warming.

Spatial non-stationarity in the distribution of fish species richness of tropical streams - Thiago Bernardi Vieira; Jorge Iván Sánchez-Botero; Danielle Sequeira Garcez; Sergio Maia Queiroz Lima; Carla Simone Pavanelli; Lilian Casatti; Welber Senteio Smith; Evanilde Benedito; Rosana Mazzoni; Paulo Santos Pompeu; Carlos Sérgio Agostinho; Luciano Fogaça de Assis Montag; et al. (Community Ecology, 2023)

Effects of Citrus limon extract on growth performance and immunity in striped catfish (Pangasius hypophthalmus) - Juliano dos Santos Macedo; Carlos Eduardo Copatti; Emmanoel Vilaça Costa; Felipe Moura Araújo da Silva; Lívia Macedo Dutra; Victória Laysna dos Anjos Santos; Jackson Roberto Guedes da Silva Almeida; Marcos Tavares-Dias; José Fernando Bibiano Melo (Aquaculture International, 2023)

New constraints on the seismotectonics and crustal structure of the Eastern Trans-Mexican Volcanic Belt based on local seismicity, focal mechanisms and a preliminary state of stress evaluation - Francisco Córdoba-Montiel; Katrin Sieron; Arturo Iglesias; Marco Caló; Oscar Alberto Castro Artola; Miguel Ángel Méndez Alarcón; Luis Fernando Ricardez Puente (Journal of South American Earth Sciences, 2023)

Malassezia spp. and Candida spp. from patients with psoriasis exhibit reduced susceptibility to antifungals - Rossana de Aguiar Cordeiro; Ane Teles Reis; Xinaida Taligare Vasconcelos Lima; Ana Raquel Colares de Andrade; Ana Luiza Ribeiro Aguiar; Fernando Victor Monteiro Portela; Lívia Maria Galdino Pereira; Santiago Gonçalves Bezerra Moura; Bruno Nascimento da Silva; Reginaldo Gonçalves de Lima-Neto; Débora Castelo-Branco Souza Collare Maia; Marcos Fábio Gadelha Rocha; et al. (Brazilian Journal of Microbiology, 2023)

Atlantic flower–invertebrate interactions: A data set of occurrence and frequency of floral visits - Danilo Boscolo; Bárbara Nobrega Rodrigues; Patrícia Alves Ferreira; Luciano Elsinor Lopes; Vinicius Rodrigues Tonetti; Isabela Cristhina Reis dos Santos; Juliana Akemi Hiruma‐Lima; Laura Nery; Karoline Baptista de Lima; Jéssica Perozi; André Victor Lucci Freitas; Blandina Felipe Viana; et al. (Ecology, 2023)
Encounters between flowers and invertebrates are key events for the functioning of tropical forests. Assessing the structure of networks composed of the interactions between those partners leads to a better understanding of ecosystem functioning and the effects of environmental factors on ecological processes. Gathering such data is, however, costly and time‐consuming, especially in the highly diverse tropics. We aimed to provide a comprehensive repository of available flower–invertebrate interaction information for the Atlantic Forest, a South American tropical forest domain. Data were obtained from published works and “gray literature,” such as theses and dissertations, as well as self‐reports by co‐authors. The data set has ~18,000 interaction records forming 482 networks, each containing between one and 1061 interaction links. Each network was sampled for about 200 h or less, with few exceptions. A total of 641 plant genera within 136 different families and 39 orders were reported, with the most abundant and rich families being Asteraceae, Fabaceae, and Rubiaceae. Invertebrates interacting with these plants were all arthropods from 10 orders, 129 families, and 581 genera, comprising 2419 morphotypes (including 988 named species). Hymenoptera was the most abundant and diverse order, with at least six times more records than the second‐ranked order (Lepidoptera). The complete data set shows Hymenoptera interacting with all plant orders and also shows Diptera, Lepidoptera, Coleoptera, and Hemiptera to be important nodes. Among plants, Asterales and Fabales had the highest number of interactions. The best sampled environment was forest (~8000 records), followed by pastures and crops. Savanna, grasslands, and urban environments (among others) were also reported, indicating a wide range of approaches dedicated to collecting flower–invertebrate interaction data in the Atlantic Forest domain. Nevertheless, most reported data were from forest understory or lower strata, indicating a knowledge gap about flower–invertebrate interactions at the canopy. Also, access to remote regions remains a limitation, generating sampling bias across the geographical range of the Atlantic Forest. Future studies in these continuous and hard‐to‐access forested areas will yield important new information regarding the interactions between flowers and invertebrates in the Atlantic Forest. There are no copyright restrictions on the data set. Please cite this data paper if the data are used in publications and teaching events.

Differential expression of the androgen receptor gene is correlated with CAG polymorphic repeats in patients with prostate cancer - Martín Irigoyen Arredondo; José Romero Quintana; Eliakym Arámbula Meraz; Fernando Bergez Hernández; Fred Luque Ortega; Alejandra Martínez Camberos; Marco Álvarez Arrazola; Enrique Romo Martínez; Dora Cedano Prieto; José Contreras Gutiérrez; Noemi García Magallanes (Journal of Genetics, 2023)

Promethazine inhibits efflux, enhances antifungal susceptibility and disrupts biofilm structure and functioning in Trichosporon - Ana Luiza Ribeiro Aguiar; Bruno Nascimento da Silva; Nicole de Mello Fiallos; Lívia Maria Galdino Pereira; Maria Laína Silva; Pedro Freitas Santos Manzi de Souza; Fernando Victor Monteiro Portela; José Júlio Costa Sidrim; Marcos Fábio Gadelha Rocha; Débora Souza Collares Maia Castelo-Branco; Rossana de Aguiar Cordeiro (Biofouling, 2023)

Polysaccharides from macro algae: Anti-inflammatory actions against systemic inflammatory process and in the gastrointestinal tract - Antônio Kleiton de Sousa; Anna Sofia Miranda Loiola Araujo; Tino Marcos Lino da Silva; Fernando Mesquita de Sousa de Lima; Jayro dos Santos Ferreira; Tarcisio Vieira de Brito; André Luiz dos Reis Barbosa (Journal of Applied Phycology, 2023)

Episodic memory dysfunction and hypersynchrony in brain functional networks in cognitively intact subjects and MCI: a study of 379 individuals - Brenda Chino; Pablo Cuesta; Javier Pacios; Jaisalmer de Frutos-Lucas; Lucía Torres-Simón; Sandra Doval; Alberto Marcos; Ricardo Bruña; Fernando Maestú (GeroScience, 2023)
Delayed recall (DR) impairment is one of the most significant predictive factors in defining the progression to Alzheimer’s disease (AD). Changes in brain functional connectivity (FC) could accompany this decline in the DR performance even in a resting state condition from the preclinical stages to the diagnosis of AD itself, so the characterization of the relationship between the two phenomena has attracted increasing interest. Another aspect to contemplate is the potential moderator role of the APOE genotype in this association, considering the evidence about their implication for the disease. 379 subjects (118 mild cognitive impairment (MCI) and 261 cognitively intact (CI) individuals) underwent an extensive evaluation, including MEG recording. Applying cluster-based permutation test, we identified a cluster of differences in FC and studied which connections drove such an effect in DR. The moderation effect of APOE genotype between FC results and delayed recall was evaluated too. Higher FC in beta band in the right occipital region is associated with lower DR scores in both groups. A significant anteroposterior link emerged in the seed-based analysis with higher values in MCI. Moreover, APOE genotype appeared as a moderator between beta FC and DR performance only in the CI group. An increased beta FC in the anteroposterior brain region appears to be associated with lower memory performance in MCI. This finding could help discriminate the pattern of the progression of healthy aging to MCI and the relation between resting state and memory performance.

Disentangling the role of soil bacterial diversity in phosphorus transformation in the maize rhizosphere - Yasmin Florentino Rodrigues; Fernando Dini Andreote; Antonio Marcos Miranda Silva; Armando Cavalcante Franco Dias; Rodrigo Gouvea Taketani; Simone Raposo Cotta (Applied Soil Ecology, 2023)

Nitrofurantoin-induced liver injury: long-term follow-up in two prospective DILI registries - Fernando Bessone; Antonella Ferrari; Nelia Hernandez; Manuel Mendizabal; Ezequiel Ridruejo; Alina Zerega; Federico Tanno; Maria Virginia Reggiardo; Julio Vorobioff; Hugo Tanno; Marco Arrese; Vinicius Nunes; et al. (Archives of Toxicology, 2023)
Nitrofurantoin is a synthetic antibiotic that is recommended as first-choice treatment for uncomplicated urinary tract infections. The prescription of this drug has increased dramatically, especially in Latin American countries. We described the demographics, clinical characteristics, biochemical features, and outcome of nitrofurantoin-induced liver injury. We analyzed 23 cases from the Latin American DILI Network (LATINDILI) and the Spanish DILI Registry. Causality was assessed with the RUCAM and RECAM scale. Of the 23 DILI cases included in our series, 96% patients were women, and the mean age of the whole cohort was 61 years. The median time of drug exposure was 175 days (interquartile range [IQR] 96–760), with 11 patients who were prescribed nitrofurantoin for more than six months. Hepatocellular damage was the most frequent pattern of liver injury (83%), and nearly half of the patients had an asymptomatic presentation (52%). Neither death nor liver transplantation was documented in this series. Overall, 65% of the patients ( n = 15) presented with positive autoantibody titres. The median time to resolution was 81 days (IQR 57–141), and 15 patients (83%) recovered within six months. Five patients (22%) developed nitrofurantoin-induced autoimmune-like hepatitis (NI-AILH), of whom two were characterized by a persistent increase in transaminases that required immunosuppressive treatment to achieve normalization of liver enzymes. Clinicians who prescribe nitrofurantoin should be aware that patients who had taken nitrofurantoin for a long term may be at risk of developing nitrofurantoin-induced autoimmune-like hepatitis.

Genes and single nucleotide polymorphisms in the pathway of saliva and dental caries: a systematic review and meta-analysis - Luiz Alexandre Chisini; Rodrigo Varella de Carvalho; Francine dos Santos Costa; Luana Carla Salvi; Flávio Fernando Demarco; Marcos Britto Correa (Biofouling, 2023)

Potentially harmful effects of seed treatment and pre-inoculation on soybean biological nitrogen fixation and yield - Felipe Fadel Sartori; Thaise Dieminger Engroff; Thaís H. Godoy Sanches; Julia M. Soave; Mila Victório Pessotto; Guilherme Felisberto; Valter E. Hilgemberg Jr.; André Fróes de Borja Reis; Mariangela Hungria; Marco A. Nogueira; David de Souza Jaccoud-Filho; Fernando Dini Andreote; et al. (European Journal of Agronomy, 2023)

Agriculture intensity and landscape configuration influence the spatial use of wildcats across Europe - Héctor Ruiz-Villar; Matteo Luca Bastianelli; Marco Heurich; Stefano Anile; Francisco Díaz-Ruiz; Pablo Ferreras; Malte Götz; Mathias Herrmann; Saskia Jerosch; Fernando Jubete; José María López-Martín; Pedro Monterroso; et al. (Biological Conservation, 2023)

Overexpression of the GmEXPA1 gene reduces plant susceptibility to Meloidogyne incognita - Marcos Fernando Basso; Isabela Tristan Lourenço-Tessutti; Clidia Eduarda Moreira-Pinto; Reneida Aparecida Godinho Mendes; Debora Gonçalves Pereira; Adriana Grandis; Leonardo Lima Pepino Macedo; Amanda Ferreira Macedo; Ana Cristina Meneses Mendes Gomes; Fabrício Barbosa Monteiro Arraes; Roberto Coiti Togawa; Marcos Mota do Carmo Costa; et al. (Plant Cell Reports, 2023)

Physicochemical and bioinformatic characterization of Oreochromis niloticus vitellogenin as an endocrine disruption biomarker - Tugstênio L. Souza; Tobias P. de Morais; Francisco Filipak Neto; Iracema Opuskevitch; Fernando C. A. S. Ferreira; Marco Antônio Ferreira Randi; Ciro Alberto de Oliveira Ribeiro; Claudemir de Souza; Maritana Mela Prodocimo (Ecotoxicology, 2023)

How can diverse national food and land-use priorities be reconciled with global sustainability targets? Lessons from the FABLE initiative - Aline Mosnier; Guido Schmidt-Traub; Michael Obersteiner; Sarah Jones; Valeria Javalera-Rincon; Fabrice DeClerck; Marcus Thomson; Frank Sperling; Paula Harrison; Katya Pérez-Guzmán; Gordon Carlos McCord; Javier Navarro-Garcia; et al. (Sustainability Science, 2023)
There is an urgent need for countries to transition their national food and land-use systems toward food and nutritional security, climate stability, and environmental integrity. How can countries satisfy their demands while jointly delivering the required transformative change to achieve global sustainability targets? Here, we present a collaborative approach developed with the FABLE—Food, Agriculture, Biodiversity, Land, and Energy—Consortium to reconcile both global and national elements for developing national food and land-use system pathways. This approach includes three key features: (1) global targets, (2) country-driven multi-objective pathways, and (3) multiple iterations of pathway refinement informed by both national and international impacts. This approach strengthens policy coherence and highlights where greater national and international ambition is needed to achieve global goals (e.g., the SDGs). We discuss how this could be used to support future climate and biodiversity negotiations and what further developments would be needed.

A novel picorna-like virus identified in the cotton boll weevil Anthonomus grandis (Coleoptera: Curculionidae) - Leonardo Assis da Silva; Marcos Fernando Basso; Bergmann Morais Ribeiro (Archives of Virology, 2023)

Bacterial pathogens’ screening in Brazilian chigger mites (Trombidiformes: Trombiculidae), with the first report of 'Candidatus Rickettsia colombianensi'-like in avian-associated chiggers - Ricardo Bassini-Silva; Fernando de Castro Jacinavicius; Sebastián Muñoz-Leal; Ralph Maturano; Julia Carvalho Takatsu; Graziela Virginia Tolesano-Pascoli; Renata D. Alquezar; Camile Lugarini; Ariane Ferreira; Luciano Moreira-Lima; Cal Welbourn; Ronald Ochoa; et al. (Archives of Microbiology, 2023)

Geographic patterns of tree dispersal modes in Amazonia and their ecological correlates - Diego F. Correa; Pablo R. Stevenson; Maria Natalia Umaña; Luiz de Souza Coelho; Diógenes de Andrade Lima Filho; Rafael P. Salomão; Iêda Leão do Amaral; Florian Wittmann; Francisca Dionízia de Almeida Matos; Carolina V. Castilho; Oliver L. Phillips; Juan Ernesto Guevara; et al. (Global Ecology and Biogeography, 2023)
Aim To investigate the geographic patterns and ecological correlates in the geographic distribution of the most common tree dispersal modes in Amazonia (endozoochory, synzoochory, anemochory and hydrochory). We examined if the proportional abundance of these dispersal modes could be explained by the availability of dispersal agents (disperser‐availability hypothesis) and/or the availability of resources for constructing zoochorous fruits (resource‐availability hypothesis). Time period Tree‐inventory plots established between 1934 and 2019. Major taxa studied Trees with a diameter at breast height (DBH) ≥ 9.55 cm. Location Amazonia, here defined as the lowland rain forests of the Amazon River basin and the Guiana Shield. Methods We assigned dispersal modes to a total of 5433 species and morphospecies within 1877 tree‐inventory plots across terra‐firme, seasonally flooded, and permanently flooded forests. We investigated geographic patterns in the proportional abundance of dispersal modes. We performed an abundance‐weighted mean pairwise distance (MPD) test and fit generalized linear models (GLMs) to explain the geographic distribution of dispersal modes. Results Anemochory was significantly, positively associated with mean annual wind speed, and hydrochory was significantly higher in flooded forests. Dispersal modes did not consistently show significant associations with the availability of resources for constructing zoochorous fruits. A lower dissimilarity in dispersal modes, resulting from a higher dominance of endozoochory, occurred in terra‐firme forests (excluding podzols) compared to flooded forests. Main conclusions The disperser‐availability hypothesis was well supported for abiotic dispersal modes (anemochory and hydrochory). The availability of resources for constructing zoochorous fruits seems an unlikely explanation for the distribution of dispersal modes in Amazonia. The association between frugivores and the proportional abundance of zoochory requires further research, as tree recruitment not only depends on dispersal vectors but also on conditions that favour or limit seedling recruitment across forest types.

Spiral polyethylene tube solar collectors performance analyzed by a new partially linear regression model - Julio C. S. Vasconcelos; Denize P. dos Santos; Fernando J. B. Brandão; Edwin M. M. Ortega; Marco A. M. Biaggioni; Gauss M. Cordeiro (Environment, Development and Sustainability, 2022)

Apparent prevalence and risk factors for bovine tuberculosis in the state of Paraná, Brazil: an assessment after 18 years since the beginning of the Brazilian program - Diego Leonardo Rodrigues; Elenice Aparecida Amorim; Fernando Ferreira; Marcos Amaku; Oswaldo Santos Baquero; José Henrique de Hildebrand e Grisi Filho; Ricardo Augusto Dias; Marcos Bryan Heinemann; Evelise Oliveira Telles; Vitor Salvador Picão Gonçalves; Christopher Compton; José Soares Ferreira Neto (Tropical Animal Health and Production, 2022)
Bovine tuberculosis (bTB) impacts considerably animal production and one health worldwide. To describe the prevalence, risk factors, and spatial pattern of the disease in the state of Paraná, Brazil, a cross-sectional study was conducted from September 2018 to February 2019. The area was divided into seven regions. Within each region, farms were randomly selected, and a predetermined number of cows was selected and tested by a comparative cervical tuberculin test. 17,210 animals were tested across 1757 farms. Herd prevalence of bTB-infected herds in Paraná was 2.5% [1.87–3.00%]. It has varied from 0.8 to 3.98% among seven regions, with clustering being detected in the west, central, and northeast areas. Animal prevalence was 0.35% [0.21–0.59%] and has varied from 0.08 to 0.6% among the pre-set regions. No major shifts in the prevalence of bTB were detected since 2007. Large-sized herds, dairy production, and feeding with whey were detected to be correlated with the presence of bTB. Exclusively among dairy herds, veterinary assistance from cooperatives, possession of self-owned equipment to cool milk, and feeding with whey were correlated with the disease. Considering these results, it is recommended that the state of Paraná seek to implement a surveillance system for the detection of bTB-infected herds transforming them into free ones, if possible, incorporating elements of risk-based surveillance. Health education is also recommended to inform farmers about the risks of introducing animals without testing and of feeding raw whey to calves.

P2Y12 receptor antagonism inhibits proliferation, migration and leads to autophagy of glioblastoma cells - Pedro Vargas; Thamiris Becker Scheffel; Fernando Mendonça Diz; Liliana Rockenbach; Nathália Grave; Angélica Regina Cappellari; Luiza Wilges Kist; Maurício Reis Bogo; Marcos Paulo Thomé; Gabriel Fernandes Leal; Amanda de Fraga Dias; Fabrício Figueiró; et al. (Purinergic Signalling, 2022)

Phylogenomic characterization and pangenomic insights into the surfactin-producing bacteria Bacillus subtilis strain RI4914 - Julie Kennya de Lima Ferreira; Alessandro de Mello Varani; Marcos Rogério Tótola; Michelle Fernandes Almeida; Dirceu de Sousa Melo; Cristina Ferreira Silva e Batista; Antonio Chalfun-Junior; Kellen Kauanne Pimenta de Oliveira; Luiz Fernando Wurdig Roesch; Victor Satler Pylro (Brazilian Journal of Microbiology, 2022)

First record of Odontaster penicillatus populations (Philippi, 1870) (Echinodermata: Asteroidea) in the Atacama and Antofagasta regions, Chile (Southeast Pacific) - Leonardo Campos; Fernando Berrios; Brenda B. Hermosillo-Núñez; Marco Ortiz (Acta Oceanologica Sinica, 2022)

A global analysis of viviparity in squamates highlights its prevalence in cold climates - Anna Zimin; Sean V. Zimin; Richard Shine; Luciano Avila; Aaron Bauer; Monika Böhm; Rafe Brown; Goni Barki; Gabriel Henrique de Oliveira Caetano; Fernando Castro Herrera; David G. Chapple; Laurent Chirio; et al. (Global Ecology and Biogeography, 2022)
Aim Viviparity has evolved more times in squamates than in any other vertebrate group; therefore, squamates offer an excellent model system in which to study the patterns, drivers and implications of reproductive mode evolution. Based on current species distributions, we examined three selective forces hypothesized to drive the evolution of squamate viviparity (cold climate, variable climate and hypoxic conditions) and tested whether viviparity is associated with larger body size. Location Global. Time period Present day. Taxon Squamata. Methods We compiled a dataset of 9061 squamate species, including their distributions, elevation, climate, body mass and reproductive modes. We applied species‐level and assemblage‐level approaches for predicting reproductive mode, both globally and within biogeographical realms. We tested the relationships of temperature, interannual and intra‐annual climatic variation, elevation (as a proxy for hypoxic conditions) and body mass with reproductive mode, using path analyses to account for correlations among the environmental predictors. Results Viviparity was strongly associated with cold climates at both species and assemblage levels, despite the prevalence of viviparity in some warm climates. Viviparity was not clearly correlated with climatic variability or elevation. The probability of being viviparous exhibited a weak positive correlation with body size. Conclusions Although phylogenetic history is important, potentially explaining the occurrence of viviparous species in regions that are warm at present, current global squamate distribution is characterized by a higher relative abundance of viviparity in cold environments, supporting the prediction of the “cold‐climate” hypothesis. The roles of climatic variation and hypoxia are less important and not straightforward. Elevation probably exerts various selective pressures and influences the prevalence of viviparity primarily through its effect on temperature rather than on oxygen concentration.

Physiological effects of microcurrent and its application for maximising acute responses and chronic adaptations to exercise - Stefan Kolimechkov; Marcos Seijo; Ian Swaine; Jack Thirkell; Juan C. Colado; Fernando Naclerio (European Journal of Applied Physiology, 2022)
Microcurrent is a non-invasive and safe electrotherapy applied through a series of sub-sensory electrical currents (less than 1 mA), which are of a similar magnitude to the currents generated endogenously by the human body. This review focuses on examining the physiological mechanisms mediating the effects of microcurrent when combined with different exercise modalities (e.g. endurance and strength) in healthy physically active individuals. The reviewed literature suggests the following candidate mechanisms could be involved in enhancing the effects of exercise when combined with microcurrent: (i) increased adenosine triphosphate resynthesis, (ii) maintenance of intercellular calcium homeostasis that in turn optimises exercise-induced structural and morphological adaptations, (iii) eliciting a hormone-like effect, which increases catecholamine secretion that in turn enhances exercise-induced lipolysis and (iv) enhanced muscle protein synthesis. In healthy individuals, despite a lack of standardisation on how microcurrent is combined with exercise (e.g. whether the microcurrent is pulsed or continuous), there is evidence concerning its effects in promoting body fat reduction, skeletal muscle remodelling and growth as well as attenuating delayed-onset muscle soreness. The greatest hindrance to understanding the combined effects of microcurrent and exercise is the variability of the implemented protocols, which adds further challenges to identifying the mechanisms, optimal patterns of current(s) and methodology of application. Future studies should standardise microcurrent protocols by accurately describing the used current [e.g. intensity (μA), frequency (Hz), application time (minutes) and treatment duration (e.g. weeks)] for specific exercise outcomes, e.g. strength and power, endurance, and gaining muscle mass or reducing body fat.

Supraparticles as slow-release fertiliser in seedling potential growth of Eucalyptus urograndis and greenhouse gas flux impacts - Gabriel Goetten de Lima; Mailson Matos; Francielen Paola de Sá; Leandro Nozomi Mashiba; Washington L. E. Magalhães; Marcos Fernando Glück Rachwal; Josileia Acordi Zanatta (Environmental Science and Pollution Research, 2022)

The Dorsolateral Prefrontal Cortex Presents Structural Variations Associated with Empathy and Emotion Regulation in Psychotherapists - Marcos E. Domínguez-Arriola; Víctor E. Olalde-Mathieu; Eduardo A. Garza-Villarreal; Fernando A. Barrios (Brain Topography, 2022)

Overexpression of a soybean Globin (GmGlb1-1) gene reduces plant susceptibility to Meloidogyne incognita - Marcos Fernando Basso; Isabela Tristan Lourenço-Tessutti; Clidia Eduarda Moreira-Pinto; Reneida Aparecida Godinho Mendes; Bruno Paes-de-Melo; Maysa Rosa das Neves; Amanda Ferreira Macedo; Viviane Figueiredo; Adriana Grandis; Leonardo Lima Pepino Macedo; Fabrício Barbosa Monteiro Arraes; Marcos Mota do Carmo Costa; et al. (Planta, 2022)

Functional characterization of the pUceS8.3 promoter and its potential use for ectopic gene overexpression - Rodrigo Rocha Fragoso; Fabricio Barbosa Monteiro Arraes; Isabela Tristan Lourenço-Tessutti; Vívian Jesus Miranda; Marcos Fernando Basso; André Vinicius Júlio Ferreira; Antônio Américo Barbosa Viana; Camila Barrozo Jesus Lins; Philippe Castro Lins; Stéfanie Menezes Moura; João Aguiar Nogueira Batista; Maria Cristina Mattar Silva; et al. (Planta, 2022)

The record and threats of the invasion of palometa Serrasalmus maculatus (Characiformes: Serrasalmidae) in the Patos lagoon drainage, southern Brazil - Vinicius Araújo Bertaco; Fernando G. Becker; Marco A. Azevedo; Juliano Ferrer; Everton R. Behr; Tiago R. de Moraes; Nelson J. R. Fagundes; Luiz R. Malabarba (Journal of Fish Biology, 2022)
We report the occurrence of an invasive alien species, palometa Serrasalmus maculatus , in the Patos Lagoon drainage. Primary occurrence data were based on three specimens captured and preserved as vouchers in scientific collections. Additionally, we searched for secondary records from unpublished scientific sources, public agencies reports and media news to find additional reports. We discussed the possible pathways of invasion, suggesting as the vector of introduction transpositions from the Uruguay River basin. Ecological implications for ichthyofauna, environmental impacts and risk of other events of invasion in the adjoining basins are discussed.

Heterologous extracellular DNA facilitates the development of Trichosporon asahii and T. inkin biofilms and enhances their tolerance to antifungals - Lívia Maria Galdino Pereira; Ana Raquel Colares de Andrade; Fernando Victor Monteiro Portela; Ana Luiza Ribeiro Aguiar; Bruno Nascimento da Silva; Santiago Gonçalves Bezerra Moura; Mariana Lara Mendes Pergentino; Marcos Fábio Gadelha Rocha; José Júlio da Costa Sidrim; Débora de Souza Collares Maia Castelo Branco; Rossana de Aguiar Cordeiro (Biofouling, 2022)

Evaluating loggerhead sea turtle (Caretta caretta) bycatch in the small-scale fisheries of Cabo Verde - Samir Martins; Manjula Tiwari; Fernando Rocha; Edson Rodrigues; Ravidson Monteiro; Sónia Araújo; Elena Abella; Nuno de Santos Loureiro; Leo J. Clarke; Adolfo Marco (Reviews in Fish Biology and Fisheries, 2022)

Chloride Ingress Resistance, Microstructure and Mechanical Properties of Lightweight Mortars with Natural Cork and Expanded Clay Prepared Using Sustainable Blended Cements - José Marcos Ortega; Fernando G. Branco; Luís Pereira; Luís Marques (Journal of Marine Science and Engineering, 2022)
The use of lightweight aggregates in construction materials is a good solution for increasing the contribution to sustainability of civil engineering works, such as maritime ones. In this regard, the possibility of using cork granulates and expanded clay is a current research topic. The combination of eco-friendly cements with lightweight aggregates could provide solutions for developing new building materials. In this work, it has been studied mortars prepared with sustainable cements and the lightweight aggregates of natural cork and expanded clay. These cements incorporated slag, limestone and fly ash. Reference mortars with only sand as aggregate were also made. The total porosity and pore size distributions were obtained. The non-steady-state chloride migration coefficient and compressive and flexural strengths were also determined. The tests were performed at 28 days and 1 year. The differences in the total porosity between the natural cork and expanded clay series were not high, depending on the binder. Natural cork mortars showed similar or slightly higher migration coefficients than the reference and expanded clay mortars at 1 year. This adequate chloride resistance and the low mechanical strengths observed for the natural cork mortars recommend the possible use of this new aggregate in non-structural cement-based materials for civil engineering works exposed to maritime environments.

MicroRNAs expression profiles in early responses to different levels of water deficit in Setaria viridis - Karoline Estefani Duarte; Marcos Fernando Basso; Nelson Geraldo de Oliveira; José Cleydson Ferreira da Silva; Bruno de Oliveira Garcia; Bárbara Andrade Dias Brito Cunha; Thiago Bergamo Cardoso; Alexandre Lima Nepomuceno; Adilson Kenji Kobayashi; Thaís Ribeiro Santiago; Wagner Rodrigo de Souza; Hugo Bruno Correa Molinari (Physiology and Molecular Biology of Plants, 2022)

Short-term effects of agroforestry systems on soil health in Southeastern Brazil - Priscila Silva Matos; Maurício Roberto Cherubin; Júnior Melo Damian; Fernando Igne Rocha; Marcos Gervasio Pereira; Everaldo Zonta (Agroforestry Systems, 2022)

Water table depth modulates productivity and biomass across Amazonian forests - Thaiane R. Sousa; Juliana Schietti; Igor O. Ribeiro; Thaise Emílio; Rafael Herrera Fernández; Hans ter Steege; Carolina V. Castilho; Adriane Esquivel‐Muelbert; Timothy Baker; Aline Pontes‐Lopes; Camila V. J. Silva; Juliana M. Silveira; et al. (Global Ecology and Biogeography, 2022)
Aim Water availability is the major driver of tropical forest structure and dynamics. Most research has focused on the impacts of climatic water availability, whereas remarkably little is known about the influence of water table depth and excess soil water on forest processes. Nevertheless, given that plants take up water from the soil, the impacts of climatic water supply on plants are likely to be modulated by soil water conditions. Location Lowland Amazonian forests. Time period 1971–2019. Methods We used 344 long‐term inventory plots distributed across Amazonia to analyse the effects of long‐term climatic and edaphic water supply on forest functioning. We modelled forest structure and dynamics as a function of climatic, soil‐water and edaphic properties. Results Water supplied by both precipitation and groundwater affects forest structure and dynamics, but in different ways. Forests with a shallow water table (depth Main conclusions We show that the two extremes of water availability (excess and deficit) both reduce productivity in Amazon upland ( terra‐firme ) forests. Biomass and productivity across Amazonia respond not simply to regional climate, but rather to its interaction with water table conditions, exhibiting high local differentiation. Our study disentangles the relative contribution of those factors, helping to improve understanding of the functioning of tropical ecosystems and how they are likely to respond to climate change.

Baseline values and environmental assessment for metal(loid)s in soils under a tropical rainy climate in a Colombian region - Juan Manuel Trujillo-González; Marco Aurelio Torres-Mora; Marlon Serrano-Gomez; Edgar Fernando Castillo-Monroy; Raimundo Jiménez Ballesta (Environmental Monitoring and Assessment, 2022)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Correction to: Early dysfunction of functional connectivity in healthy elderly with subjective memory complaints - Ricardo Bajo; Nazareth P. Castellanos; Maria Eugenia López; José María Ruiz-Sanchez de Leon; Pedro Montejo; Mercedes Montenegro; Marcos Llanero; Pedro Gil; Raquel Yubero; Evgenia Baykova; Nuria Paul; Sara Aurtenetxe; et al. (GeroScience, 2022)

Which birds are Brazilians seeing on urban and non-urban feeders? An analysis based on a collective online birding - Eduardo Roberto Alexandrino; Thaís Abreu Camboim; Flávia Guimarães Chaves; Alex Augusto Abreu Bovo; Marco Aurélio Galvão da Silva; Daniela Alves Maia da Silva; Margi Moss; Tatiana Pongiluppi Souza; Clarissa de Oliveira Santos; Caio Bezerra de Mattos Brito; Maristela Camolesi Alcantara; Karlla V. C. Barbosa; et al. (Ornithology Research, 2022)

Industry 4.0 real-world testing of dynamic organizational life cycle assessment (O-LCA) of a ceramic tile manufacturer - Marco Cucchi; Lucrezia Volpi; Anna Maria Ferrari; Fernando E. García-Muiña; Davide Settembre-Blundo (Environmental Science and Pollution Research, 2022)
In manufacturing, Industry 4.0 operating models enable greener technologies. Thanks to digital technologies, environmental sustainability and organizational competitiveness are mutually reinforcing. The challenge for manufacturing organizations is to understand and quantify the magnitude of this synergistic action, and the holistic perspective of life cycle assessment tools may be a solution to the problem. Organizational Life Cycle Assessment (O-LCA) unlike Product Life Cycle Assessment (LCA) is still an under-researched methodology with few applications in manufacturing contexts. This paper aims to fill this gap by implementing and validating O-LCA in the case of an Italian ceramic tile manufacturer. Following the O-LCA guidelines and exploiting Industry 4.0 technologies to perform the inventory analysis, the environmental assessment was conducted in three different plants, comparing the sum of the partial impact results with the overall results scaled to the whole organization. The experimental results demonstrated the validity of the organizational approach as an appropriate methodological option to obtain relevant information on environmental performance that, being based on empirical evidence, better support decision-making processes. Furthermore, the study provides empirical evidence of how Industry 4.0 is an enabler not only for the adoption of greener technologies, but especially for facilitating the organizational environmental impact assessment that is the necessary condition in order to set up and maintain greener manufacturing contexts.

Multilocus phylogeography of the endemic and endangered angular angelshark (Squatina guggenheim) in the Southwest Atlantic Ocean - Ingrid Vasconcellos Bunholi; Bruno Lopes da Silva Ferrette; Rodrigo Rodrigues Domingues; Matheus Marcos Rotundo; Juan Martín Cuevas; Mirta García; Sebastián Gómez; Renato Hajenius Aché de Freitas; Claudio Oliveira; Fausto Foresti; Fernando Fernandes Mendonça (Hydrobiologia, 2022)

Phosphorus in soils and fluvial sediments from a Cerrado biome watershed under agricultural expansion - Fernando Braga Rimá; Yuri Jacques Agra Bezerra da Silva; Marcos Paulo Rodrigues Teixeira; Angelo Jamil Maia; Kamylla Gonçalves Oliveira Assis; Rayanna Jacques Agra Bezerra da Silva; Valdomiro Severino de Souza Júnior; Ygor Jacques Agra Bezerra da Silva; José Wellington Batista Lopes; Ronny Sobreira Barbosa; Vijay P. Singh (Environmental Monitoring and Assessment, 2022)

Mapping Potential Toxic Elements in Agricultural and Natural Soils of the Piedemonte Llanero in Colombia - Juan Manuel Trujillo-González; Marco Aurelio Torres-Mora; Marlon Serrano-Gómez; Edgar Fernando Castillo-Monroy; Raimundo Jiménez Ballesta; Jesús Rodrigo-Comino (Water, Air, & Soil Pollution, 2022)

Phenotypic differences for growth, feed efficiency, and age of first calving of Brazilian zebu females - André Campêlo Araujo; Paulo Luiz Souza Carneiro; Johnny Iglesias Mendes Araújo; Bárbara Machado Campos; Marcos Paulo Gonçalves de Rezende; Raimundo Martins Filho; Luiz Fernando Brito; Carlos Henrique Mendes Malhado (Tropical Animal Health and Production, 2022)

Association Mapping for Sugarcane Quality Traits at Three Harvest Times - Alisson Esdras Coutinho; Marcel Fernando da Silva; Dilermando Perecin; Roberto Carvalheiro; Mauro Alexandre Xavier; Marcos Guimarães de Andrade Landell; Luciana Rossini Pinto (Sugar Tech, 2022)

Feather stable isotopes (δ2Hf and δ13Cf) identify the Sub-Saharan wintering grounds of turtle doves from Europe - Melanie Marx; Yvonne R. Schumm; Kevin J. Kardynal; Keith A. Hobson; Gregorio Rocha; Pavel Zehtindjiev; Dimitris Bakaloudis; Benjamin Metzger; Jacopo G. Cecere; Fernando Spina; Marco Cianchetti-Benedetti; Sylke Frahnert; et al. (European Journal of Wildlife Research, 2022)
Conservation of migratory birds requires knowledge of breeding and nonbreeding ranges and the connections between them. European turtle doves ( Streptopelia turtur ) are Palearctic-African long-distance migrants with wintering areas in the Sub-Saharan belt that are classed as vulnerable due to strong population declines. However, detailed non-breeding locations of individuals from different migratory flyways are unknown. To identify wintering regions of turtle doves, we measured stable isotopes of feathers grown on the wintering grounds and used a dual-isotope (hydrogen ( δ 2 H f ) and carbon ( δ 13 C f )) probabilistic assignment to analyse origins of individuals migrating through the western and central/eastern flyways. The most probable wintering areas for turtle dove samples from both flyways were in the western and central Sub-Sahara. However, we found differences in δ 2 H f and δ 13 C f values between turtle doves following different migratory routes (western vs central/eastern flyway). This result suggests a higher likelihood of origins in the central Sub-Sahara for central and eastern migrants, while turtle doves using the western flyway originated primarily in the western Sub-Sahara, highlighting the importance of both regions for the future conservation of turtle doves from European breeding populations. The establishment of migratory connectivity of populations requires sampling from birds from the European as well as Asian continent; however, we provide important results that can be used to test hypotheses regarding population declines resulting from factors experienced over the full annual cycle for some populations.

Minc03328 effector gene downregulation severely affects Meloidogyne incognita parasitism in transgenic Arabidopsis thaliana - Valdeir Junio Vaz Moreira; Isabela Tristan Lourenço-Tessutti; Marcos Fernando Basso; Maria Eugênia Lisei-de-Sa; Carolina Vianna Morgante; Bruno Paes-de-Melo; Fabrício Barbosa Monteiro Arraes; Diogo Martins-de-Sa; Maria Cristina Mattar Silva; Janice de Almeida Engler; Maria Fatima Grossi-de-Sa (Planta, 2022)

Moderate-intensity continuous training and high-intensity interval training improve cognition, and BDNF levels of middle-aged overweight men - Neumir Sales de Lima; Ricardo Augusto Leoni De Sousa; Fabiano Trigueiro Amorim; Fernando Gripp; Caíque Olegário Diniz e Magalhães; Samuel Henrique Pinto; Marco Fabrício Dias Peixoto; Renato Sobral Monteiro-Junior; Kelsey Bourbeau; Ricardo Cardoso Cassilhas (Metabolic Brain Disease, 2022)

Changes in soil carbon and nitrogen stocks after conversion of subtropical natural forest to loblolly pine plantations - Mariana Alves Ibarr; Josiléia Acordi Zanatta; Jeferson Dieckow; Marcos Fernando Glück Rachwal; Ricardo Henrique Ribeiro; Denise Jeton Cardoso; Bruna Ramalho; James Stahl (European Journal of Forest Research, 2022)

Genetic variability analyses considering multi-environment trials in maize breeding - Igor Ferreira Coelho; Renan Garcia Malikouski; Jeniffer Santana Pinto Coelho Evangelista; Marco Antônio Peixoto; Rodrigo Silva Alves; Jefferson Fernando Naves Pinto; Edésio Fialho dos Reis; Leonardo Lopes Bhering (Euphytica, 2022)

ATLANTIC ANTS: a data set of ants in Atlantic Forests of South America - Rogério R. Silva; Felipe Martello; Rodrigo Machado Feitosa; Otávio Guilherme M. Silva; Lívia Pires do Prado; Carlos Roberto F. Brandão; Emília Zoppas de Albuquerque; Maria Santina C. Morini; Jacques Hubert Charles Delabie; Erison Carlos dos Santos Monteiro; Agripino Emanuel Oliveira Alves; Alexander L. Wild; et al. (Ecology, 2022)
Ants, an ecologically successful and numerically dominant group of animals, play key ecological roles as soil engineers, predators, nutrient recyclers, and regulators of plant growth and reproduction in most terrestrial ecosystems. Further, ants are widely used as bioindicators of the ecological impact of land use. We gathered information of ant species in the Atlantic Forest of South America. The ATLANTIC ANTS data set, which is part of the ATLANTIC SERIES data papers, is a compilation of ant records from collections (18,713 records), unpublished data (29,651 records), and published sources (106,910 records; 1,059 references), including papers, theses, dissertations, and book chapters published from 1886 to 2020. In total, the data set contains 153,818 ant records from 7,636 study locations in the Atlantic Forest, representing 10 subfamilies, 99 genera, 1,114 ant species identified with updated taxonomic certainty, and 2,235 morphospecies codes. Our data set reflects the heterogeneity in ant records, which include ants sampled at the beginning of the taxonomic history of myrmecology (the 19th and 20th centuries) and more recent ant surveys designed to address specific questions in ecology and biology. The data set can be used by researchers to develop strategies to deal with different macroecological and region‐wide questions, focusing on assemblages, species occurrences, and distribution patterns. Furthermore, the data can be used to assess the consequences of changes in land use in the Atlantic Forest on different ecological processes. No copyright restrictions apply to the use of this data set, but we request that authors cite this data paper when using these data in publications or teaching events.

Identification and quantification of potassium (K + ) deficiency in maize plants using an unmanned aerial vehicle and visible / near-infrared semi-professional digital camera - Renato Herrig Furlanetto; Marco Rafael Nanni; Luís Guilherme Teixeira Crusiol; Guilherme Fernando Capristo Silva; Adilson de Oliveira Junior; Rubson Natal Ribeiro Sibaldelli (International Journal of Remote Sensing, 2021)

Application of neural network to simulate the behavior of hospitalizations and their costs under the effects of various polluting gases in the city of São Paulo - Amanda Carvalho Miranda; José Carlos Curvelo Santana; Charles Lincoln Kenji Yamamura; Jorge Marcos Rosa; Elias Basile Tambourgi; Linda Lee Ho; Fernando Tobal Berssaneti (Air Quality, Atmosphere & Health, 2021)

Habitat filtering and inferred dispersal ability condition across‐scale species turnover and rarity in Macaronesian island spider assemblages - Jagoba Malumbres‐Olarte; François Rigal; Marco Girardello; Pedro Cardoso; Luís Carlos Crespo; Isabel R. Amorim; Miquel Arnedo; Mário Boieiro; José Carlos Carvalho; Rui Carvalho; Rosalina Gabriel; Lucas Lamelas‐Lopez; et al. (Journal of Biogeography, 2021)
Aim Habitat diversity has been linked to the diversity and structure of island communities, however, little is known about patterns and processes within habitats. Here we aim to determine the contributions of habitat type and inferred dispersal frequency to the differences in taxonomic structure between assemblages in the same island habitat. Location The Macaronesian archipelagos (Azores, Madeira, the Canary Islands and Cabo Verde). Taxon Spiders (Araneae). Methods We established forest and dry habitat sites (each with five plots) on two islands per archipelago. We collected spiders using standardised sampling protocols. We tested the differences in beta diversity separately for each habitat and for each inferred category of ballooning (an aerial dispersal strategy) frequency across geographic scales through nested non‐parametric permutational multivariate analyses of variance. We then tested whether ballooning and habitat influenced heterogeneity in species composition (dispersion in beta diversity) in the two habitat types. We analysed the effects of habitat and ballooning on species abundance distribution (SAD) and rarity by fitting Gambin models and evaluating the contribution of ballooning categories to SAD. Results Communities of the same archipelago and habitat were taxonomically more similar, and beta diversity increased with geographic scale, being greater in dry habitats. There was greater species replacement among assemblages in dry habitats than in forests, with greater differences for rare ballooners. There were no differences in SAD between habitats although dry habitat sites seemed to harbour more species with low abundances (rare species) than forests. Main conclusions Habitat type does not only condition the differences between spider assemblages of the same habitat but also the scale at which they occur. These differences may be determined by the heterogeneity in the physical structure of each habitat as well as how much this structure facilitates aerial dispersal (ballooning), and should be considered in theories/hypotheses on island community assembly as well as in conservation strategies.

Functional traits driving species role in the structure of terrestrial vertebrate scavenger networks - Esther Sebastián‐González; Zebensui Morales‐Reyes; Francisco Botella; Lara Naves‐Alegre; Juan M. Pérez‐García; Patricia Mateo‐Tomás; Pedro P. Olea; Marcos Moleón; Jomar Magalhães Barbosa; Fernando Hiraldo; Eneko Arrondo; José A. Donázar; et al. (Ecology, 2021)
Species assemblages often have a non‐random nested organization, which in vertebrate scavenger (carrion‐consuming) assemblages is thought to be driven by facilitation in competitive environments. However, not all scavenger species play the same role in maintaining assemblage structure, as some species are obligate scavengers (i.e., vultures) and others are facultative, scavenging opportunistically. We used a database with 177 vertebrate scavenger species from 53 assemblages in 22 countries across five continents to identify which functional traits of scavenger species are key to maintaining the scavenging network structure. We used network analyses to relate ten traits hypothesized to affect assemblage structure with the “role” of each species in the scavenging assemblage in which it appeared. We characterized the role of a species in terms of both the proportion of monitored carcasses on which that species scavenged, or scavenging breadth (i.e., the species “normalized degree”), and the role of that species in the nested structure of the assemblage (i.e., the species “paired nested degree”), therefore identifying possible facilitative interactions among species. We found that species with high olfactory acuity, social foragers, and obligate scavengers had the widest scavenging breadth. We also found that social foragers had a large paired nested degree in scavenger assemblages, probably because their presence is easier to detect by other species to signal carcass occurrence. Our study highlights differences in the functional roles of scavenger species and can be used to identify key species for targeted conservation to maintain the ecological function of scavenger assemblages.

Biomonitoring of surface water quality in the Chopim River within the Conservation Unit Campos de Palmas Wildlife Refuge, southern Brazil - Daiana Lauxen Schutz; Inara Giacobbo de Marco; Geiciane Locatelli Alves; José Vitor Abilhõa Vincoski; Sabrina Ishikawa; Ana Paula de Oliveira Schmitz; Eduardo Michel Vieira Gomes; Fernando Cesar Manosso; Ivane Benedetti Tonial; Juan Carlos Pokrywiecki; Rodrigo Lingnau; Ticiane Sauer Pokrywieki; et al. (Environmental Monitoring and Assessment, 2021)

Seroprevalence and risk factors for bovine brucellosis in the state of Paraná, Brazil: an analysis after 18 years of ongoing control measures - Diego Leonardo Rodrigues; Elenice Aparecida Amorim; Fernando Ferreira; Marcos Amaku; Oswaldo Santos Baquero; José Henrique de Hildebrand e Grisi Filho; Ricardo Augusto Dias; Marcos Bryan Heinemann; Evelise Oliveira Telles; Vitor Salvador Picão Gonçalves; Cord Heuer; José Soares Ferreira Neto (Tropical Animal Health and Production, 2021)

Combined and isolated effects of alcohol consumption and sleep deprivation on maximal strength, muscle endurance and aerobic exercise performance in healthy men: a cross-over randomized controlled trial - Rodrigo Rodrigues; Rodrigo de Azevedo Franke; Bruno C. Teixeira; Rodrigo C. O. Macedo; André Luiz Lopes; Fernando Diefenthaeler; Álvaro Reischak-Oliveira; Bruno Manfredini Baroni; Marco Aurélio Vaz (Sleep and Biological Rhythms, 2021)

Developing of a model to predict lying behavior of dairy cows on silvopastoral system during the winter season - Karolini Tenffen de Sousa; Matheus Deniz; Matheus Fernando Moro; Isabelle Cordova Gomes; Marcos Martinez do Vale; João Ricardo Dittrich (International Journal of Biometeorology, 2021)

Global phylogeography of sailfish: deep evolutionary lineages with implications for fisheries management - Bruno Lopes da Silva Ferrette; Bruno Mourato; Fábio Hissa Vieira Hazin; Freddy Arocha; Samuel Mackey Williams; Carlos Egberto Rodrigues Junior; Fábio Porto-Foresti; Alberto Ferreira de Amorim; Matheus Marcos Rotundo; Rui Coelho; John P. Hoolihan; Fambaye Ngom Sow; et al. (Hydrobiologia, 2021)

Large-scale Degradation of the Tocantins-Araguaia River Basin - Fernando Mayer Pelicice; Angelo Antonio Agostinho; Alberto Akama; José Dilermando Andrade Filho; Valter M. Azevedo-Santos; Marcus Vinicius Moreira Barbosa; Luis Mauricio Bini; Marcelo Fulgêncio Guedes Brito; Carlos Roberto dos Anjos Candeiro; Érica Pellegrini Caramaschi; Priscilla Carvalho; Rodrigo Assis de Carvalho; et al. (Environmental Management, 2021)

Modeling and optimization of reactive cotton dyeing using response surface methodology combined with artificial neural network and particle swarm techniques - Jorge Marcos Rosa; Flavio Guerhardt; Silvestre Eduardo Rocha Ribeiro Júnior; Peterson A. Belan; Gustavo A. Lima; José Carlos Curvelo Santana; Fernando Tobal Berssaneti; Elias Basile Tambourgi; Rosangela Maria Vanale; Sidnei Alves de Araújo (Clean Technologies and Environmental Policy, 2021)

The Geodiversity of Brazil: Quantification, Distribution, and Implications for Conservation Areas - Juliana de Paula Silva; Grace Bungenstab Alves; Jurandyr Luciano Sanches Ross; Fábio Soares de Oliveira; Marcos Antônio Leite do Nascimento; Mateus Grochoski Felini; Fernando César Manosso; Diamantino Ínsua Pereira (Geoheritage, 2021)

Correction to: Bacterial etiology of community-acquired pneumonia in immunocompetent hospitalized patients and appropriateness of empirical treatment recommendations: an international point-prevalence study - Manuela Carugati; S. Aliberti; G. Sotgiu; F. Blasi; A. Gori; R. Menendez; M. Encheva; M. Gallego; P. Leuschner; S. Ruiz-Buitrago; S. Battaglia; R. Fantini; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Exploring novel capping framework: high substituent pyridine-hydroxamic acid derivatives as potential antiproliferative agents - Fernando Hernández-Borja; Itzel Mercado-Sánchez; Yolanda Alcaraz; Marco A. García-Revilla; Clarisa Villegas Gómez; David Ordaz-Rosado; Nancy Santos-Martínez; Rocío García-Becerra; Miguel A. Vazquez (DARU Journal of Pharmaceutical Sciences, 2021)

Disentangling the taxonomic status and phylogeographic structure of Marmora’s (Curruca sarda) and Balearic Warbler (Curruca balearica): a genetic multi-marker approach - Davide Nespoli; Irene Pellegrino; Marco Galaverni; Romolo Caniglia; Joseph Sunyer; Chiara Mengoni; Ettore Randi; Andrea Galimberti; Diego Rubolini; Fernando Spina; Gabriel Gargallo; Mattia Brambilla (Journal of Ornithology, 2021)
Marmora’s Warbler ( Curruca sarda ) and Balearic Warbler ( C. balearica ) are allopatric sibling species and were recently split mostly based on morphological and ethological characteristics. Here we provide the first phylogenetic and phylogeographic analyses of this species complex to support the taxonomic status of C. sarda and C. balearica in light of integrative taxonomy. We sampled the two taxa in most of their breeding ranges and we sequenced three mitochondrial and one nuclear gene region. All C. balearica individuals had private haplotypes for the four markers and formed monophyletic clades. Genetic distances between the two taxa were comparable with those found between other species belonging to the Curruca genus. Furthermore, most of the genetic variance was expressed at the interspecific level, rather than between different populations within taxa or between individuals within populations. Our results strongly support the current taxonomic status of these two warblers as distinct species.

Nitrous oxide and methane emissions from soil and nitrogen uptake by eucalyptus fertilized with enhanced efficiency fertilizers - Mariana Alves Ibarr; Josiléia Acordi Zanatta; Jeferson Dieckow; Ricardo Henrique Ribeiro; Marcos Fernando Glück Rachwal; James Stahl (Plant and Soil, 2021)

Partitioning resilience of a marine foundation species into resistance and recovery trajectories - Fernando Tuya; Yolanda Fernández-Torquemada; Yoana del Pilar-Ruso; Fernando Espino; Pablo Manent; Leticia Curbelo; Francisco Otero-Ferrer; Jose A. de la Ossa; Laura Royo; Laura Antich; Inés Castejón; Julia Máñez-Crespo; et al. (Oecologia, 2021)

Beyond host specificity: the biotechnological exploitation of chitolectin from teratocytes of Toxoneuron nigriceps to control non-permissive hosts - Bruna Laís Merlin; Lilian Ellen Pino; Lázaro Eustáquio Pereira Peres; Fábio Prataviera; Edwin Moises Marcos Ortega; Fernando Luis Cônsoli (Journal of Pest Science, 2021)

Obituary: Walter Adolfo Voss (1933–2020) - Ismael Franz; Carla S. Fontana; Glayson A. Bencke; Marco A. Crozariol; Fernando C. Straube (Ornithology Research, 2021)

In-water and dry-dock hull fouling assessments reveal high risk for regional translocation of nonindigenous species in the southwestern Atlantic - Marco Meloni; Nancy Correa; Fabio Bettini Pitombo; Ignacio Luis Chiesa; Brenda Doti; Rodolfo Elías; Gabriel Genzano; Clara B. Giachetti; Diego Giménez; Juan López-Gappa; Catalina Pastor; Adriane Pereira Wandeness; et al. (Hydrobiologia, 2021)

Blutaparon portulacoides ethanolic extract reduced IL-1β and inflammatory parameters induced by the Mycobacterium complex and carrageenan in mice - Roberto Mikio Kassuya; Joyce Alencar Santos Radai; Luis Fernando Benitez Macorini; Viktor Krejci Nunes; Marcos José Salvador; Patricia Regina Terço Leite; Rodrigo Juliano Oliveira; Júlio Croda; Arielle Cristina Arena; Cândida Aparecida Leite Kassuya (Inflammopharmacology, 2021)

Serious liver injury induced by Nimesulide: an international collaborative study - Fernando Bessone; Nelia Hernandez; Manuel Mendizabal; Ezequiel Ridruejo; Gisela Gualano; Eduardo Fassio; Mirta Peralta; Hugo Fainboim; Margarita Anders; Hugo Tanno; Federico Tanno; Raymundo Parana; et al. (Archives of Toxicology, 2021)

Ecological aspects of killer whales from the Mexican Central Pacific coast: Revealing a new ecotype in the Eastern Tropical Pacific - Manuel H. Vargas‐Bravo; Fernando R. Elorriaga‐Verplancken; Aramis Olivos‐Ortiz; Blanca Morales‐Guerrero; Marco A. Liñán‐Cabello; Christian D. Ortega‐Ortiz (Marine Mammal Science, 2021)

hRNAi-mediated knock-down of Sphenophorus levis V-ATPase E in transgenic sugarcane (Saccharum spp interspecific hybrid) affects the insect growth and survival - Chakravarthi Mohan; Priscila Yumi Tanaka Shibao; Fernando Fonseca Pereira de Paula; Danyelle Toyama; Marcos Antonio Sanches Vieira; Antonio Figueira; Danielle Scotton; Andrea Soares-Costa; Flavio Henrique-Silva (Plant Cell Reports, 2021)

Cost‐effectiveness of longitudinal surveillance for Piscirickettsia salmonis using qPCR in Atlantic salmon farms ( Salmo salar ) in Chile - Marina K. V. C. Delphino; Fernando O. Mardones; Joaquin Neumann Heise; Alicia Gallardo; Daniel Jimenez; Andrea Peña; Marco Rozas‐Serri; Ian A. Gardner (Journal of Fish Diseases, 2021)
Costs of diagnostic testing including sample collection, sampling frequency and sample size are an important consideration in the evaluation of the economic feasibility of alternative surveillance strategies for detection of infectious diseases in aquatic animals. In Chile, Piscirickettsia salmonis is the primary reason for antibiotic treatments in farmed Atlantic salmon. In 2012, a surveillance and control programme for piscirickettsiosis was established with an overall goal of reducing antibiotic use. The present study estimated the cost‐effectiveness of different sampling frequencies and sample sizes to achieve at least 95% confidence of early detection of P. salmonis at the netpen and farm levels using a validated qPCR test. We developed a stochastic model that incorporated variability in test accuracy, within‐pen prevalence and sampling costs. Our findings indicated that the current piscirickettsiosis surveillance programme based on risk‐based sampling of five moribund or dead fish from 2 to 3 netpens is cost‐effective and gives a high probability of detection of P. salmonis in Atlantic salmon farms in Chile at both the netpen and farm levels. Results from this study should incentivize salmon farmers to establish cost‐effective strategies for early detection of P. salmonis infection and the application of this approach to other highly infectious diseases.

Statistical modeling of sea ice concentration in the northwest region of the Antarctic Peninsula - Fernando Luis Hillebrand; Ulisses Franz Bremer; Marcos Wellausen Dias de Freitas; Juliana Costi; Cláudio Wilson Mendes Júnior; Jorge Arigony-Neto; Jefferson Cardia Simões; Cristiano Niederauer da Rosa; Janisson Batista de Jesus (Environmental Monitoring and Assessment, 2021)

Out-of-plane mechanism in the seismic risk of masonry façades - Miguel A. Jaimes; Marcos M. Chávez; Fernando Peña; Adrián D. García-Soto (Bulletin of Earthquake Engineering, 2021)

Response of Trichogramma pretiosum females (Hymenoptera: Trichogrammatidae) to herbivore-induced Bt maize volatiles - Priscilla T. Nascimento; Marcos A. M. Fadini; Michele S. Rocha; Camila S. F. Souza; Beatriz A. Barros; Júlio O. F. Melo; Renzo G. Von Pinho; Fernando H. Valicente (Arthropod-Plant Interactions, 2021)

HIIT is superior than MICT on cardiometabolic health during training and detraining - Fernando Gripp; Roberto Carlos Nava; Ricardo Cardoso Cassilhas; Elizabethe Adriana Esteves; Caíque Olegário Diniz Magalhães; Marco Fabrício Dias-Peixoto; Flávio de Castro Magalhães; Fabiano Trigueiro Amorim (European Journal of Applied Physiology, 2021)

Soil loss and sediment yield in a perennial catchment in southwest Piauí, Brazil - Kamylla Gonçalves Oliveira Assis; Yuri Jacques Agra Bezerra da Silva; José Wellington Batista Lopes; João Carlos Medeiros; Marcos Paulo Rodrigues Teixeira; Fernando Braga Rimá; Vijay P. Singh (Environmental Monitoring and Assessment, 2021)

Raman and FT-IR spectroscopy of prefiring paintings and slips in pre-Hispanic South American pottery—the case of Diaguita Inca pottery: an initial glazing-painting process? (Tinogasta, Catamarca, Argentina) - Guillermo A. De La Fuente; Fernando Marte; Noemí E. Mastrangelo; Marina Martínez Carricondo; Guillermo Rozas; Sergio D. Vera; Carlos Nazar; Marcos Tascón (Archaeological and Anthropological Sciences, 2021)

Long‐term variability and trends in meteorological droughts in Western Europe (1851–2018) - Sergio M. Vicente‐Serrano; Fernando Domínguez‐Castro; Conor Murphy; Jamie Hannaford; Fergus Reig; Dhais Peña‐Angulo; Yves Tramblay; Ricardo M. Trigo; Neil Mac Donald; M. Yolanda Luna; Mark Mc Carthy; Gerard Van der Schrier; et al. (International Journal of Climatology, 2021)
We analysed long‐term variability and trends in meteorological droughts across Western Europe using the Standardized Precipitation Index (SPI). Precipitation data from 199 stations spanning the period 1851–2018 were employed, following homogenisation, to derive SPI‐3 and SPI‐12 series for each station, together with indices on drought duration and severity. Results reveal a general absence of statistically significant long‐term trends in the study domain, with the exception of significant trends at some stations, generally covering short periods. The largest decreasing trends in SPI‐3 (i.e., increasing drought conditions) were found for summer in the British and Irish Isles. In general, drought episodes experienced in the last two or three decades have precedents during the last 170·years, emphasizing the importance of long records for assessing change. The main characteristic of drought variability in Western Europe is its strong spatial diversity, with regions exhibiting a homogeneous temporal evolution. Notably, the temporal variability of drought in Western Europe is more dominant than long‐term trends. This suggests that long‐term drought trends cannot be confirmed in Western Europe using precipitation records alone. This study provides a long‐term regional assessment of drought variability in Western Europe, which can contribute to better understanding of regional climate change during the past two centuries.

RivFishTIME: A global database of fish time‐series to study global change ecology in riverine systems - Lise Comte; Juan Carvajal‐Quintero; Pablo A. Tedesco; Xingli Giam; Ulrich Brose; Tibor Erős; Ana F. Filipe; Marie‐Josée Fortin; Katie Irving; Claire Jacquet; Stefano Larsen; Sapna Sharma; et al. (Global Ecology and Biogeography, 2021)
Motivation We compiled a global database of long‐term riverine fish surveys from 46 regional and national monitoring programmes and from individual academic research efforts, with which numerous basic and applied questions in ecology and global change research can be explored. Such spatially and temporally extensive datasets have been lacking for freshwater systems in comparison to terrestrial ones. Main types of variables contained The database includes 11,386 time‐series of riverine fish community catch data, including 646,270 species‐specific abundance records, together with metadata related to the geographical location and sampling methodology of each time‐series. Spatial location and grain The database contains 11,072 unique sampling locations (stream reach), spanning 19 countries, five biogeographical realms and 402 hydrographical basins world‐wide. Time period and grain The database encompasses the period 1951–2019. Each time‐series is composed of a minimum of two yearly surveys (mean = 8 years) and represents a minimum time span of 10 years (mean = 19 years). Major taxa and level of measurement The database includes 944 species of ray‐finned fishes (Class Actinopterygii). Software format csv. Main conclusion Our collective effort provides the most comprehensive long‐term community database of riverine fishes to date. This unique database should interest ecologists who seek to understand the impacts of human activities on riverine fish biodiversity and to model and predict how fish communities will respond to future environmental change. Together, we hope it will promote advances in macroecological research in the freshwater realm.

Genes and SNPs in the pathway of immune response and caries risk: a systematic review and meta-analysis - Luiz Alexandre Chisini; Mariana Gonzalez Cademartori; Marucs Cristian Muniz Conde; Francine Dos Santos Costa; Luciana Tovo-Rodrigues; Rodrigo Varella de Carvalho; Flávio Fernando Demarco; Marcos Britto Correa (Biofouling, 2020)

Soil Biological Properties and Arbuscular Mycorrhizal Fungal Communities of Representative Crops Established in the Andean Region from Ecuadorian Highlands - María Eugenia Avila-Salem; Fabián Montesdeoca; Marco Orellana; Katherine Pacheco; Soraya Alvarado; Ninozhka Becerra; César Marín; Fernando Borie; Paula Aguilera; Pablo Cornejo (Journal of Soil Science and Plant Nutrition, 2020)

A multivariate model of time to conversion from mild cognitive impairment to Alzheimer’s disease - María Eugenia López; Agustín Turrero; Pablo Cuesta; Inmaculada Concepción Rodríguez-Rojo; Ana Barabash; Alberto Marcos; Fernando Maestú; Alberto Fernández (GeroScience, 2020)

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.

NEOTROPICAL ALIEN MAMMALS: a data set of occurrence and abundance of alien mammals in the Neotropics - Clarissa Alves da Rosa; Bruno R. Ribeiro; Vanesa Bejarano; Fernando Henrique Puertas; Adriana Bocchiglieri; Adriana Loeser dos Santos Barbosa; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adriele Aparecida Pereira; Adryelle Francisca de Souza Moreira; Agnis Cristiane de Souza; Aiesca Pellegrin; et al. (Ecology, 2020)
Biological invasion is one of the main threats to native biodiversity. For a species to become invasive, it must be voluntarily or involuntarily introduced by humans into a nonnative habitat. Mammals were among first taxa to be introduced worldwide for game, meat, and labor, yet the number of species introduced in the Neotropics remains unknown. In this data set, we make available occurrence and abundance data on mammal species that (1) transposed a geographical barrier and (2) were voluntarily or involuntarily introduced by humans into the Neotropics. Our data set is composed of 73,738 historical and current georeferenced records on alien mammal species of which around 96% correspond to occurrence data on 77 species belonging to eight orders and 26 families. Data cover 26 continental countries in the Neotropics, ranging from Mexico and its frontier regions (southern Florida and coastal‐central Florida in the southeast United States) to Argentina, Paraguay, Chile, and Uruguay, and the 13 countries of Caribbean islands. Our data set also includes neotropical species (e.g., Callithrix sp., Myocastor coypus , Nasua nasua) considered alien in particular areas of Neotropics. The most numerous species in terms of records are from Bos sp. ( n = 37,782), Sus scrofa ( n = 6,730), and Canis familiaris ( n = 10,084); 17 species were represented by only one record (e.g., S yncerus caffer, Cervus timorensis, Cervus unicolor, Canis latrans ). Primates have the highest number of species in the data set ( n = 20 species), partly because of uncertainties regarding taxonomic identification of the genera Callithrix, which includes the species Callithrix aurita, Callithrix flaviceps, Callithrix geoffroyi, Callithrix jacchus, Callithrix kuhlii, Callithrix penicillata , and their hybrids. This unique data set will be a valuable source of information on invasion risk assessments, biodiversity redistribution and conservation‐related research. There are no copyright restrictions. Please cite this data paper when using the data in publications. We also request that researchers and teachers inform us on how they are using the data.

Effect of bergamot on lipid profile in humans: A systematic review - Itziar Lamiquiz-Moneo; Jaume Giné-González; Sonsoles Alisente; Ana M. Bea; Sofía Pérez-Calahorra; Victoria Marco-Benedí; Lucía Baila-Rueda; Estíbaliz Jarauta; Ana Cenarro; Fernando Civeira; Rocío Mateo-Gallego (Critical Reviews in Food Science and Nutrition, 2020)

Comparative analysis of SNP data and hybrid taxa information by using a classificatory linear mixed model to study the genetic variation and heritability of initial height growth in selected poplar hybrids - Francisco Zamudio; Marco Yañez; Fernando Guerra; Derie Fuentes; Alvaro Gonzalez (Tree Genetics & Genomes, 2020)

Bayesian estimation of diagnostic sensitivity and specificity of a qPCR and a bacteriological culture method for Piscirickettsia salmonis in farmed Atlantic salmon ( Salmo salar L.) in Chile - Emilie Laurin; Ian A. Gardner; Andrea Peña; Marco Rozas‐Serri; Jorge Gayosa; Joaquin Neumann Heise; Fernando O. Mardones (Journal of Fish Diseases, 2020)
Early detection of piscirickettsiosis is an important purpose of government‐ and industry‐based surveillance for the disease in Atlantic salmon farms in Chile. Real‐time qPCRs are currently used for surveillance because bacterial isolation is inadequately sensitive or rapid enough for routine use. Since no perfect tests exist, we used Bayesian latent class models to estimate diagnostic sensitivity ( DSe ) and specificity ( DSp ) of qPCR and culture using separate two‐test, single‐population models for three farms ( n = 148, 151, 44). Informative priors were used for DSp (culture (beta(999,1); qPCR (beta(98,2)), and flat priors (beta 1,1) for DSe and prevalence. Models were run for liver and kidney tissues combined and separately, based on the presence of selected gross‐pathological signs. Across all models, qPCR DSe was 5‐ to 30‐fold greater than for culture. Combined‐tissue qPCR median DSe was highest in Farm 3 (sampled during P. salmonis outbreak ( DSe = 97.6%)) versus Farm 1 ( DSe = 85.6%) or Farm 2 ( DSe = 83.5%), both sampled before clinical disease. Median DSe of qPCR was similar for liver and kidney, but higher when gross‐pathological signs were evident at necropsy. High DSe and DSp and rapid turnaround‐time indicate that the qPCR is fit for surveillance programmes and diagnosis during an outbreak. Targeted testing of salmon with gross‐pathological signs can enhance DSe .

Multi-trait multi-environment diallel analyses for maize breeding - Igor Ferreira Coelho; Rodrigo Silva Alves; João Romero do Amaral Santos de Car Rocha; Marco Antônio Peixoto; Larissa Pereira Ribeiro Teodoro; Paulo Eduardo Teodoro; Jefferson Fernando Naves Pinto; Edésio Fialho dos Reis; Leonardo Lopes Bhering (Euphytica, 2020)

The global abundance of tree palms - Robert Muscarella; Thaise Emilio; Oliver L. Phillips; Simon L. Lewis; Ferry Slik; William J. Baker; Thomas L. P. Couvreur; Wolf L. Eiserhardt; Jens‐Christian Svenning; Kofi Affum‐Baffoe; Shin‐Ichiro Aiba; Everton C. de Almeida; et al. (Global Ecology and Biogeography, 2020)
Aim Palms are an iconic, diverse and often abundant component of tropical ecosystems that provide many ecosystem services. Being monocots, tree palms are evolutionarily, morphologically and physiologically distinct from other trees, and these differences have important consequences for ecosystem services (e.g., carbon sequestration and storage) and in terms of responses to climate change. We quantified global patterns of tree palm relative abundance to help improve understanding of tropical forests and reduce uncertainty about these ecosystems under climate change. Location Tropical and subtropical moist forests. Time period Current. Major taxa studied Palms (Arecaceae). Methods We assembled a pantropical dataset of 2,548 forest plots (covering 1,191 ha) and quantified tree palm (i.e., ≥10 cm diameter at breast height) abundance relative to co‐occurring non‐palm trees. We compared the relative abundance of tree palms across biogeographical realms and tested for associations with palaeoclimate stability, current climate, edaphic conditions and metrics of forest structure. Results On average, the relative abundance of tree palms was more than five times larger between Neotropical locations and other biogeographical realms. Tree palms were absent in most locations outside the Neotropics but present in >80% of Neotropical locations. The relative abundance of tree palms was more strongly associated with local conditions (e.g., higher mean annual precipitation, lower soil fertility, shallower water table and lower plot mean wood density) than metrics of long‐term climate stability. Life‐form diversity also influenced the patterns; palm assemblages outside the Neotropics comprise many non‐tree (e.g., climbing) palms. Finally, we show that tree palms can influence estimates of above‐ground biomass, but the magnitude and direction of the effect require additional work. Conclusions Tree palms are not only quintessentially tropical, but they are also overwhelmingly Neotropical. Future work to understand the contributions of tree palms to biomass estimates and carbon cycling will be particularly crucial in Neotropical forests.

Productivity and Profitability of the Sugarcane Production in the State of Sao Paulo, Brazil - Fernando Rodrigues de Amorim; Marco Tulio Ospina Patino; Petra Maria Bartmeyer; David Ferreira Lopes Santos (Sugar Tech, 2020)

Bacterial etiology of community-acquired pneumonia in immunocompetent hospitalized patients and appropriateness of empirical treatment recommendations: an international point-prevalence study - Manuela Carugati; S. Aliberti; G. Sotgiu; F. Blasi; A. Gori; R. Menendez; M. Encheva; M. Gallego; P. Leuschner; S. Ruiz-Buitrago; S. Battaglia; R. Fantini; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

Climatic refugia boosted allopatric diversification in Western Mediterranean vipers - Fernando Martínez‐Freiría; Inês Freitas; Marco A. L. Zuffi; Philippe Golay; Sylvain Ursenbacher; Guillermo Velo‐Antón (Journal of Biogeography, 2020)
Aim The ecological dimension of evolutionary processes has been scarcely addressed in phylogeographic studies. We reconstruct the historical biogeography of Western Mediterranean vipers to discover the role of climate in fostering diversification. Location Western Mediterranean Basin. Taxon Vipera aspis and Vipera latastei‐monticola complex. Methods We used nearly range‐wide phylogeographic analyses of three mitochondrial genes followed by geographic assignment of 4,056 records to genetic units to test phylogenetic niche conservatism, under a 3D hypervolume approach, and reconstruct paleoclimatic scenarios for the diversification of main lineages during Pleistocene. Results Bayesian inferences from mtDNA recovered three Miocene clades and nine Pliocene lineages that diversified during the Pleistocene. Diversification was mostly restricted to southern regions of Iberian and Italian peninsulas and to the north‐western African mountains until the late Pliocene. Some lineages expanded northwards during the Pleistocene. Accordingly, genetic diversity was higher in southern regions. Ecological niche tests mostly supported allopatric diversification with niche conservatism, although niche shifts occurred with two divergence events. Palaeoclimatic models identified particular requirements for the current distribution of main lineages and distinct responses to the cooling and warming events of the Pleistocene. Areas of climatic stability during the Pleistocene were identified for main lineages; however, climatic stability was weakly correlated with haplotype diversity. Main conclusions In the Western Mediterranean biodiversity hotspot, palaeo‐tectonic and palaeo‐climatic factors drove diversification since the Miocene. Comparisons among patterns of diversification, haplotype diversity, and climatic stability suggest that southern Iberian and Italian peninsulas, and north‐western African mountains acted as refugia since the Pliocene, while some northern areas favoured population persistence during the Pleistocene. Climate adaptation likely played a secondary role in the diversification of some lineages.

The role of restoration and scientific examination for the accurate attribution of a European painting in South America - Mariana Calderón Mejía; Marcos Tascon; Damasia Gallegos; Dolores Gónzalez Pondal; Mariana Bini; Lucia Liccioli; Serena Barone; Lorenzo Giuntini; Marielena Fedi; Francesco Taccetti; Fernando Marte (Rendiconti Lincei. Scienze Fisiche e Naturali, 2020)

Skeletal muscle hypertrophy: molecular and applied aspects of exercise physiology - Victor Hugo F. Arantes; Dailson Paulucio da Silva; Renato Luiz de Alvarenga; Augusto Terra; Alexander Koch; Marco Machado; Fernando Augusto Monteiro Saboia Pompeu (German Journal of Exercise and Sport Research, 2020)

Proposal for a microcosm biofilm model for the study of vulvovaginal candidiasis - Rossana de Aguiar Cordeiro; Ana Raquel Colares de Andrade; Fernando Victor Monteiro Portela; Lívia Maria Galdino Pereira; Santiago Gonçalves Bezerra Moura; Mônica Dantas Sampaio; Estefania Mota Araripe Pereira; Gláucia Morgana de Melo Guedes; Silviane Praciano Bandeira; Reginaldo Gonçalves de Lima-Neto; Vânia Maria Maciel Melo; Raimunda Sâmia Nogueira Brilhante; et al. (Biofouling, 2020)

Macromolecule extracted from Gracilaria caudata reduces inflammation and restores hepatic function in nimesulide-induced hepatic damage - Genilson José Dias Júnior; Sarah Izabelly Alves Lemos; Tarcisio Vieira de Brito; Cynthia Maria Carvalho Pereira; José Simião da Cruz Júnior; Jayro dos Santos Ferreira; Lauanda da Rocha Rodrigues; José Victor do Nascimento Lima; Carlos Eduardo da Silva Monteiro; Alvaro Xavier Franco; Pedro Marcos Gomes Soares; Even Herlany Pereira Alves; et al. (Journal of Applied Phycology, 2020)

Properties of juvenile wood of Schizolobium parahyba var. amazonicum (paricá) under different cropping systems - Camila Balby Ribeiro da Silva; Jose Alves dos Santos Junior; Anselmo Júnior Corrêa Araújo; Agust Sales; Marco Antonio Siviero; Fernando Wallase Carvalho Andrade; Jonnys Paz Castro; João Vicente de Figueiredo Latorraca; Luiz Eduardo de Lima Melo (Agroforestry Systems, 2020)

The effect of various after-ripening temperature regimens on the germination behaviour of Ambrosia artemisiifolia - Silvia Fogliatto; Marco Milan; Fernando De Palo; Francesco Vidotto (Plant Biosystems, 2020)

Insights obtained using different modules of the cotton uceA1.7 promoter - Marcos Fernando Basso; Isabela Tristan Lourenço-Tessutti; Carlos Busanello; Clidia Eduarda Moreira Pinto; Elínea de Oliveira Freitas; Thuanne Pires Ribeiro; Janice de Almeida Engler; Antonio Costa de Oliveira; Carolina Vianna Morgante; Marcio Alves-Ferreira; Maria Fatima Grossi-de-Sa (Planta, 2020)

Correction to: Effectiveness of combining microcurrent with resistance training in trained males - Fernando Naclerio; Marcos Seijo; Bettina Karsten; George Brooker; Leandro Carbone; Jack Thirkell; Eneko Larumbe-Zabala (European Journal of Applied Physiology, 2020)
The original version of this article unfortunately contained a mistake.

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Histoplasmosis Outbreaks in Brazil: Lessons to Learn About Preventing Exposure - Bernardo Tenório Guerra; Fernando Almeida-Silva; Rodrigo Almeida-Paes; Rossana Patrícia Basso; João Paulo Romualdo Alarcão Bernardes; Marcos Abreu Almeida; Lisandra Serra Damasceno; Melissa Orzechowski Xavier; Bodo Wanke; Rosely M. Zancopé-Oliveira; Marcus de Melo Teixeira (Mycopathologia, 2019)

Effectiveness of combining microcurrent with resistance training in trained males - Fernando Naclerio; Marcos Seijo; Bettina Karsten; George Brooker; Leandro Carbone; Jack Thirkell; Eneko Larumbe-Zabala (European Journal of Applied Physiology, 2019)
Introduction Microcurrent has been used to promote tissue healing after injury or to hasten muscle remodeling post exercise post exercise. Purpose To compare the effects of resistance training in combination with either, microcurrent or sham treatment, on-body composition and muscular architecture. Additionally, changes in performance and perceived delayed onset muscle soreness (DOMS) were determined. Methods Eighteen males (25.7 ± 7.6 years) completed an 8-week resistance training program involving 3 workouts per week (24 total sessions) wearing a microcurrent (MIC, n = 9) or a sham (SH, n = 9) device for 3-h post-workout or in the morning during non-training days. Measurements were conducted at pre and post intervention. Results Compared to baseline, both groups increased ( p < 0.05) muscle thickness of the elbow flexors (MIC + 2.9 ± 1.4 mm; SH + 3.0 ± 2.4 mm), triceps brachialis (MIC + 4.3 ± 2.8 mm; SH + 2.7 ± 2.6 mm), vastus medialis (MIC + 1.5 ± 1.5 mm; SH + 0.9 ± 0.8 mm) and vastus lateralis (MIC + 6.8 ± 8.0 mm; SH + 3.2 ± 1.8 mm). Although both groups increased ( p < 0.01) the pennation angle of vastus lateralis (MIC + 2.90° ± 0.95°; SH + 1.90° ± 1.35°, p < 0.01), the change measured in MIC was higher ( p = 0.045) than that observed in SH. Furthermore, only MIC enlarged ( p < 0.01) the pennation angle of brachialis (MIC + 1.93 ± 1.51). Both groups improved ( p < 0.05) bench press strength and power but only MIC enhanced ( p < 0.01) vertical jump height. At post intervention, only MIC decreased ( p < 0.05) DOMS at 12-h, 24-h, and 48-h after performing an exercise-induced muscle soreness protocol. Conclusion A 3-h daily use of microcurrent maximized muscular architectural changes and attenuated DOMS with no added significant benefits on body composition and performance.

Study of lipid reserves in Liolaemus koslowskyi (Squamata: Liolaemidae): reproductive and ecological implications - Marcos Maximiliano Paz; Noelia Elizabeth García; Romina Valeria Semhan; Fernando José Lobo; Cristian Simón Abdala (Journal of Comparative Physiology B, 2019)

Back home? Uncertainties for returning seized animals to the source‐areas under climate change - Guilherme Fernando Gomes Destro; Virgínia de Fernandes; André Felipe Alves de Andrade; Paulo De Marco; Levi Carina Terribile (Global Change Biology, 2019)
Regardless of the economic, social and environmental impacts caused by wild animal trafficking worldwide, the suitable destination of seized specimens is one of the main challenges faced by environmental managers and authorities. In Brazil, returning seized animals to the wild has been the most frequent path in population restoration programs, and has been carried out, as a priority, in areas where the animals were captured. However, in addition to the difficulty in identifying the locations of illegal captures, little scientific knowledge is available on the future viability of the source‐areas to global climate change. Thus, the current work aims to evaluate the impacts of climate change on the main source‐municipalities for animal trafficking in Brazil, referred to herein as source‐areas. For this, using ecological niche modeling, the environmental suitability of the source‐areas for illegal animal captures was evaluated in two scenarios at two different time horizons: optimistic (RCP 26) and pessimistic (RCP 85) emission scenarios in both 2050 and 2070 projections. Moreover, the source‐areas were compared with the Brazilian Federal protected areas, used here as the control group. According to the results, Brazilian source‐municipalities are not always the best option for maintaining the most seized species in the future simulations, and, therefore, seem not be the best option for projects that aim for the return of these animals to the wild. In this sense, despite the genetic and ecological issues inherent in translocation projects, our results suggest that population restoration programs for seized species need to be rethought, and furthermore other suitable areas could be considered for truly ensuring the survival and maintenance of overexploited populations in the long term.

Current Aspects of Diagnosis and Therapeutics of Histoplasmosis and Future Trends: Moving onto a New Immune (Diagnosis and Therapeutic) Era? - Fernando Almeida-Silva; Diego de Souza Gonçalves; Marcos de Abreu Almeida; Allan J. Guimarães (Current Clinical Microbiology Reports, 2019)

Positive interactions among native and invasive vascular plants in Antarctica: assessing the “nurse effect” at different spatial scales - Cristian Atala; Luis R. Pertierra; Pedro Aragón; Fernando Carrasco-Urra; Paris Lavín; Jorge Gallardo-Cerda; Natalia Ricote-Martínez; Cristian Torres-Díaz; Marco A. Molina-Montenegro (Biological Invasions, 2019)

Hidden paintings, forgotten histories: a micro-stratigraphic approach to study coated rock art - Lucas Gheco; Marcos Tascon; Marcos Gastaldi; Eugenia Ahets Etcheberry; Soledad Pereda; Noemi Mastrangelo; Marcos Quesada; Fernando Marte (Archaeological and Anthropological Sciences, 2019)

Scavenging in the Anthropocene: Human impact drives vertebrate scavenger species richness at a global scale - Esther Sebastián‐González; Jomar Magalhães Barbosa; Juan M. Pérez‐García; Zebensui Morales‐Reyes; Francisco Botella; Pedro P. Olea; Patricia Mateo‐Tomás; Marcos Moleón; Fernando Hiraldo; Eneko Arrondo; José A. Donázar; Ainara Cortés‐Avizanda; et al. (Global Change Biology, 2019)
Understanding the distribution of biodiversity across the Earth is one of the most challenging questions in biology. Much research has been directed at explaining the species latitudinal pattern showing that communities are richer in tropical areas; however, despite decades of research, a general consensus has not yet emerged. In addition, global biodiversity patterns are being rapidly altered by human activities. Here, we aim to describe large‐scale patterns of species richness and diversity in terrestrial vertebrate scavenger (carrion‐consuming) assemblages, which provide key ecosystem functions and services. We used a worldwide dataset comprising 43 sites, where vertebrate scavenger assemblages were identified using 2,485 carcasses monitored between 1991 and 2018. First, we evaluated how scavenger richness (number of species) and diversity (Shannon diversity index) varied among seasons (cold vs. warm, wet vs. dry). Then, we studied the potential effects of human impact and a set of macroecological variables related to climatic conditions on the scavenger assemblages. Vertebrate scavenger richness ranged from species‐poor to species rich assemblages (4–30 species). Both scavenger richness and diversity also showed some seasonal variation. However, in general, climatic variables did not drive latitudinal patterns, as scavenger richness and diversity were not affected by temperature or rainfall. Rainfall seasonality slightly increased the number of species in the community, but its effect was weak. Instead, the human impact index included in our study was the main predictor of scavenger richness. Scavenger assemblages in highly human‐impacted areas sustained the smallest number of scavenger species, suggesting human activity may be overriding other macroecological processes in shaping scavenger communities. Our results highlight the effect of human impact at a global scale. As species‐rich assemblages tend to be more functional, we warn about possible reductions in ecosystem functions and the services provided by scavengers in human‐dominated landscapes in the Anthropocene.

NEOTROPICAL XENARTHRANS: a data set of occurrence of xenarthran species in the Neotropics - Paloma Marques Santos; Adriana Bocchiglieri; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adryelle Moreira; Agnis Cristiane de Souza; Agustin Manuel Abba; Agustin Paviolo; Ailin Gatica; Akyllan Zoppi Medeiro; Alan Nilo Costa; Alberto Gonzalez Gallina; et al. (Ecology, 2019)
Xenarthrans—anteaters, sloths, and armadillos—have essential functions for ecosystem maintenance, such as insect control and nutrient cycling, playing key roles as ecosystem engineers. Because of habitat loss and fragmentation, hunting pressure, and conflicts with domestic dogs, these species have been threatened locally, regionally, or even across their full distribution ranges. The Neotropics harbor 21 species of armadillos, 10 anteaters, and 6 sloths. Our data set includes the families Chlamyphoridae (13), Dasypodidae (7), Myrmecophagidae (3), Bradypodidae (4), and Megalonychidae (2). We have no occurrence data on Dasypus pilosus (Dasypodidae). Regarding Cyclopedidae, until recently, only one species was recognized, but new genetic studies have revealed that the group is represented by seven species. In this data paper, we compiled a total of 42,528 records of 31 species, represented by occurrence and quantitative data, totaling 24,847 unique georeferenced records. The geographic range is from the southern United States, Mexico, and Caribbean countries at the northern portion of the Neotropics, to the austral distribution in Argentina, Paraguay, Chile, and Uruguay. Regarding anteaters, Myrmecophaga tridactyla has the most records ( n = 5,941), and Cyclopes sp. have the fewest ( n = 240). The armadillo species with the most data is Dasypus novemcinctus ( n = 11,588), and the fewest data are recorded for Calyptophractus retusus ( n = 33). With regard to sloth species, Bradypus variegatus has the most records ( n = 962), and Bradypus pygmaeus has the fewest ( n = 12). Our main objective with Neotropical Xenarthrans is to make occurrence and quantitative data available to facilitate more ecological research, particularly if we integrate the xenarthran data with other data sets of Neotropical Series that will become available very soon (i.e., Neotropical Carnivores, Neotropical Invasive Mammals, and Neotropical Hunters and Dogs). Therefore, studies on trophic cascades, hunting pressure, habitat loss, fragmentation effects, species invasion, and climate change effects will be possible with the Neotropical Xenarthrans data set. Please cite this data paper when using its data in publications. We also request that researchers and teachers inform us of how they are using these data.

Phylogeography of eagle rays of the genus Aetobatus: Aetobatus narinari is restricted to the continental western Atlantic Ocean - João Bráullio L. Sales; Cintia Negrão de Oliveira; Wagner César Rosa dos Santos; Matheus Marcos Rotundo; Yrlene Ferreira; Jonathan Ready; Iracilda Sampaio; Claudio Oliveira; Vanessa P. Cruz; Raul E. Lara-Mendoza; Luis Fernando da Silva Rodrigues-Filho (Hydrobiologia, 2019)

ATLANTIC BIRD TRAITS : a data set of bird morphological traits from the Atlantic forests of South America - Rodolpho Credo Rodrigues; Érica Hasui; Julia Camara Assis; João Carlos Castro Pena; Renata L. Muylaert; Vinicius Rodrigues Tonetti; Felipe Martello; André Luis Regolin; Thiago Vernaschi Vieira da Costa; Mauro Pichorim; Eduardo Carrano; Leonardo Esteves Lopes; et al. (Ecology, 2019)
Scientists have long been trying to understand why the Neotropical region holds the highest diversity of birds on Earth. Recently, there has been increased interest in morphological variation between and within species, and in how climate, topography, and anthropogenic pressures may explain and affect phenotypic variation. Because morphological data are not always available for many species at the local or regional scale, we are limited in our understanding of intra‐ and interspecies spatial morphological variation. Here, we present the ATLANTIC BIRD TRAITS , a data set that includes measurements of up to 44 morphological traits in 67,197 bird records from 2,790 populations distributed throughout the Atlantic forests of South America. This data set comprises information, compiled over two centuries (1820–2018), for 711 bird species, which represent 80% of all known bird diversity in the Atlantic Forest. Among the most commonly reported traits are sex ( n = 65,717), age ( n = 63,852), body mass ( n = 58,768), flight molt presence ( n = 44,941), molt presence ( n = 44,847), body molt presence ( n = 44,606), tail length ( n = 43,005), reproductive stage ( n = 42,588), bill length ( n = 37,409), body length ( n = 28,394), right wing length ( n = 21,950), tarsus length ( n = 20,342), and wing length ( n = 18,071). The most frequently recorded species are Chiroxiphia caudata ( n = 1,837), Turdus albicollis ( n = 1,658), Trichothraupis melanops ( n = 1,468), Turdus leucomelas ( n = 1,436), and Basileuterus culicivorus ( n = 1,384). The species recorded in the greatest number of sampling localities are Basileuterus culicivorus ( n = 243), Trichothraupis melanops ( n = 242), Chiroxiphia caudata ( n = 210), Platyrinchus mystaceus ( n = 208), and Turdus rufiventris ( n = 191). ATLANTIC BIRD TRAITS ( ABT ) is the most comprehensive data set on measurements of bird morphological traits found in a biodiversity hotspot; it provides data for basic and applied research at multiple scales, from individual to community, and from the local to the macroecological perspectives. No copyright or proprietary restrictions are associated with the use of this data set. Please cite this data paper when the data are used in publications or teaching and educational activities.

Secretory IgA-mediated immune response in saliva and early detection of Pseudomonas aeruginosa in the lower airways of pediatric cystic fibrosis patients - Renan Marrichi Mauch; Claudio Lucio Rossi; Marcos Tadeu Nolasco da Silva; Talita Bianchi Aiello; José Dirceu Ribeiro; Antônio Fernando Ribeiro; Niels Høiby; Carlos Emilio Levy (Medical Microbiology and Immunology, 2019)

Dissolved humic substances supplied as potential enhancers of Cu, Cd, and Pb adsorption by two different mangrove sediments - Marco Pittarello; Jader Galba Busato; Paolo Carletti; Fernando Fabriz Sodré; Leonardo Barros Dobbss (Journal of Soils and Sediments, 2019)

ATLANTIC EPIPHYTES : a data set of vascular and non‐vascular epiphyte plants and lichens from the Atlantic Forest - Flavio Nunes Ramos; Sara Ribeiro Mortara; Nathalia Monalisa‐Francisco; João Pedro Costa Elias; Luiz Menini Neto; Leandro Freitas; Rodrigo Kersten; André Márcio Amorim; Fernando Bittencourt Matos; André Felippe Nunes‐Freitas; Suzana Alcantara; Marcia Helena Nagahama Alexandre; et al. (Ecology, 2019)
Epiphytes are hyper‐diverse and one of the frequently undervalued life forms in plant surveys and biodiversity inventories. Epiphytes of the Atlantic Forest, one of the most endangered ecosystems in the world, have high endemism and radiated recently in the Pliocene. We aimed to (1) compile an extensive Atlantic Forest data set on vascular, non‐vascular plants (including hemiepiphytes), and lichen epiphyte species occurrence and abundance; (2) describe the epiphyte distribution in the Atlantic Forest, in order to indicate future sampling efforts. Our work presents the first epiphyte data set with information on abundance and occurrence of epiphyte phorophyte species. All data compiled here come from three main sources provided by the authors: published sources (comprising peer‐reviewed articles, books, and theses), unpublished data, and herbarium data. We compiled a data set composed of 2,095 species, from 89,270 holo/hemiepiphyte records, in the Atlantic Forest of Brazil, Argentina, Paraguay, and Uruguay, recorded from 1824 to early 2018. Most of the records were from qualitative data (occurrence only, 88%), well distributed throughout the Atlantic Forest. For quantitative records, the most common sampling method was individual trees (71%), followed by plot sampling (19%), and transect sampling (10%). Angiosperms (81%) were the most frequently registered group, and Bromeliaceae and Orchidaceae were the families with the greatest number of records (27,272 and 21,945, respectively). Ferns and Lycophytes presented fewer records than Angiosperms, and Polypodiaceae were the most recorded family, and more concentrated in the Southern and Southeastern regions. Data on non‐vascular plants and lichens were scarce, with a few disjunct records concentrated in the Northeastern region of the Atlantic Forest. For all non‐vascular plant records, Lejeuneaceae, a family of liverworts, was the most recorded family. We hope that our effort to organize scattered epiphyte data help advance the knowledge of epiphyte ecology, as well as our understanding of macroecological and biogeographical patterns in the Atlantic Forest. No copyright restrictions are associated with the data set. Please cite this Ecology Data Paper if the data are used in publication and teaching events.

Compositional response of Amazon forests to climate change - Adriane Esquivel‐Muelbert; Timothy R. Baker; Kyle G. Dexter; Simon L. Lewis; Roel J. W. Brienen; Ted R. Feldpausch; Jon Lloyd; Abel Monteagudo‐Mendoza; Luzmila Arroyo; Esteban Álvarez-Dávila; Niro Higuchi; Beatriz S. Marimon; et al. (Global Change Biology, 2019)
Most of the planet's diversity is concentrated in the tropics, which includes many regions undergoing rapid climate change. Yet, while climate‐induced biodiversity changes are widely documented elsewhere, few studies have addressed this issue for lowland tropical ecosystems. Here we investigate whether the floristic and functional composition of intact lowland Amazonian forests have been changing by evaluating records from 106 long‐term inventory plots spanning 30 years. We analyse three traits that have been hypothesized to respond to different environmental drivers (increase in moisture stress and atmospheric CO 2 concentrations): maximum tree size, biogeographic water‐deficit affiliation and wood density. Tree communities have become increasingly dominated by large‐statured taxa, but to date there has been no detectable change in mean wood density or water deficit affiliation at the community level, despite most forest plots having experienced an intensification of the dry season. However, among newly recruited trees, dry‐affiliated genera have become more abundant, while the mortality of wet‐affiliated genera has increased in those plots where the dry season has intensified most. Thus, a slow shift to a more dry‐affiliated Amazonia is underway, with changes in compositional dynamics (recruits and mortality) consistent with climate‐change drivers, but yet to significantly impact whole‐community composition. The Amazon observational record suggests that the increase in atmospheric CO 2 is driving a shift within tree communities to large‐statured species and that climate changes to date will impact forest composition, but long generation times of tropical trees mean that biodiversity change is lagging behind climate change.

ATLANTIC ‐ PRIMATES : a dataset of communities and occurrences of primates in the Atlantic Forests of South America - Laurence Culot; Lucas Augusto Pereira; Ilaria Agostini; Marco Antônio Barreto de Almeida; Rafael Souza Cruz Alves; Izar Aximoff; Alex Bager; María Celia Baldovino; Thiago Ribas Bella; Júlio César Bicca‐Marques; Caryne Braga; Carlos Rodrigo Brocardo; et al. (Ecology, 2019)
Primates play an important role in ecosystem functioning and offer critical insights into human evolution, biology, behavior, and emerging infectious diseases. There are 26 primate species in the Atlantic Forests of South America, 19 of them endemic. We compiled a dataset of 5,472 georeferenced locations of 26 native and 1 introduced primate species, as hybrids in the genera Callithrix and Alouatta . The dataset includes 700 primate communities, 8,121 single species occurrences and 714 estimates of primate population sizes, covering most natural forest types of the tropical and subtropical Atlantic Forest of Brazil, Paraguay and Argentina and some other biomes. On average, primate communities of the Atlantic Forest harbor 2 ± 1 species (range = 1–6). However, about 40% of primate communities contain only one species. Alouatta guariba (N = 2,188 records) and Sapajus nigritus (N = 1,127) were the species with the most records. Callicebus barbarabrownae (N = 35), Leontopithecus caissara (N = 38), and Sapajus libidinosus (N = 41) were the species with the least records. Recorded primate densities varied from 0.004 individuals/km 2 ( Alouatta guariba at Fragmento do Bugre, Paraná, Brazil) to 400 individuals/km 2 ( Alouatta caraya in Santiago, Rio Grande do Sul, Brazil). Our dataset reflects disparity between the numerous primate census conducted in the Atlantic Forest, in contrast to the scarcity of estimates of population sizes and densities. With these data, researchers can develop different macroecological and regional level studies, focusing on communities, populations, species co‐occurrence and distribution patterns. Moreover, the data can also be used to assess the consequences of fragmentation, defaunation, and disease outbreaks on different ecological processes, such as trophic cascades, species invasion or extinction, and community dynamics. There are no copyright restrictions. Please cite this Data Paper when the data are used in publications. We also request that researchers and teachers inform us of how they are using the data.

Characterization of the responses to saline stress in the symbiotic green microalga Trebouxia sp. TR9 - Ernesto Hinojosa-Vidal; Francisco Marco; Fernando Martínez-Alberola; Francisco J. Escaray; Francisco J. García-Breijo; José Reig-Armiñana; Pedro Carrasco; Eva Barreno (Planta, 2018)

Genomic prediction ability for beef fatty acid profile in Nelore cattle using different pseudo-phenotypes - Hermenegildo Lucas Justino Chiaia; Elisa Peripolli; Rafael Medeiros de Oliveira Silva; Fabiele Loise Braga Feitosa; Marcos Vinícius Antunes de Lemos; Mariana Piatto Berton; Bianca Ferreira Olivieri; Rafael Espigolan; Rafael Lara Tonussi; Daniel Gustavo Mansan Gordo; Lucia Galvão de Albuquerque; Henrique Nunes de Oliveira; et al. (Journal of Applied Genetics, 2018)

Pan‐tropical prediction of forest structure from the largest trees - Jean‐François Bastin; Ervan Rutishauser; James R. Kellner; Sassan Saatchi; Raphael Pélissier; Bruno Hérault; Ferry Slik; Jan Bogaert; Charles De Cannière; Andrew R. Marshall; John Poulsen; Patricia Alvarez‐Loyayza; et al. (Global Ecology and Biogeography, 2018)
Aim Large tropical trees form the interface between ground and airborne observations, offering a unique opportunity to capture forest properties remotely and to investigate their variations on broad scales. However, despite rapid development of metrics to characterize the forest canopy from remotely sensed data, a gap remains between aerial and field inventories. To close this gap, we propose a new pan‐tropical model to predict plot‐level forest structure properties and biomass from only the largest trees. Location Pan‐tropical. Time period Early 21st century. Major taxa studied Woody plants. Methods Using a dataset of 867 plots distributed among 118 sites across the tropics, we tested the prediction of the quadratic mean diameter, basal area, Lorey's height, community wood density and aboveground biomass (AGB) from the i th largest trees. Results Measuring the largest trees in tropical forests enables unbiased predictions of plot‐ and site‐level forest structure. The 20 largest trees per hectare predicted quadratic mean diameter, basal area, Lorey's height, community wood density and AGB with 12, 16, 4, 4 and 17.7% of relative error, respectively. Most of the remaining error in biomass prediction is driven by differences in the proportion of total biomass held in medium‐sized trees (50–70 cm diameter at breast height), which shows some continental dependency, with American tropical forests presenting the highest proportion of total biomass in these intermediate‐diameter classes relative to other continents. Main conclusions Our approach provides new information on tropical forest structure and can be used to generate accurate field estimates of tropical forest carbon stocks to support the calibration and validation of current and forthcoming space missions. It will reduce the cost of field inventories and contribute to scientific understanding of tropical forest ecosystems and response to climate change.

Acute toxicity and effects of Roundup Original® on pintado da Amazônia - Jhonnes Marcos dos Santos Teixeira; Valfran da Silva Lima; Fernando Rafael de Moura; Patrícia da Costa Marisco; Adilson Paulo Sinhorin; Valéria Dornelles Gindri Sinhorin (Environmental Science and Pollution Research, 2018)

Identification of Mycobacterium species and Rhodococcus equi in peccary lymph nodes - Amanda Bonalume Cordeiro de Morais; Carmen Alicia Daza Bolaños; Ana Carolina Alves; Cássia Yumi Ikuta; Gustavo Henrique Batista Lara; Marcos Bryan Heinemann; Rogério Giuffrida; Fernando Paganini Listoni; Mateus de Souza Ribeiro Mioni; Rodrigo Garcia Motta; Shinji Takai; Márcio Garcia Ribeiro (Tropical Animal Health and Production, 2018)

Combination Therapy with Sulfasalazine and Valproic Acid Promotes Human Glioblastoma Cell Death Through Imbalance of the Intracellular Oxidative Response - Carlos Gustavo Garcia; Suzana Assad Kahn; Luiz Henrique Medeiros Geraldo; Igor Romano; Ivan Domith; Deborah Christinne Lima e Silva; Fernando dos Santos Assunção; Marcos José Ferreira; Camila Cabral Portugal; Jorge Marcondes de Souza; Luciana Ferreira Romão; Annibal Duarte Pereira Netto; et al. (Molecular Neurobiology, 2018)

Phylogeography and species distribution modelling reveal the effects of the Pleistocene ice ages on an intertidal limpet from the south‐eastern Pacific - María Cecilia Pardo‐Gandarillas; Christian M. Ibáñez; Felipe I. Torres; Víctor Sanhueza; Alejandra Fabres; Joaquín Escobar‐Dodero; Fernando O. Mardones; Marco A. Méndez (Journal of Biogeography, 2018)
Aim The distribution and genetic composition of marine populations is the result of climatic and oceanographic factors as well as life history strategies. Studying species with wide distributions and high dispersal potential in sites that were differentially affected during the Pleistocene glaciations provides an opportunity to evaluate the genetic and distributional effect of glaciations on marine populations, such as the limpet Siphonaria lesonii . The aim of the present study is to evaluate the differential effects of glaciations on areas covered and not covered by ice sheets during the Pleistocene glaciations. Location Intertidal zone of the south‐eastern Pacific covering approximately 5,000 km of coastline of Peru and Chile. Methods We performed molecular analyses of mitochondrial and nuclear data jointly, as well as environmental niche modelling ( ENM ) of populations of the limpet Siphonaria lessonii . Using ENM , we modelled the potential distributional range of the species in the present and its distribution during the Last Glacial Maximum ( LGM ). Results Two lineages were found that were separated by a break at 41° S, corresponding to the biogeographical discontinuity previously reported for this region. Both of these lineages experienced genetic and demographical fluctuations that match the Pleistocene glaciations; however, the variability was more intense in the southern lineage. Phylogeography and ENM yielded complementary results for the southern lineage, which experienced loss of genetic diversity and habitat during the LGM , whereas the northern lineage evidenced loss of genetic diversity without distributional changes. Main conclusions The phylogeographical and ENM approaches suggest a historical scenario involving demographic and distributional contractions of S. lessonii surviving in glacial refugia in the southern portion of the south‐eastern Pacific. This study is the first to include both phylogeographical and ENM analyses of marine species from the Southern Hemisphere.

Brassica napus Growth in Lead-Polluted Soil: Bioaccumulation in Plant Organs at Different Ontogenetic Stages and Lead Fractionation in Soil - Gisele V. Ferreyroa; Jonathan Gelma; Mariana D. Sosa; Marcos A. Orellana Benitez; Mabel B. Tudino; Raúl S. Lavado; Fernando V. Molina (Water, Air, & Soil Pollution, 2018)

Rolling into the deep of the land planarian genus Choeradoplana (Tricladida, Continenticola, Geoplanidae) taxonomy - Fernando Carbayo; Marcos Santos Silva; Marta Riutort; Marta Álvarez-Presas (Organisms Diversity & Evolution, 2018)

Association study between copy number variation and beef fatty acid profile of Nellore cattle - Marcos Vinicius Antunes de Lemos; Elisa Peripolli; Mariana Piatto Berton; Fabiele Loise Braga Feitosa; Bianca Ferreira Olivieri; Nedenia Bonvino Stafuzza; Rafael Lara Tonussi; Sabrina Kluska; Hermenegildo Lucas Justino Chiaia; Lenise Mueller; Adrielli Mathias Ferrinho; Angelica Simone Cravo Prereira; et al. (Journal of Applied Genetics, 2018)

Contamination of soil and the medicinal plant Phyllanthus niruri Linn. with cadmium in ceramic industrial areas - Vanessa Santana Vieira Santos; Karen Magalhães Arantes; Ester Luiza Gonçalves; Carlos Fernando Campos; Edimar Olegário de Campos Júnior; Antônio Marcos Machado de Oliveira; Boscolli Barbosa Pereira (Environmental Monitoring and Assessment, 2018)

Effects of hurricane Odile on the infrastructure of Baja California Sur, Mexico - David Murià-Vila; Miguel Á. Jaimes; Adrián Pozos-Estrada; Alberto López; Eduardo Reinoso; Marcos M. Chávez; Fernando Peña; Jorge Sánchez-Sesma; Oscar López (Natural Hazards, 2018)

Resveratrol and Brain Mitochondria: a Review - Fernanda Rafaela Jardim; Fernando Tonon de Rossi; Marielle Xavier Nascimento; Renata Gabriele da Silva Barros; Paula Agrizzi Borges; Isabella Cristina Prescilio; Marcos Roberto de Oliveira (Molecular Neurobiology, 2018)

ATLANTIC MAMMAL TRAITS : a data set of morphological traits of mammals in the Atlantic Forest of South America - Fernando Gonçalves; Ricardo S. Bovendorp; Gabrielle Beca; Carolina Bello; Raul Costa‐Pereira; Renata L. Muylaert; Raisa R. Rodarte; Nacho Villar; Rafael Souza; Maurício E. Graipel; Jorge J. Cherem; Deborah Faria; et al. (Ecology, 2018)
Measures of traits are the basis of functional biological diversity. Numerous works consider mean species‐level measures of traits while ignoring individual variance within species. However, there is a large amount of variation within species and it is increasingly apparent that it is important to consider trait variation not only between species, but also within species. Mammals are an interesting group for investigating trait‐based approaches because they play diverse and important ecological functions (e.g., pollination, seed dispersal, predation, grazing) that are correlated with functional traits. Here we compile a data set comprising morphological and life history information of 279 mammal species from 39,850 individuals of 388 populations ranging from −5.83 to −29.75 decimal degrees of latitude and −34.82 to −56.73 decimal degrees of longitude in the Atlantic forest of South America. We present trait information from 16,840 individuals of 181 species of non‐volant mammals (Rodentia, Didelphimorphia, Carnivora, Primates, Cingulata, Artiodactyla, Pilosa, Lagomorpha, Perissodactyla) and from 23,010 individuals of 98 species of volant mammals (Chiroptera). The traits reported include body mass, age, sex, reproductive stage, as well as the geographic coordinates of sampling for all taxa. Moreover, we gathered information on forearm length for bats and body length and tail length for rodents and marsupials. No copyright restrictions are associated with the use of this data set. Please cite this data paper when the data are used in publications. We also request that researchers and teachers inform us of how they are using the data.

Influences of nitrogen fertilization and energy supplementation for growth perfomance of beef cattle on Alexander grass - Tiago Venturini; Luís Fernando Glasenapp de Menezes; Marcelo Marcos Montagner; Wagner Paris; Gean Rodrigo Schmitz; Marcos Luis Molinete (Tropical Animal Health and Production, 2017)

Within-crown acclimation of leaf-level physiological and morphological parameters in young loblolly pine stands - Marco A. Yáñez; Thomas R. Fox; John R. Seiler; Fernando Guerra; Ricardo M. Baettig; Francisco Zamudio; Javier E. Gyenge (Trees, 2017)

ATLANTIC BATS : a data set of bat communities from the Atlantic Forests of South America - Renata d. L. Muylaert; Richard D. Stevens; Carlos E. L. Esbérard; Marco A. R. Mello; Guilherme S. T. Garbino; Luiz H. Varzinczak; Deborah Faria; Marcelo d. M. Weber; Patricia Kerches Rogeri; André L. Regolin; Hernani F. M. d. Oliveira; Luciana d. M. Costa; et al. (Ecology, 2017)
Bats are the second most diverse mammal order and they provide vital ecosystem functions (e.g., pollination, seed dispersal, and nutrient flux in caves) and services (e.g., crop pest suppression). Bats are also important vectors of infectious diseases, harboring more than 100 different virus types. In the present study, we compiled information on bat communities from the Atlantic Forests of South America, a species‐rich biome that is highly threatened by habitat loss and fragmentation. The ATLANTIC BATS data set comprises 135 quantitative studies carried out in 205 sites, which cover most vegetation types of the tropical and subtropical Atlantic Forest: dense ombrophilous forest, mixed ombrophilous forest, semideciduous forest, deciduous forest, savanna, steppe, and open ombrophilous forest. The data set includes information on more than 90,000 captures of 98 bat species of eight families. Species richness averaged 12.1 per site, with a median value of 10 species (ranging from 1 to 53 species). Six species occurred in more than 50% of the communities: Artibeus lituratus , Carollia perspicillata , Sturnira lilium , Artibeus fimbriatus , Glossophaga soricina , and Platyrrhinus lineatus . The number of captures divided by sampling effort, a proxy for abundance, varied from 0.000001 to 0.77 individuals·h −1 ·m −2 (0.04 ± 0.007 individuals·h −1 ·m −2 ). Our data set reveals a hyper‐dominance of eight species that together that comprise 80% of all captures: Platyrrhinus lineatus (2.3%), Molossus molossus (2.8%), Artibeus obscurus (3.4%), Artibeus planirostris (5.2%), Artibeus fimbriatus (7%), Sturnira lilium (14.5%), Carollia perspicillata (15.6%), and Artibeus lituratus (29.2%).

ATLANTIC ‐ CAMTRAPS : a dataset of medium and large terrestrial mammal communities in the Atlantic Forest of South America - Fernando Lima; Gabrielle Beca; Renata L. Muylaert; Clinton N. Jenkins; Miriam L. L. Perilli; Ana Maria O. Paschoal; Rodrigo L. Massara; Adriano P. Paglia; Adriano G. Chiarello; Maurício E. Graipel; Jorge J. Cherem; André L. Regolin; et al. (Ecology, 2017)
Our understanding of mammal ecology has always been hindered by the difficulties of observing species in closed tropical forests. Camera trapping has become a major advance for monitoring terrestrial mammals in biodiversity rich ecosystems. Here we compiled one of the largest datasets of inventories of terrestrial mammal communities for the Neotropical region based on camera trapping studies. The dataset comprises 170 surveys of medium to large terrestrial mammals using camera traps conducted in 144 areas by 74 studies, covering six vegetation types of tropical and subtropical Atlantic Forest of South America (Brazil and Argentina), and present data on species composition and richness. The complete dataset comprises 53,438 independent records of 83 species of mammals, includes 10 species of marsupials, 15 rodents, 20 carnivores, eight ungulates and six armadillos. Species richness averaged 13 species (±6.07 SD ) per site. Only six species occurred in more than 50% of the sites: the domestic dog Canis familiaris , crab‐eating fox Cerdocyon thous , tayra Eira barbara , south American coati Nasua nasua , crab‐eating raccoon Procyon cancrivorus and the nine‐banded armadillo Dasypus novemcinctus . The information contained in this dataset can be used to understand macroecological patterns of biodiversity, community, and population structure, but also to evaluate the ecological consequences of fragmentation, defaunation, and trophic interactions.

Sodium thiosulphate attenuates brain inflammation induced by systemic lipopolysaccharide administration in C57BL/6J mice - Gonzalo Acero; Miryam Nava Catorce; Ricardo González-Mendoza; Marco Antonio Meraz-Rodríguez; Luis Fernando Hernández-Zimbron; Roberto González-Salinas; Goar Gevorkian (Inflammopharmacology, 2017)

Neurological involvement in patients with acute/recent HIV-1 infection. A case-control study - Juan Ambrosioni; Francisca Artigues; David Nicolás; Judit Peñafiel; Fernando Agüero; Christian Manzardo; María Mar Mosquera; Sonsoles Sánchez-Palomino; Elisa De Lazzari; María A. Marcos; Montserrat Plana; José M. Miró (Journal of NeuroVirology, 2017)

Early metallurgy in SE Iberia. The workshop of Las Pilas (Mojácar, Almería, Spain) - Mercedes Murillo-Barroso; Marcos Martinón-Torres; Mª Dolores Camalich Massieu; Dimas Martín Socas; Fernando Molina González (Archaeological and Anthropological Sciences, 2017)

Identifying, attributing, and overcoming common data quality issues of manned station observations - Stefan Hunziker; Stefanie Gubler; Juan Calle; Isabel Moreno; Marcos Andrade; Fernando Velarde; Laura Ticona; Gualberto Carrasco; Yaruska Castellón; Clara Oria; Mischa Croci‐Maspoli; Thomas Konzelmann; et al. (International Journal of Climatology, 2017)
In situ climatological observations are essential for studies related to climate trends and extreme events. However, in many regions of the globe, observational records are affected by a large number of data quality issues. Assessing and controlling the quality of such datasets is an important, often overlooked aspect of climate research. Besides analysing the measurement data, metadata are important for a comprehensive data quality assessment. However, metadata are often missing, but may partly be reconstructed by suitable actions such as station inspections. This study identifies and attributes the most important common data quality issues in Bolivian and Peruvian temperature and precipitation datasets. The same or similar errors are found in many other predominantly manned station networks worldwide. A large fraction of these issues can be traced back to measurement errors by the observers. Therefore, the most effective way to prevent errors is to strengthen the training of observers and to establish a near real‐time quality control ( QC ) procedure. Many common data quality issues are hardly detected by usual QC approaches. Data visualization, however, is an effective tool to identify and attribute those issues, and therefore enables data users to potentially correct errors and to decide which purposes are not affected by specific problems. The resulting increase in usable station records is particularly important in areas where station networks are sparse. In such networks, adequate selection and treatment of time series based on a comprehensive QC procedure may contribute to improving data homogeneity more than statistical data homogenization methods.

Variation in Copper Accumulation at the Tissue Level of Five Hybrid Poplars Subjected to Copper Stress - Jorge Cornejo; Jaime Tapia; Fernando Guerra; Marco Yáñez; Ricardo Baettig; Jorge Guajardo; Eduardo Alarcón; Gladys Vidal (Water, Air, & Soil Pollution, 2017)

Semi professional digital camera calibration techniques for Vis/NIR spectral data acquisition from an unmanned aerial vehicle - Luís Guilherme Teixeira Crusiol; Marcos Rafael Nanni; Guilherme Fernando Capristo Silva; Renato Herrig Furlanetto; Anderson Antonio da Silva Gualberto; Aline de Carvalho Gasparotto; Mariana Nunes De Paula (International Journal of Remote Sensing, 2017)

Determining the adiabatic temperature rise of concrete by inverse analysis: case study of a spillway gate pier - Eduardo M. R. Fairbairn; Marcos M. Silvoso; Fernando L. B. Ribeiro; Romildo D. Toledo-Filho (European Journal of Environmental and Civil Engineering, 2017)

Genetic correlation estimates between beef fatty acid profile with meat and carcass traits in Nellore cattle finished in feedlot - Fabieli Loise Braga Feitosa; Bianca Ferreira Olivieri; Carolyn Aboujaoude; Angélica Simone Cravo Pereira; Marcos Vinicius Antunes de Lemos; Hermenegildo Lucas Justino Chiaia; Mariana Piatto Berton; Elisa Peripolli; Adrielle Matias Ferrinho; Lenise Freitas Mueller; Mônica Roberta Mazalli; Lucia Galvão de Albuquerque; et al. (Journal of Applied Genetics, 2017)

Effects of protein–carbohydrate supplementation on immunity and resistance training outcomes: a double-blind, randomized, controlled clinical trial - Fernando Naclerio; Eneko Larumbe-Zabala; Nadia Ashrafi; Marco Seijo; Birthe Nielsen; Judith Allgrove; Conrad P. Earnest (European Journal of Applied Physiology, 2017)

Space-time modeling for post-fire vegetation recovery - Lucia Paci; Alan E. Gelfand; María Asunción Beamonte; Marcos Rodrigues; Fernando Pérez-Cabello (Stochastic Environmental Research and Risk Assessment, 2017)

Oxidative stress responses of Daphnia magna exposed to effluents spiked with emerging contaminants under ozonation and advanced oxidation processes - Ana Lourdes Oropesa; Sara C Novais; Marco F. L Lemos; Azahara Espejo; Carlos Gravato; Fernando Beltrán (Environmental Science and Pollution Research, 2017)

Variation in stem mortality rates determines patterns of above‐ground biomass in A mazonian forests: implications for dynamic global vegetation models - Michelle O. Johnson; David Galbraith; Manuel Gloor; Hannes De Deurwaerder; Matthieu Guimberteau; Anja Rammig; Kirsten Thonicke; Hans Verbeeck; Celso von Randow; Abel Monteagudo; Oliver L. Phillips; Roel J. W. Brienen; et al. (Global Change Biology, 2016)
Understanding the processes that determine above‐ground biomass ( AGB ) in Amazonian forests is important for predicting the sensitivity of these ecosystems to environmental change and for designing and evaluating dynamic global vegetation models ( DGVM s). AGB is determined by inputs from woody productivity [woody net primary productivity ( NPP )] and the rate at which carbon is lost through tree mortality. Here, we test whether two direct metrics of tree mortality (the absolute rate of woody biomass loss and the rate of stem mortality) and/or woody NPP , control variation in AGB among 167 plots in intact forest across Amazonia. We then compare these relationships and the observed variation in AGB and woody NPP with the predictions of four DGVM s. The observations show that stem mortality rates, rather than absolute rates of woody biomass loss, are the most important predictor of AGB , which is consistent with the importance of stand size structure for determining spatial variation in AGB . The relationship between stem mortality rates and AGB varies among different regions of Amazonia, indicating that variation in wood density and height/diameter relationships also influences AGB . In contrast to previous findings, we find that woody NPP is not correlated with stem mortality rates and is weakly positively correlated with AGB . Across the four models, basin‐wide average AGB is similar to the mean of the observations. However, the models consistently overestimate woody NPP and poorly represent the spatial patterns of both AGB and woody NPP estimated using plot data. In marked contrast to the observations, DGVM s typically show strong positive relationships between woody NPP and AGB . Resolving these differences will require incorporating forest size structure, mechanistic models of stem mortality and variation in functional composition in DGVM s.

Use of sugarcane filter cake and nitrogen, phosphorus and potassium fertilization in the process of bioremediation of soil contaminated with diesel - Fernando Reynel Fundora Tellechea; Marco Antônio Martins; Alexsandro Araujo da Silva; Emanuela Forestieri da Gama-Rodrigues; Meire Lelis Leal Martins (Environmental Science and Pollution Research, 2016)

Distribution of oxytocin and co-localization with arginine vasopressin in the brain of mice - Marcos Otero-García; Carmen Agustín-Pavón; Enrique Lanuza; Fernando Martínez-García (Brain Structure and Function, 2016)

Contributions of the mammal community, habitat structure, and spatial distance to dung beetle community structure - Juliano André Bogoni; Maurício Eduardo Graipel; Pedro Volkmer de Castilho; Felipe Moreli Fantacini; Vanessa Villanova Kuhnen; Micheli Ribeiro Luiz; Thiago Bernardes Maccarini; Cássio Batista Marcon; Christiane de Souza Pimentel Teixeira; Marcos Adriano Tortato; Fernando Z. Vaz-de-Mello; Malva Isabel Medina Hernández (Biodiversity and Conservation, 2016)

Patterns of land use, extensification, and intensification of Brazilian agriculture - Lívia C. P. Dias; Fernando M. Pimenta; Ana B. Santos; Marcos H. Costa; Richard J. Ladle (Global Change Biology, 2016)
Sustainable intensification of agriculture is one of the main strategies to provide global food security. However, its implementation raises enormous political, technological, and social challenges. Meeting these challenges will require, among other things, accurate information on the spatial and temporal patterns of agricultural land use and yield. Here, we investigate historical patterns of agricultural land use (1940–2012) and productivity (1990–2012) in Brazil using a new high‐resolution (approximately 1 km 2 ) spatially explicit reconstruction. Although Brazilian agriculture has been historically known for its extensification over natural vegetation (Amazon and Cerrado), data from recent years indicate that extensification has slowed down and was replaced by a strong trend of intensification. Our results provide the first comprehensive historical overview of agricultural land use and productivity in Brazil, providing clear insights to guide future territorial planning, sustainable agriculture, policy, and decision‐making.

Farmland biodiversity and agricultural management on 237 farms in 13 European and two African regions - Gisela Lüscher; Youssef Ammari; Aljona Andriets; Siyka Angelova; Michaela Arndorfer; Debra Bailey; Katalin Balázs; Marion Bogers; Robert G. H. Bunce; Jean‐Philippe Choisis; Peter Dennis; Mario Díaz; et al. (Ecology, 2016)
Farmland is a major land cover type in Europe and Africa and provides habitat for numerous species. The severe decline in farmland biodiversity of the last decades has been attributed to changes in farming practices, and organic and low‐input farming are assumed to mitigate detrimental effects of agricultural intensification on biodiversity. Since the farm enterprise is the primary unit of agricultural decision making, management‐related effects at the field scale need to be assessed at the farm level. Therefore, in this study, data were collected on habitat characteristics, vascular plant, earthworm, spider, and bee communities and on the corresponding agricultural management in 237 farms in 13 European and two African regions. In 15 environmental and agricultural homogeneous regions, 6–20 farms with the same farm type (e.g., arable crops, grassland, or specific permanent crops) were selected. If available, an equal number of organic and non‐organic farms were randomly selected. Alternatively, farms were sampled along a gradient of management intensity. For all selected farms, the entire farmed area was mapped, which resulted in total in the mapping of 11 338 units attributed to 194 standardized habitat types, provided together with additional descriptors. On each farm, one site per available habitat type was randomly selected for species diversity investigations. Species were sampled on 2115 sites and identified to the species level by expert taxonomists. Species lists and abundance estimates are provided for each site and sampling date (one date for plants and earthworms, three dates for spiders and bees). In addition, farmers provided information about their management practices in face‐to‐face interviews following a standardized questionnaire. Farm management indicators for each farm are available (e.g., nitrogen input, pesticide applications, or energy input). Analyses revealed a positive effect of unproductive areas and a negative effect of intensive management on biodiversity. Communities of the four taxonomic groups strongly differed in their response to habitat characteristics, agricultural management, and regional circumstances. The data has potential for further insights into interactions of farmland biodiversity and agricultural management at site, farm, and regional scale.

Lambing rate and prolificacy in inseminated hair sheep treated with bovine somatotropin - José Maria Carrera-Chávez; Joel Hernández-Cerón; Carlos Fernando Aréchiga-Flores; Marco Antonio López-Carlos; Raúl Renato Lozano-Domínguez; Andrés Quezada-Casasola; Francisco Guadalupe Echavarría-Cháirez (Tropical Animal Health and Production, 2016)

A constitutive expression system for Pichia pastoris based on the PGK1 promoter - Andrelisse Arruda; Viviane Castelo Branco Reis; Vinícius Daniel Ferreira Batista; Bruno Sahim Daher; Luiza Cesca Piva; Janice Lisboa De Marco; Lidia Maria Pepe de Moraes; Fernando Araripe Gonçalves Torres (Biotechnology Letters, 2016)

Afferent projections to the different medial amygdala subdivisions: a retrograde tracing study in the mouse - Bernardita Cádiz-Moretti; Marcos Otero-García; Fernando Martínez-García; Enrique Lanuza (Brain Structure and Function, 2016)

Physiological and sanitary condition of the white clam Dosinia ponderosa collected from a coastal area impacted by shrimp farm effluent - Marcel Martínez-Porchas; Susana Maria Scheuren-Acevedo; Luis Rafael Martínez-Córdova; Teresa Gollas-Galvan; Ramon H. Barraza-Guardado; Fernando Enríquez-Ocaña; Edilmar Cortés-Jacinto; Marco A. Porchas-Cornejo (Aquaculture International, 2016)

Ottensite, brizziite and mopungite from Pereta mine (Tuscany, Italy): new occurrences and crystal structure refinement of mopungite - Erica Bittarello; Fernando Cámara; Marco E. Ciriotti; Alessandra Marengo (Mineralogy and Petrology, 2015)

Genetic Effects of eNOS Polymorphisms on Biomarkers Related to Cardiovascular Status in a Population Coexposed to Methylmercury and Lead - Gustavo Rafael Mazzaron Barcelos; Kátia Cristina De Marco; Vânia Braghini de Rezende; Gilberto Úbida Leite Braga; Lusânia Maria Greggi Antunes; José Eduardo Tanus-Santos; Fernando Barbosa (Archives of Environmental Contamination and Toxicology, 2015)

Phytotoxicity and Identification of Secondary Metabolites of Sapindus saponaria L. Leaf Extract - Patrícia Umeda Grisi; Moacir Rossi Forim; Eveline Soares Costa; Simoni Anese; Marcos Fernando Franco; Marcos Nogueira Eberlin; Sônia Cristina Juliano Gualtieri (Journal of Plant Growth Regulation, 2015)

CTT1 overexpression increases life span of calorie-restricted Saccharomyces cerevisiae deficient in Sod1 - Germana Rona; Ricardo Herdeiro; Cristiane Juliano Mathias; Fernando Araripe Torres; Marcos Dias Pereira; Elis Eleutherio (Biogerontology, 2015)

Relationship between honeybee nutrition and their microbial communities - Miriane Acosta Saraiva; Ana Paula Pegoraro Zemolin; Jeferson Luis Franco; Juliano Tomazzoni Boldo; Valdir Marcos Stefenon; Eric W. Triplett; Flávio Anastácio de Oliveira Camargo; Luiz Fernando Wurdig Roesch (Antonie van Leeuwenhoek, 2015)

The Monviso Massif and the Cottian Alps as Symbols of the Alpine Chain and Geological Heritage in Piemonte, Italy - Franco Rolfo; Piera Benna; Paola Cadoppi; Daniele Castelli; Sergio E. Favero-Longo; Marco Giardino; Gianni Balestro; Elena Belluso; Alessandro Borghi; Fernando Cámara; Roberto Compagnoni; Simona Ferrando; et al. (Geoheritage, 2015)

Retinal‐binding proteins mirror prokaryotic dynamics in multipond solar salterns - María Gomariz; Manuel Martínez‐García; Fernando Santos; Marco Constantino; Inmaculada Meseguer; Josefa Antón (Environmental Microbiology, 2015)
Summary Microbial opsin (i.e. retinal‐binding protein) dynamics has been studied along a salinity gradient in S anta P ola solar salterns ( A licante, S pain) by using culture‐independent approaches and statistical analyses. Five ponds of salinities ranging from 18% to above 40% were sampled nine times along a year. Forty‐three opsin‐like sequences were retrieved by denaturing gradient gel electrophoresis and clustered into 18 different phylogroups, indicating that their diversity was higher than expected according to previous data. Moreover, the statistical correlation between environmental factors controlling microbial community structure and dynamics of environmental rhodopsin proteins indicated almost identical temporal fluctuations between the opsin‐related sequences and their corresponding putative ‘producers’ in nature. Although most sequences were related to others previously detected in hypersaline environments, some pond‐specific opsins putatively belonged to previously uncharacterized hosts. Furthermore, we propose that subtle changes in the bacteriorhodopsin ‘retinal proton binding pocket’, which is key in the photocycle function, could be the molecular basis behind a fine ‘photocycle‐tuning’ mechanism to avoid inter/intraspecies light‐competition in hypersaline environments.

Sugarcane performance under phosphorus deficiency: physiological responses and genotypic variation - Fernando C. Bachiega Zambrosi; Rafael Vasconcelos Ribeiro; Paulo E. Ribeiro Marchiori; Heitor Cantarella; Marcos G. Andrade Landell (Plant and Soil, 2015)

A Critical Comparison of Different Approaches to Sediment-Quality Assessments in the Santos Estuarine System in Brazil - Ronaldo J. Torres; Augusto Cesar; Victor A. Pastor; Camilo D. S. Pereira; Rodrigo B. Choueri; Fernando S. Cortez; Rodofley D. Morais; Denis M. S. Abessa; Marcos R. L. do Nascimento; Cassia R. Morais; Pedro S. Fadini; Tomas A. Del Valls Casillas; et al. (Archives of Environmental Contamination and Toxicology, 2015)

Colitis generates remote antinociception in rats: the role of the l-arginine/NO/cGMP/PKG/KATP pathway and involvement of cannabinoid and opioid systems - André Luiz dos Reis Barbosa; Rhamon Barroso de Sousa; João Nathanael Lima Torres; Thiago Mattar Cunha; Fernando de Queiroz Cunha; Pedro Marcos Gomes Soares; Ronaldo de Albuquerque Ribeiro; Mariana Lima Vale; Marcellus Henrique Loiola Ponte Souza (Inflammation Research, 2014)

Markedly divergent estimates of A mazon forest carbon density from ground plots and satellites - Edward T. A. Mitchard; Ted R. Feldpausch; Roel J. W. Brienen; Gabriela Lopez‐Gonzalez; Abel Monteagudo; Timothy R. Baker; Simon L. Lewis; Jon Lloyd; Carlos A. Quesada; Manuel Gloor; Hans ter Steege; Patrick Meir; et al. (Global Ecology and Biogeography, 2014)
Aim The accurate mapping of forest carbon stocks is essential for understanding the global carbon cycle, for assessing emissions from deforestation, and for rational land‐use planning. Remote sensing ( RS ) is currently the key tool for this purpose, but RS does not estimate vegetation biomass directly, and thus may miss significant spatial variations in forest structure. We test the stated accuracy of pantropical carbon maps using a large independent field dataset. Location Tropical forests of the A mazon basin. The permanent archive of the field plot data can be accessed at: http://dx.doi.org/10.5521/FORESTPLOTS.NET/2014_1 Methods Two recent pantropical RS maps of vegetation carbon are compared to a unique ground‐plot dataset, involving tree measurements in 413 large inventory plots located in nine countries. The RS maps were compared directly to field plots, and kriging of the field data was used to allow area‐based comparisons. Results The two RS carbon maps fail to capture the main gradient in Amazon forest carbon detected using 413 ground plots, from the densely wooded tall forests of the north‐east, to the light‐wooded, shorter forests of the south‐west. The differences between plots and RS maps far exceed the uncertainties given in these studies, with whole regions over‐ or under‐estimated by > 25%, whereas regional uncertainties for the maps were reported to be Main conclusions Pantropical biomass maps are widely used by governments and by projects aiming to reduce deforestation using carbon offsets, but may have significant regional biases. Carbon‐mapping techniques must be revised to account for the known ecological variation in tree wood density and allometry to create maps suitable for carbon accounting. The use of single relationships between tree canopy height and above‐ground biomass inevitably yields large, spatially correlated errors. This presents a significant challenge to both the forest conservation and remote sensing communities, because neither wood density nor species assemblages can be reliably mapped from space.

Seven years of negative detection results confirm that Xylella fastidiosa, the causal agent of CVC, is not transmitted from seeds to seedlings - Helvécio Della Coletta-Filho; Sérgio Alves Carvalho; Luis Fernando Carvalho Silva; Marcos Antonio Machado (European Journal of Plant Pathology, 2014)

The effect of sex and genotype on growth performance, feed efficiency, and carcass traits of local sheep group Pantaneiro and Texel or Santa Inês crossbred finished on feedlot - Fernando Miranda de Vargas Junior; Charles Ferreira Martins; Guilherme dos Santos Pinto; Marcos Barbosa Ferreira; Hélio de Almeida Ricardo; André Gustavo Leão; Alexandre Rodrigo Mendes Fernandes; Alfredo Teixeira (Tropical Animal Health and Production, 2014)

Extending the socio-sexual brain: arginine-vasopressin immunoreactive circuits in the telencephalon of mice - Marcos Otero-Garcia; Ana Martin-Sanchez; Lluis Fortes-Marco; Joana Martínez-Ricós; Carmen Agustin-Pavón; Enrique Lanuza; Fernando Martínez-García (Brain Structure and Function, 2014)

Isolation, prevalence, and risk factors for infection by shiga toxin-producing Escherichia coli (STEC) in dairy cattle - Marcos Roberto Alves Ferreira; Edismauro Garcia Freitas Filho; Jefferson Fernando Naves Pinto; Márcia Dias; Cecília Nunes Moreira (Tropical Animal Health and Production, 2014)

Therapeutic potential of biodegradable microparticles containing Punica granatum L. (pomegranate) in murine model of asthma - Jéssica F. F. de Oliveira; Diego V. Garreto; Mayara C. P. da Silva; Thiare S. Fortes; Rejane B. de Oliveira; Flávia R. F. Nascimento; Fernando B. Da Costa; Marcos A. G. Grisotto; Roberto Nicolete (Inflammation Research, 2013)

Disturbances, elevation, topography and spatial proximity drive vegetation patterns along an altitudinal gradient of a top biodiversity hotspot - Pedro V. Eisenlohr; Luciana F. Alves; Luís Carlos Bernacci; Maíra C. G. Padgurschi; Roseli B. Torres; Eduardo M. B. Prata; Flavio Antonio M. dos Santos; Marco Antônio Assis; Eliana Ramos; André Luís C. Rochelle; Fernando R. Martins; Mariana C. R. Campos; et al. (Biodiversity and Conservation, 2013)

Workshop on life cycle sustainability assessment: the state of the art and research needs—November 26, 2012, Copenhagen, Denmark - Marco Cinelli; Stuart R. Coles; Andreas Jørgensen; Alessandra Zamagni; Chalaka Fernando; Kerry Kirwan (The International Journal of Life Cycle Assessment, 2013)

Is a neutral expression also a neutral stimulus? A study with functional magnetic resonance - Fernando Carvajal; Sandra Rubio; Juan M. Serrano; Marcos Ríos-Lago; Juan Alvarez-Linera; Lara Pacheco; Pilar Martín (Experimental Brain Research, 2013)

Mercury Toxicity to Freshwater Organisms: Extrapolation Using Species Sensitivity Distribution - Andreia C. M. Rodrigues; Fátima T. Jesus; Marco A. F. Fernandes; Fernando Morgado; Amadeu M. V. M. Soares; Sizenando N. Abreu (Bulletin of Environmental Contamination and Toxicology, 2013)

Moderate exercise increases the metabolism and immune function of lymphocytes in rats - Francisco Navarro; Aline Villa Nova Bacurau; Guilherme Borges Pereira; Ronaldo Carvalho Araújo; Sandro Soares Almeida; Milton Rocha Moraes; Marco Carlos Uchida; Luis Fernando Bicudo Pereira Costa Rosa; James Navalta; Jonato Prestes; Reury Frank Pereira Bacurau (European Journal of Applied Physiology, 2013)

Growth and chlorophyll a fluorescence in Erythrina crista-galli L. plants under flooding conditions - Cristina F. Larré; Juliana A. Fernando; Patricia Marini; Marcos A. Bacarin; José A. Peters (Acta Physiologiae Plantarum, 2013)

Anti-inflammatory and Immunomodulatory Effect of an Extract of Coccidioides posadasii in Experimental Arthritis - Ana Carolina Matias Dinelly Pinto; Rossana de Aguiar Cordeiro; José Julio Costa Sidrim; Ana Karine Rocha de Melo Leite; Ana Caroline Rocha de Melo Leite; Virgínia Cláudia Carneiro Girão; Raimunda Sâmia Nogueira Brilhante; Marcos Fábio Gadelha Rocha; Fernando de Queiroz Cunha; Francisco Airton Castro Rocha (Mycopathologia, 2013)

Swimming behaviour of the multicellular magnetotactic prokaryote ‘Candidatus Magnetoglobus multicellularis’ under applied magnetic fields and ultraviolet light - Fernando P. Almeida; Nathan B. Viana; Ulysses Lins; Marcos Farina; Carolina N. Keim (Antonie van Leeuwenhoek, 2013)

Determination of antibacterial activity of vacuum distillation fractions of lemongrass essential oil - Manuel A. Falcão; Ana L. B. Fianco; Aline M. Lucas; Marcos A. A. Pereira; Fernando C. Torres; Rubem M. F. Vargas; Eduardo Cassel (Phytochemistry Reviews, 2012)

Genetic diversity in widespread species is not congruent with species richness in alpine plant communities - Pierre Taberlet; Niklaus E. Zimmermann; Thorsten Englisch; Andreas Tribsch; Rolf Holderegger; Nadir Alvarez; Harald Niklfeld; Gheorghe Coldea; Zbigniew Mirek; Atte Moilanen; Wolfgang Ahlmer; Paolo Ajmone Marsan; et al. (Ecology Letters, 2012)
The Convention on Biological Diversity ( CBD ) aims at the conservation of all three levels of biodiversity, that is, ecosystems, species and genes. Genetic diversity represents evolutionary potential and is important for ecosystem functioning. Unfortunately, genetic diversity in natural populations is hardly considered in conservation strategies because it is difficult to measure and has been hypothesised to co‐vary with species richness. This means that species richness is taken as a surrogate of genetic diversity in conservation planning, though their relationship has not been properly evaluated. We tested whether the genetic and species levels of biodiversity co‐vary, using a large‐scale and multi‐species approach. We chose the high‐mountain flora of the Alps and the Carpathians as study systems and demonstrate that species richness and genetic diversity are not correlated. Species richness thus cannot act as a surrogate for genetic diversity. Our results have important consequences for implementing the CBD when designing conservation strategies.

Respiratory responses of three Antarctic ascidians and a sea pen to increased sediment concentrations - Luciana Torre; Natalia Servetto; Matias Leonel Eöry; Fernando Momo; Marcos Tatián; Doris Abele; Ricardo Sahade (Polar Biology, 2012)

Invasive Africanized honeybees change the structure of native pollination networks in Brazil - Gilberto M. de M. Santos; Cândida M. L. Aguiar; Julieta Genini; Celso F. Martins; Fernando C. V. Zanella; Marco A. R. Mello (Biological Invasions, 2012)

Searching for Euglossa cyanochlora Moure, 1996 (Hymenoptera: Apidae), one of the rarest bees in the world - André Nemésio; Natália de C. M. Cerântola; Heraldo L. Vasconcelos; João Carlos Nabout; Fernando A. Silveira; Marco A. Del Lama (Journal of Insect Conservation, 2012)

The Phaseolus vulgaris miR159a precursor encodes a second differentially expressed microRNA - Cecilia Contreras-Cubas; Fernando A. Rabanal; Catalina Arenas-Huertero; Marco A. Ortiz; Alejandra A. Covarrubias; José Luis Reyes (Plant Molecular Biology, 2012)

Occurrence of the Non‐Native Annual Bluegrass on the Antarctic Mainland and Its Negative Effects on Native Plants - MARCO A. MOLINA‐MONTENEGRO; FERNANDO CARRASCO‐URRA; CRISTIAN RODRIGO; PETER CONVEY; FERNANDO VALLADARES; ERNESTO GIANOLI (Conservation Biology, 2012)
Few non‐native species have colonized Antarctica, although increased human activity and accelerated climate change may increase their number, distributional range, and effects on native species on the continent. We searched 13 sites on the maritime Antarctic islands and 12 sites on the Antarctic Peninsula for annual bluegrass (Poa annua), a non‐native flowering plant. We also evaluated the possible effects of competition between P. annua and 2 vascular plants native to Antarctica, Antarctic pearlwort (Colobanthus quitensis) and Antarctic hairgrass (Deschampsia antarctica). We grew the native species in experimental plots with and without annual bluegrass under conditions that mimicked the Antarctic environment. After 5 months, we measured photosynthetic performance on the basis of chlorophyll fluorescence and determined total biomass of both native species. We found individual specimens of annual bluegrass at 3 different sites on the Antarctic Peninsula during the 2007–2008 and 2009–2010 austral summers. The presence of bluegrass was associated with a statistically significant reduction in biomass of pearlwort and hairgrass, whereas the decrease in biomass of bluegrass was not statistically significant. Similarly, the presence of bluegrass significantly reduced the photosynthetic performance of the 2 native species. Sites where bluegrass occurred were close to major maritime routes of scientific expeditions and of tourist cruises to Antarctica. We believe that if current levels of human activity and regional warming persist, more non‐native plant species are likely to colonize the Antarctic and may affect native species.

Chemotypical variation in Vanilla planifolia Jack. (Orchidaceae) from the Puebla-Veracruz Totonacapan region - Víctor Manuel Salazar-Rojas; B. Edgar Herrera-Cabrera; Adriana Delgado-Alvarado; Marcos Soto-Hernández; Fernando Castillo-González; Mario Cobos-Peralta (Genetic Resources and Crop Evolution, 2012)

Silver Discharged in Effluents from Image-Processing Services: a Risk to Human and Environmental Health - Jamyle Calencio Grigoletto; Susana Inés Segura-Muñoz; Fernando Barbosa-Junior; Sérgio Marcos Sanches; Angela Maria Magosso Takayanagui (Biological Trace Element Research, 2011)

Determination of Antibiotics in Brazilian Surface Waters Using Liquid Chromatography–Electrospray Tandem Mass Spectrometry - Marco Antonio F. Locatelli; Fernando F. Sodré; Wilson F. Jardim (Archives of Environmental Contamination and Toxicology, 2011)

Sugarcane (Saccharum X officinarum): A Reference Study for the Regulation of Genetically Modified Cultivars in Brazil - Adriana Cheavegatti-Gianotto; Hellen Marília Couto de Abreu; Paulo Arruda; João Carlos Bespalhok Filho; William Lee Burnquist; Silvana Creste; Luciana di Ciero; Jesus Aparecido Ferro; Antônio Vargas de Oliveira Figueira; Tarciso de Sousa Filgueiras; Mária de Fátima Grossi-de-Sá; Elio Cesar Guzzo; et al. (Tropical Plant Biology, 2011)

Monitoring of resistance or susceptibility of adults and larvae of Amblyomma cajennense (Acari: Ixodidae) to synthetic acaricides in Goiás, Brazil - Edméia de Paula e Souza Freitas; Marco Túlio Antônio Garcia Zapata; Fernando de Freitas Fernandes (Experimental and Applied Acarology, 2011)

FPGA computation of the 3D heat equation - Fernando Pardo; Paula López; Diego Cabello; Marco Balsi (Computational Geosciences, 2010)

Environmental influence on urban rodent bait consumption - Matteo Patergnani; Lapo Mughini Gras; Giovanni Poglayen; Aldo Gelli; Fernando Pasqualucci; Marco Farina; Laura Stancampiano (Journal of Pest Science, 2010)

Reduction of ICAM-1 expression by carbon monoxide via soluble guanylate cyclase activation accounts for modulation of neutrophil migration - Daniela Dal-Secco; Andressa Freitas; Monica A. Abreu; Thiago P. Garlet; Marcos A. Rossi; Sérgio H. Ferreira; João S. Silva; José C. Alves-Filho; Fernando Q. Cunha (Naunyn-Schmiedeberg's Archives of Pharmacology, 2010)

Development of secondary palate requires strict regulation of ECM remodeling: sequential distribution of RECK, MMP-2, MMP-3, and MMP-9 - Ana Claudia Cardoso de Oliveira Demarchi; Willian Fernando Zambuzzi; Katiúcia Batista Silva Paiva; Maria das Graças da Silva-Valenzuela; Fabio Daumas Nunes; Rita de Cássia Sávio Figueira; Regina Maki Sasahara; Marcos Angelo Almeida Demasi; Sheila Maria Brochado Winnischofer; Mari Cleide Sogayar; José Mauro Granjeiro (Cell and Tissue Research, 2010)

Modulation of inflammatory response by selective inhibition of cyclooxygenase-1 and cyclooxygenase-2 in acute kidney injury - Carla Q. Feitoza; Patricia Semedo; Giselle M. Gonçalves; Marcos A. Cenedeze; Hélady S. Pinheiro; Oscar Fernando Pavão dos Santos; Richardt Gama Landgraf; Alvaro Pacheco-Silva; Niels Olsen Saraiva Câmara (Inflammation Research, 2010)

Occurrence of Emerging Contaminants in Brazilian Drinking Waters: A Sewage-To-Tap Issue - Fernando F. Sodré; Marco Antonio F. Locatelli; Wilson F. Jardim (Water, Air, & Soil Pollution, 2010)

Effects of dredging operations on sediment quality: contaminant mobilization in dredged sediments from the Port of Santos, SP, Brazil - Ronaldo J. Torres; Denis M. S. Abessa; Fernando C. Santos; Luciane A. Maranho; Marcela B. Davanso; Marcos R. L. do Nascimento; Antonio A. Mozeto (Journal of Soils and Sediments, 2009)

Effect of exercise on glutamine metabolism in macrophages of trained rats - Ronaldo Vagner Thomatieli dos Santos; Érico Chagas Caperuto; Marco Túlio de Mello; Luis Fernando Bicudo Pereira Costa Rosa (European Journal of Applied Physiology, 2009)

Tree species composition and environmental relationships in a Neotropical swamp forest in Southeastern Brazil - Aloysio de P. Teixeira; Marco A. Assis; Fernando R. Siqueira; José C. Casagrande (Wetlands Ecology and Management, 2008)

N-Methylation of N α-Acetylated, Fully Cα-Ethylated, Linear Peptides - Alessandro Moretto; Marta De Zotti; Marco Crisma; Fernando Formaggio; Claudio Toniolo (International Journal of Peptide Research and Therapeutics, 2008)

Hematologic Values of Free-ranging Cebus cay and Cebus nigritus in Southern Brazil - Karina Keller Marques da Costa Flaiban; Kledir Anderson H. Spohr; Luciano de Souza Malanski; Walfrido Kühl Svoboda; Marcos M. Shiozawa; Carmen Lúcia S. Hilst; Lucas Moraes Aguiar; Gabriela Ludwig; Fernando C. Passos; Italmar Teodorico Navarro; Mara Regina Stipp Balarin; Júlio Augusto Naylor Lisbôa (International Journal of Primatology, 2008)

Copper, Iron, and Zinc Status in Children with Moderate and Severe Acute Malnutrition Recovered Following WHO Protocols - Gerardo Weisstaub; Marcos Medina; Fernando Pizarro; Magdalena Araya (Biological Trace Element Research, 2008)

The effect of human use of sandy beaches on developmental stability of Talitrus saltator (Montagu, 1808) (Crustacea, Amphipoda). A study on fluctuating asymmetry - Sandra Barca‐Bravo; María J. Servia; Fernando Cobo; Marcos A. Gonzalez (Marine Ecology, 2008)
In recent years, there has been an increasing intensity of human use of coastal areas in Galicia (NW Spain). Actually, there is great concern about rapid and unplanned urban and industrial development on certain locations, as this can generate adverse impacts on those areas. In this study, we selected three sandy beaches along the Galician coast (Chanteiro, Insuela and Valieros) facing different levels of anthropic pressure, and we analysed Talitrus saltator individuals with the aim of elucidating whether anthropogenic pressures on beaches such as tourism or pollution have an influence on the incidence of morphological developmental alterations in sandhoppers in the field. Specifically, levels of fluctuating asymmetry were selected as indicators of environmental stress. Results of two sampling dates (May and September) show that individuals collected at the most touristy and polluted beach were those showing the highest asymmetry values, although results were only statistically significant for samples collected during spring. Results are in accordance with the hypothesis that beach management and pollution reduce symmetry in sandhoppers living in altered beaches.

Copper and Liver Function Indicators Vary Depending on the Female Hormonal Cycle and Serum Hormone Binding Globulin (SHBG) Concentration in Healthy Women - Mariana Ayala; Fernando Pizarro; Marco A. Méndez; Miguel Arredondo; Magdalena Araya (Biological Trace Element Research, 2008)

A Quantitative Method for Modeling Blend Composition Distributions in the Presence of Agglomerates - Marcos Llusa; Fernando Muzzio (Journal of Pharmaceutical Innovation, 2007)

Case study of complaints on drinking water quality - Fernando Pizarro; Magdalena Araya; Marcela Vásquez; Gustavo Lagos; Manuel Olivares; Marco A. Méndez; Bárbara Leyton; Arturo Reyes; Victoria Letelier; Ricardo Uauy (Biological Trace Element Research, 2007)

Case study of complaints on drinking water quality - Fernando Pizarro; Magdalena Araya; Marcela Vásquez; Gustavo Lagos; Manuel Olivares; Marco A. Méndez; Bárbara Leyton; Arturo Reyes; Victoria Letelier; Ricardo Uauy (Biological Trace Element Research, 2007)

MIGRATORY DESTINATIONS OF HUMPBACK WHALES FROM THE MAGELLAN STRAIT FEEDING GROUND, SOUTHEAST PACIFIC - Jorge Acevedo; Kristin Rasmussen; Fernando Félix; Cristina Castro; Martha Llano; Eduardo Secchi; Marco T. Saborío; Anelio Aguayo‐Lobo; Ben Haase; Meike Scheidat; Luciano Dalla‐Rosa; Carlos Olavarría; et al. (Marine Mammal Science, 2007)

Cougar Predation on Black-and-Gold Howlers on Mutum Island, Southern Brazil1 - Gabriela Ludwig; Lucas M. Aguiar; João M. D. Miranda; Gustavo M. Teixeira; Walfrido K. Svoboda; Luciano S. Malanski; Marcos M. Shiozawa; Carmen L. S. Hilst; Italmar T. Navarro; Fernando C. Passos (International Journal of Primatology, 2007)

Techniques and Trap Models for Capturing Wild Tufted Capuchins - Vlamir J. Rocha; Lucas M. Aguiar; Gabriela Ludwig; Carmen L. S. Hilst; Gustavo M. Teixeira; Walfrido K. Svoboda; Marcos M. Shiozawa; Luciano S. Malanski; Italmar T. Navarro; José Hernan F. Mariño; Fernando C. Passos (International Journal of Primatology, 2007)

Changes in Copper Speciation and Geochemical Fate in Freshwaters Following Sewage Discharges - Fernando F. Sodré; Marco T. Grassi (Water, Air, & Soil Pollution, 2007)

Stem tilting, pseudocephalium orientation, and stem allometry in Cephalocereus columna-trajani along a short latitudinal gradient - Pedro Luis Valverde; Fernando Vite; Marco Aurelio Pérez-Hernández; José Alejandro Zavala-Hurtado (Plant Ecology, 2006)

The Complete Nucleotide Sequence and Genomic Organization of Citrus Leprosis Associated Virus, Cytoplasmatic type (CiLV-C) - Renata C. Pascon; João Paulo Kitajima; Michèle C. Breton; Laura Assumpção; Christian Greggio; Almir S. Zanca; Vagner Katsumi Okura; Marcos C. Alegria; Maria E. Camargo; Giovana G.C. Silva; Jussara C. Cardozo; Marcelo A. Vallim; et al. (Virus Genes, 2006)

Functional Neuroimaging Studies of Cognitive Recovery After Acquired Brain Damage in Adults - Juan M. Muñoz-Cespedes; Marcos Rios-Lago; Nuria Paul; Fernando Maestu (Neuropsychology Review, 2005)

Effects of azadirachtin on the two-spotted spider mite, Tetranychus urticae (Acari: Tetranychidae) - Elena Martínez-Villar; Francisco J. Sáenz-De-Cabezón; Fernando Moreno-Grijalba; Vicente Marco; Ignacio Pérez-Moreno (Experimental and Applied Acarology, 2005)

Effects of Short-Term Climatic Variations on Fluctuating Asymmetry Levels in Chironomus Riparius Larvae at a Polluted Site - María J. Servia; Fernando Cobo; Marcos A. González (Hydrobiologia, 2004)

Comparison of the mass and energy exchange of a pasture and a mature transitional tropical forest of the southern Amazon Basin during a seasonal transition - Nicolau Priante‐Filho; George L. Vourlitis; Mauro Massao Shiota Hayashi; José De Souza Nogueira; José Holanda Campelo; Paulo César Nunes; Luciana Sanches E Souza; Eduardo Guimarães Couto; Wander Hoeger; Fernando Raiter; Jansen Luiz Trienweiler; Eduardo Jacusiel Miranda; et al. (Global Change Biology, 2004)
This research utilized tower‐based eddy covariance to quantify the trends in net ecosystem mass (CO 2 and H 2 O vapor) and energy exchange of important land‐cover types of NW Mato Grosso during the March–December 2002 seasonal transition. Measurements were made in a mature transitional (ecotonal) tropical forest near Sinop, Mato Grosso, and a cattle pasture near Cotriguaçú, Mato Grosso, located 500 km WNW of Sinop. Pasture net ecosystem CO 2 exchange (NEE) was considerably more variable than the forest NEE over the seasonal transition, and the pasture had significantly higher rates of maximum gross primary production in every season except the dry–wet season transition (September–October). The pasture also had significantly higher rates of whole‐ecosystem dark respiration than the forest during the wetter times of the year. Average (±95% CI) rates of total daily NEE during the March–December 2002 measurement period were 26±15 mmol m −2 day −1 for the forest (positive values indicate net CO 2 loss by the ecosystem) and −38±26 mmol m −2 day −1 for the pasture. While both ecosystems partitioned more net radiation ( R n ) into latent heat flux ( L e ), the forest had significantly higher rates of L e and lower rates of sensible heat flux ( H ) than the pasture; a trend that became more extreme during the onset of the dry season. Large differences in pasture and forest mass and energy exchange occurred even though seasonal variations in micrometeorology (air temperature, humidity, and radiation) were relatively similar for both ecosystems. While the short measurement period and lack of spatial replication limit the ability to generalize these results to pasture and forest regions of the Amazon Basin, these results suggest important differences in the magnitude and seasonal variation of NEE and energy partitioning for pasture and transitional tropical forest.

Arsenic and Heavy Metal Pollution of Soil, Water and Sediments in a Semi-Arid Climate Mining Area in Mexico - Israel Razo; Leticia Carrizales; Javier Castro; Fernando Díaz-Barriga; Marcos Monroy (Water, Air, & Soil Pollution, 2004)

U-Pb evidence for a polyorogenic evolution of the HP-HT units of the NW Iberian Massif - Javier Fernández-Suárez; Fernando Corfu; Ricardo Arenas; Alberto Marcos; José Martínez Catalán; Florentino García; Jacobo Abati; Francisco Fernández (Contributions to Mineralogy and Petrology, 2002)

Evaluating Potential Effects of Exotic Freshwater Fish From Incomplete Species Presence–absence Data - Miguel Pascual; Patricio Macchi; Javier Urbanski; Fernando Marcos; Carla Riva Rossi; Mauro Novara; Patricia Dell'Arciprete (Biological Invasions, 2002)

Silphinene Sesquiterpenes as Model Insect Antifeedants - Azucena González-Coloma; Fernando Valencia; Nuria Martín; Joseph J. Hoffmann; Louis Hutter; J. Alberto Marco; Matías Reina (Journal of Chemical Ecology, 2002)

Reactive intermediates in peptide synthesis: Molecular and crystal structures of HOAt and HOOBt, and some ester and amide derivatives of HOBt, HOAt and HOOBt - Marco Crisma; Giovanni Valle; Vittorio Moretto; Fernando Formaggio; Claudio Toniolo; Fernando Albericio (International Journal of Peptide Research and Therapeutics, 1998)

Cα-methyl phenylglycine-based semi-synthetic ampicillin and cephalexin analogues - Eric Mossel; Fernando Formaggio; Marco Crisma; Claudio Toniolo; Theo Sonke; Eric C. Roos; Quirinus B. Broxterman; Johan Kamphuis (International Journal of Peptide Research and Therapeutics, 1998)

Crystallographic structure of a helical lipopeptaibol antibiotic analogue - Marco Crisma; Vania Monaco; Fernando Formaggio; Claudio Toniolo; Clifford George; Judith L. Flippen-Anderson (International Journal of Peptide Research and Therapeutics, 1997)

s of papers presented at the 81st annual meeting of The Potato Association of America Charlottetown, P.E.I., Canada August 3 – 7, 1997 - S. T. Ali-Khan; C. Hetner; L. Ladislav; V. Currie; Walter J. Arsenault; A. Naseer Aziz; Janet E. A. Seabrook; George C. C. Tai; J. B. Bamberg; Alfonso H. del Rio; Max Martin; J. B. Bamberg; et al. (American Journal of Potato Research, 1997)